Low-temperature stress reshapes hepatic metabolic profiles in cultured Epinephelus akaara - Jichun Li; Rui Zhao; Hongling Ping; Tao Zhang; Huilai Shi; Longbo Gao; Bin Lu; Bin Li; Yingying Ye; Jiji Li; Jianshe Zhang (Aquaculture, 2027)

Baseline levels and spatial distribution of arsenic species in surface sediments of the East China Sea shelf - Tianyu Bian; Xiaoyong Duan; Bin Chen; Xingliang He; Shenghua Lv; Meina Li; Ke Cao; Fei Gao; Ping Yin (Marine Pollution Bulletin, 2026)

Electron pump-shuttle cathode enables coupled directed-electron flows for resource-oriented treatment of radioactive wastewater - Xijun Fu; Shuai Gao; Haodong Ji; Yanbiao Liu; Sujie Yang; Binsheng He; Ping Cao; Qingyan Zhang; Le Li; Yifeng Hu; Qingyi Zeng (Water Research, 2026)

No-tillage straw mulching alters fallow rainfall use and improves long-term water balance and yield stability of winter wheat: A 38-year simulation on the Loess Plateau - Xinrui Shi; Chao Li; Chen Cui; Ping Li; Yuzheng Zong; Dongsheng Zhang; Zhiqiang Gao; Xingyu Hao (Agricultural Systems, 2026)

Beyond gastroenteritis: first evidence of systemic biochemical disturbances, predominantly coagulation dysfunction, in Neoboletus poisoning - Jia Li; Yuan-Tian Lu; Xiu-Juan Li; Ming Li; Ping Wei; Tai-Jie Yu; Yu-Xian Gao; Ting Li; Yuan-Yuan Xiong; Yi Liu; Li-Ping Tang (Toxicon, 2026)

Acute liver injury and facial edema following ingestion of mushroom Descolea quercina - Ting Li; Xiu-Juan Li; Tai-Jie Yu; Wen-Hao Zhang; Yuan-Tian Lu; Yu-Xian Gao; Yuan-Yuan Xiong; Jun Gao; Yi Liu; Li-Ping Tang (Toxicon, 2026)

Columnar optical properties of locally emitted light-absorbing carbonaceous aerosols - Kang Hu; Hong Liao; Dantong Liu; Jianbing Jin; Siyuan Li; Yangzhou Wu; Yuxing Gao; Xiaotong Jiang; Shitong Zhao; Ping Tian; Fei Wang; Na Kang; et al. (Journal of Environmental Sciences, 2026)

New perspectives on the role of oil-gas in mineralization of sandstone-hosted uranium deposits: Carbonate evidence from Yuejin Ⅱ, Qaidam Basin, China - Yi-Han Lin; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Jun-Ying Ding; Zhi-Lin Cheng; Zhao-Hui Li; Xue-Feng Gao; Ping Feng (Journal of Asian Earth Sciences, 2026)

Microneedle patches at the bio-agricultural Interface: Toward precision, resilience, and sustainability - Fangzheng Zhou; Xiaochen Huang; Yaqi Teng; Ping Yu; Boqiang Li; Haowen Sun; Yixin Gao; Ruikun He; Wei Sun; Bei Fan; Xiaoxue Jia; Long Li; et al. (Food Research International, 2026)

Multi-copy expression of classical swine fever virus E2 in a recombinant pseudorabies virus enhances immunogenicity and supports its potential as a PRV-CSFV bivalent vaccine candidate - Xianfei Shang; Hui Zhao; Yufeng He; Zhenxiang Rong; Xiquan Ke; Jinglei Gao; Ke Zhang; Jiyuan Luo; Min Zhang; Huanchun Chen; Xiangmin Li; Ping Qian (Veterinary Microbiology, 2026)

Analytical modeling for uplift resistance of subsea pipelines in loose sand: Local flow-around failure mechanism and smooth-pipe validation - Xiao-Mi Li; Yu-Min Shi; Ning Wang; Xiao-Bing Lu; Fu-Ping Gao (Ocean Engineering, 2026)

Boosting CO₂ sequestration and lipid production in microalgae via a dual-ligand MOF bio-hybrid strategy - Longfei Yuan; Mengwei Li; Xinqing Gao; Manrong Wu; Yitong Wu; Yiming Li; Jianjun Liao; Ping Zhang; Linlin Zhang (Journal of Environmental Chemical Engineering, 2026)

Avermectin induces developmental toxicity and immunotoxicity in zebrafish larvae - Wei-Guo Wang; Shou-Lin Li; Da-Wei Yan; Yun-Fei Sha; Wen-Ping Xu; Jia-Gao Cheng; Zhong Li; Li-Ming Tao; Yang Zhang (Journal of Environmental Sciences, 2026)

Synthesis and valorization of corn silk-derived carbon dots for antimicrobial fruit preservation - Yong-Ping Wen; Meng-Ting Wu; Kwang-Pyo Kim; Meng-Yi Chen; Jia-Hui Liu; Ya-Ping Li; An-Guo Wu; Xiang Li; Song-Zhi Xie; Die Gao; Jian-Ming Wu; Xiao-Gang Zhou (International Journal of Food Microbiology, 2026)

Boosting lattice oxygen activation and active sites generation via an Mn-O electron bridge for efficient simultaneous oxidation of toluene and NO over Mn5Co4Ce3Ox catalyst - Lei Gao; Yukai Quan; Ping Fang; Dong Xie; Caiting Li; Cheng Sun; Jiahao Zhang; Ruotao Bai; Jingshuo Zhang (Fuel, 2026)

GABA-enriched Lactobacillus buchneri XBMU-C1 fermentation broth lowers blood pressure in L-NAME-induced hypertensive rats via RAAS suppression and PI3K/Akt/eNOS activation - Dandan Gao; Chenchen Wang; Ying Chen; Jiwen Wang; Junyao Mei; Yujie Cao; Xuankang Yang; Shangyun Kang; Jinyong Ma; Ping Li (Food Research International, 2026)

A non-complex-algorithmic and manually calculable fragment-resolved isotope framework ratios for geographic authentication of refined sugar - ShuoCong Li; ZhenPeng Zhen; XiaoFeng Xie; RongWei Fu; DeJin Kong; Zhu Lin; ZhaoHua Ping; GuiHua Wang; YuFeng Gao (Food Chemistry, 2026)

Regulatory mechanisms of N2O emissions from latosolic red soil by different ecotypes of earthworms: Insights from microbial diversity and metagenomic analysis - Chang Wei; Chang-Wen Yun; Xiao-Qing Li; Lang-Hao Lai; Jian-Peng Gao; Meng-Ping Tang; Chun-Na Zhou; Yu-Long Zhang; Hui-Juan Xu (Environmental Pollution, 2026)

Erosion and entrainment in dry granular flows: Insights from large-scale experiments - Shi-lin Zhang; Yang Gao; Yue-ping Yin; Lonneke Roelofs; Wen-pei Wang; Xie-wen Hu; Bin Li (Engineering Geology, 2026)

Hydrometeorological thresholds controlling soil carbon, nitrogen, and vegetation productivity dynamics in an Inner Mongolian grassland watershed (1981–2019) - Ge Gao; Jia Liu; Limin Duan; Yixuan Wang; Yicheng Wang; Jianzhu Li; Ping Feng; Josep Peñuelas (CATENA, 2026)

Straw mulching mitigates warming-induced yield loss and leverages elevated CO2 to improve winter wheat productivity under projected climate scenarios - Qi Yang; Xiaoran Chen; Zixuan Wang; Yuzheng Zong; Dongsheng Zhang; Xinrui Shi; Zhiqiang Gao; Ping Li; Xingyu Hao (Agricultural and Forest Meteorology, 2026)

A robot herding strategy combining CMFF and MPC for shepherding - Hongbo Liu; Ping Song; Gang Liu; Xiaoping Xin; Yuping Rong; Luyu Ding; Junyao Gao; Zhuoming Wang; Yinglong Zhang; Pengzhen Li (Computers and Electronics in Agriculture, 2026)

Landscaping neurodevelopment of attention-deficit hyperactivity disorder - Ningning Liu; Yin-Shan Wang; Zi-Xuan Zhou; Peng Gao; Chongjing Luo; Xinyi Zhang; Ziqing Zhu; Yuan Gao; Fei Ren; Yan Zhu; Li-Zhen Chen; Haimei Li; et al. (Science Bulletin, 2026)

Isoprenylated phenolic derivatives from Corethrodendron scoparium and their anti-triple negative breast cancer activity - Yuan Gao; Ping Hai; Hai-Yan Jia; Mei-Ling Yang; Hui-Xia Fan; Jin Yang; Xian-Yan Li; Lian Yang; Zhi-Qiang Luo; Jian Yang (Phytochemistry, 2026)

Orbitally driven ammonium upwelling fueled primary productivity during the peak Cambrian Explosion - Guangming Meng; Haifeng Gai; Chengang Lu; Yanming Zhao; Yineng Tan; Yang Liu; Yue Feng; Gang Li; Xing Wang; Wei Liu; Yijie Xing; Ping Gao; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Toward understanding tidal flat regime shifts: Contrasting hydro-sediment dynamics revealed by paired observations of two tidal flats - Shibing Zhu; Ya Ping Wang; Yuan Li; Qingguang Zhu; Fei Xing; Mingliang Li; Chao Gao; Shucun Sun (Journal of Hydrology, 2026)

Water vapor adsorption mechanisms of marine overmature kerogen during graphitization: Systematic analysis based on chemical structure, surface wettability and pore structure - Yijie Xing; Yihao Xing; Guangming Meng; Ping Gao; Yanming Zhao; Wei Liu; Jinku Li; Xianming Xiao (International Journal of Coal Geology, 2026)

Surface coordination-induced heterogeneous nucleation of hierarchical coatings enabling pyrolysis vapor-mediated post mineralization for adaptive protection - Chengliang Zhou; Yanli Liao; Yanlei Gao; Xin He; Ping Jiang; Xia Zheng; Suwen Yang; Xingong Li (Chemical Engineering Journal, 2026)

Molybdenum-functionalized thiolated chitosan repurposes aqueous V(V) as an in situ PMS activator for simultaneous organic degradation and vanadium recovery - Yating Wu; Ting Xiang; Lei Zhang; Ping Gao; Lei Li; Chensi Shen; Fang Li; Juan Zhou (Chemical Engineering Journal, 2026)

Mechanistic insights into sucralose immunotoxicology: Dose-related modulation of the gut-immune axis in food allergy - Wenyan Li; Qiang Shi; Yifan Nie; Zhongliang Wang; Shuangyan Zheng; Ping Tong; Jinyan Gao; Yong Wu; Hongbing Chen (Chemico-Biological Interactions, 2026)

Two Contributions to the Hypogeous Boletales of China: A Novel Rhizopogon Species and a New National Record of Turmalinea persicina - Jia Li; Chang Xu; Tai‐Jie Yu; Wen‐Hao Zhang; Xiu‐Juan Li; Yu‐Xian Gao; Yuan‐Tian Lu; Li‐Ping Tang (New Zealand Journal of Botany, 2026)
Hypogeous Boletales are ectomycorrhizal fungi with sequestered hymenophores; some species are ecologically valuable as edible mushrooms. Despite their ecological and economical importance, the diversity of this group in China remains poorly understood. In this study, we performed phylogenetic analyses based on four loci (ITS, LSU, TEF1‐α , and RPB2 ) and detailed morphological examinations of specimens belonging to Rhizopogon (Rhizopogonaceae) and Turmalinea (Boletaceae). We describe and illustrate R. sinoevadens , a new species from China, and report the first Chinese record of T. persicina , a species originally described from Japan. These discoveries underscore the previously underestimated diversity of hypogeous Boletales in China and provide a foundation for future taxonomic and ecological studies.

Drivers of greenhouse gas emissions from global coastal blue carbon ecosystems: a synthesis of methane and carbon dioxide fluxes - Fei Wang; Xiaoyong Duan; Gang Tong; Xue Li; Ke Cao; Xingliang He; Bin Chen; Fei Gao; Ping Yin; Xianguo Li; Dahai Zhang (Acta Oceanologica Sinica, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Comprehensive life-cycle assessment of a hybrid renewable energy system–powered decentralized sewage treatment system in cold and rural Inner Mongolia - Shangbin Ma; Ping Miao; Shugang Guo; Yaoting Hu; Hongli Ma; Pengyu Li; Pengfei Cao; Dawen Gao; Jing Luo; Jianguo Liu; Tianlong Zheng (Journal of Water Process Engineering, 2026)

The impact of atmospheric aging processes on the ice nucleation activity of Asian dust: A perspective from online continuous flow diffusion chamber observations - Jiayun Li; Xinyuan Chang; Dantong Chen; Kai Bi; Yunbo Chen; Xincheng Ma; Ruijie Li; Ping Tian; Mengyu Huang; Xiaoyu Ren; Shuai Wang; Zhaoze Deng; et al. (Atmospheric Pollution Research, 2026)

Calculation of hydrogeological parameters based on a high-flow long-duration water release test of multiple deep boreholes, Xiadian coalfield, North China - Fang Li; Rui Luo; Zhijia Yu; Wubin Gao; Jianggen He; Yu Ping; Shiyuan Tian; Zihan Wang; Tao Cheng; Colin G. Farquharson; Xinyi Wang (Hydrogeology Journal, 2026)

Integrating slush samples and eDNA metabarcoding to enhance marine fish biodiversity monitoring - Qilin Gutang; Hancheng Zhao; Xiaoxuan Yu; Yan Gao; Kunhuan Li; Jianghua Yang; Xiaowei Zhang; Ping Li; Edmond Sanganyado; Zonghang Zhang; Jianqing Lin; Wenhua Liu (Fisheries Research, 2026)

Taxonomy of Neostagonosporella on Chimonobambusa with descriptions of two new taxa - Xiu-Lan Xu; Yu Deng; Li-Ping Gao; Qian-Ying Huang; Wei Liu; Li Zhuang; Fei Chen; Qian-Gang Xiao; Zhen Zeng; Feng Liu; Qi-Rong Sun; Ying-Gao Liu; et al. (Mycological Progress, 2026)

Differential effects of a novel mesoionic insecticide, triflumezopyrim, on Apis mellifera and Apis cerana - Mei-Ling Zhang; Shu-Wei Wang; Wen-Min Li; Sasiprapa Krongdang; Yan-Yan Wu; Ping-Li Dai; Shan-Shan Li; Jing Gao (Journal of Hazardous Materials, 2026)

Corrigendum to Avermectin induces developmental toxicity and immunotoxicity in zebrafish larvae. Journal of Environmental Sciences (2026), doi: https://doi.org/10.1016/j.jes.2026.03.02 - Wei-Guo Wang; Shou-Lin Li; Da-Wei Yan; Yun-Fei Sha; Wen-Ping Xu; Jia-Gao Cheng; Zhong Li; Li-Ming Tao; Yang Zhang (Journal of Environmental Sciences, 2026)

Spatiotemporal variability, driving factors, and potential human health risks of fluoride and nitrate in surface water and groundwater of a sandy desert lake basin, Northwest China - Xiangwei Li; Muhan Li; Shen Qu; Keyi Zhang; Yuanzhen Zhao; Ao Gao; Renpu Wang; Dongchao Huo; Zongbao Yue; Bowen Ye; Hongli Ma; Ping Miao; et al. (Journal of Environmental Sciences, 2026)

Unravelling flavor formation in Chinese steamed bread made with fermented glutinous rice wine dough: insights from microbial succession, metabolomics, and volatile profiling - Jia-Xuan Li; Feng-Ping Qin; Meng-Ting Chen; Yu-Yu Liu; Xiao-Na Guo; Ke-Xue Zhu; Fei Gao; Jun-Jie Xing (Food Research International, 2026)

Groundwater-surface water interactions and material fluxes in a typical watershed, Ordos Plateau, NW China: insight from hydrochemistry, stable isotopes and 222Rn mass balance model - Wei Bao; Yixuan Wang; Ao Gao; Jiping Yao; Shen Qu; Jiajun Li; Dong Qian; Le Qiao; Lijuan Hu; Hongli Ma; Ping Miao; Haixia Wu; et al. (Environmental Geochemistry and Health, 2026)

Cerebellar Contributions to Cognitive Affective Function and Postural Tremor in Neurological Wilson’s Disease - Ping Jin; Dong-xu Yin; Yu-xie Huang; Zi-wen Li; Xin-feng Ma; Kang Lin; Ya-yun Xu; Wei-ming Gao; Qun-rong Ye; Yong-zhu Han; Gong-qiang Wang (The Cerebellum, 2026)

Oral co-exposure to Clostridioides difficile toxin A and ovalbumin disrupts intestinal homeostasis and predisposes to food allergy in mice - Xiaoqian Xu; Xiang Zeng; Youdou Cheng; Ping Yang; Jinyan Gao; Xuanyi Meng; Yong Wu; Xin Li; Ping Tong; Hongbing Chen (Toxicon, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Avermectin disrupts blood-brain barrier integrity in zebrafish larvae via the Wnt/β-catenin signaling pathway - Wei-Guo Wang; Lin-Jing Du; Huan-Ou Ma; Wen-Ping Xu; Li-Ming Tao; Zhong Li; Jia-Gao Cheng; Li Zhao; Yang Zhang (Pesticide Biochemistry and Physiology, 2026)

Stomatal width and vascular bundle anatomy govern foliar uptake and phloem transport of atmospheric Pb in wheat - Liu-Xu Feng; Xiang-Yu Li; Pei-Pei Gao; Yan Li; Gui-Li Hua; Ding-Hao Li; Li-Ping Geng; Xiao-Min Wang; Hong-J. Di; Wen-Ju Liu; Pei-Ying Xue (Journal of Hazardous Materials, 2026)

Climate-smart straw return amplifies CO2 fertilization effects while decoupling N2O emissions: Evidence from soil metagenomics and metabolomics - Ruonan Duan; Wei Gao; Qiqi He; Zhichao Zhai; Yuzheng Zong; Dongsheng Zhang; Xinrui Shi; Xingyu Hao; Ping Li (Journal of Cleaner Production, 2026)

Establishment of a screening method for potential allergens and assessment of the allergenicity of Chlorella variabilis - Shanshan Zhang; Mengting Zhu; Xiaoqian Xu; Li Guo; Hao Wang; Ping Tong; Hongbing Chen; Jinyan Gao (Food Chemistry, 2026)

Geomorphological controls on elevational differentiation of sediment 210Pbₑₓ and 137Cs activities in a water-level fluctuation zone - Jinlin Li; Xiubin He; Jie Wei; Qiang Tang; Yuhai Bao; Ping Huang; Shengjun Wu; Xin Gao; Ziqiang Mao (CATENA, 2026)

Quantifying scale effects in pile scour depth prediction for field applications via interpretable machine learning - Yang-Xin Zhou; Qing-Kai Song; Wen-Gang Qi; Li-Jing Yang; Xiao-Bing Lu; Fu-Ping Gao (Coastal Engineering, 2026)

Graphitization of marine kerogen and its effects on nanopores and adsorption performance - Guangming Meng; Xianming Xiao; Haifeng Gai; Yanming Zhao; Yijie Xing; Kun Zhang; Yu Liu; Qin Zhou; Tengfei Li; Wei Liu; Peng Cheng; Ping Gao (Science China Earth Sciences, 2026)

Does a positive culture correlate with the volume of synovial fluid inoculated into blood culture bottles for the diagnosis of periprosthetic joint infection? - Jia-Zheng Xu; Zhi-Sen Gao; Zhen Zhang; Ping Song; Wei Chai; Rui Li (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Competition partially decouples the climate-growth relationship in plantations and reduces their drought resilience - Chongfan Guan; Jinsong Zhang; Shoujia Sun; Wanting Gao; Zijing Li; Jinfeng Cai; Ping Meng (Agricultural and Forest Meteorology, 2026)

Robust Noise Identification and Data Reconstruction for Marine Magnetotelluric Time-Domain Data using STA/LTA and Compressive Sensing with Orthogonal Matching Pursuit - Yun-sheng Zhao; Ming-zhen Zhang; Min-gui Cai; Yan Gao; Zhan-xiang He; Jian-ping Li (Applied Geophysics, 2026)

Osteopontin-driven TGF-β1 signaling via integrin αvβ3-NF-κB axis impairs NK cell function in head and neck squamous cell carcinoma - Zhe Shen; Xin Li; Shi Luo; Yuzhang Gao; Imadoudini Hassimi Safia; Jie Jiang; Xin Qi; Wei Huang; Yalan Liu; Xing Fang; Yaoyun Tang; Ping Wu (Apoptosis, 2026)

The “Last-mile Efforts” of Subseasonal Prediction and Services for Climate Resilience and Sustainability: Review and Outlook - Jing Yang; Mengqian Lu; Anling Liu; Tat Fan Cheng; Yuxian Pan; Miaoni Gao; Lun Dai; Shentong Li; Wen Deng; Xinyao Feng; Shiyu Zhang; Lu Tang; et al. (Advances in Atmospheric Sciences, 2026)
Subseasonal predictions from 2 weeks to 2 months have made significant advancements over the past decade, driven by progress in physical understanding, climate modeling, computational capabilities, and artificial intelligence (AI). These predictions are increasingly in demand due to their potential to provide stakeholders with adequate lead time for effective disaster adaptation, mitigation, and resource management. However, there remain critical gaps in the engagement between prediction providers and service users. Providers often lack insight into the specific needs of users and do not have transferrable strategies to build trust through tailored evaluations and clear confidence levels, which often results in repeatedly devising approaches for each provider–user interaction. Further, users frequently struggle to interpret predictions and are hesitant to make decisions based on these uncertain outcomes. This paper attempts to make “last-mile efforts” by reviewing relevant literature, operational systems, and the most informative communications and engagement strategies with key sectors. It proposes a preliminary framework to standardize the approach for provider–user interaction in the context of subseasonal prediction and services, with potential applicability and extension to seamless prediction systems in the future. Lastly, we underscore future directions for subseasonal predictions, emphasizing the integration of dynamic climate modeling and AI-driven enhancements with large ensemble techniques to improve both reliability and confidence. This review is part of the United Nations Educational Scientific and Cultural Organization (UNESCO) International Decade of Sciences for Sustainable Development (2024–33) and contributes to the Seamless Prediction and Services for Sustainable Natural and Built Environment (SEPRESS) Program (2025–32), an initiative endorsed under this global framework.

PFOS promotes Alzheimer’s disease through aggravating the cell apoptosis and AKT/GSK3β/NF-κB/NLRP3 pathway mediated inflammation - Ming Li; Xianhao Ping; Huixin Song; Jin Sun; Qian Yang; Li-Na Gao (Toxicology, 2026)

Cuticular evidence and taxonomic reassessment of Miocene Albizia fossils in southwest China: Implications for the biogeography of A. julibrissin - Ping Lu; Jin-Bo Gao; De-Liang Li; Xiao-Qing Liang (Review of Palaeobotany and Palynology, 2026)

Digital disaster prevention for ocean engineering: Current progress and future directions - Zhen-Zhong Hu; Yilin Li; Fu-Ping Gao; Jian-Min Zhang (Ocean Engineering, 2026)

Characteristics of structural superimposed halo at the Jiawula Ag-Pb-Zn deposit, Inner Mongolia, China and its significance for exploration - Xin-yu Gao; Gui-yuan Sun; Kang Wang; Wei Zhang; Zhi-ping Li; Wen-ju Li; Jiang Wei; Lin Yang; Hong-zhe Xie; Zi-wen Yang; Chao Ma (Journal of Geochemical Exploration, 2026)

Possible inter-room aerosol-mediated COVID-19 transmission in a quarantine hotel: A case study - Merrill LIM; Junjing YANG; Sze Tat TAN; Man XIAO; Chun Ping GAO; Vernon LEE; Yee Leong TEOH; James CHAN; Lin CUI; Yichen DING; Joanna SHEN; Ruixin LI; et al. (Building and Environment, 2026)

Impacts of diverse urbanization scenarios on typhoon precipitation patterns in the Pearl River Delta: A case study of Typhoon Mangkhut - Yongwei He; Zhongming Gao; Yulong Ma; Ping Zhou; Jingyu Yao; Xixi Yang; Lei Li (Atmospheric Research, 2026)

Impacts of Distinct Synoptic Patterns on Fine‐Scale Precipitation Characteristics in Complex Terrain of S outhwestern C hina - Zhibo Gao; Lun Li; Chuanfeng Zhao; Guolu Gao; Rouyi Jiang; Hongqing Yang; Sichang Liu; Ping Lu (International Journal of Climatology, 2026)
Due to the effects of large‐scale topography of the Tibetan Plateau (TP), Yunnan‐Guizhou Plateau and Sichuan Basin (SCB), Southwest China (SWC) is characterised by complex synoptic patterns and variable precipitation features. However, the impacts of different synoptic patterns on fine‐scale daily and sub‐daily precipitation in SWC remain poorly understood. To address this issue, this study employs the Self‐Organising Map method to classify summertime synoptic patterns based on rainy‐day circulation fields over SWC into three distinct types. These types are primarily distinguished by the position of the western Pacific subtropical high (WPSH). In the northward‐shifted and inland‐extended pattern (Type 2, 31%), strong afternoon radiative forcing over SWC enhances nocturnal southerly advection, which transports moisture from the South China Sea northward into the SCB, enhancing CAPE and facilitating rapid convective development along the eastern slope of the TP. Under the eastward‐displaced pattern (Type 3, 30%), both radiative forcing and southerly advection weaken. South‐westerly moisture transport from the Bay of Bengal converges with cold air over southern Guizhou (GZ) and South China, creating a high‐CAPE zone conducive to precipitation initiation and subsequent eastward propagation. When the WPSH is located near its climatological position (Type 1, 39%), the lower troposphere over SWC is simultaneously influenced by warm‐moist flows from both the Bay of Bengal and the South China Sea. This configuration leads to pronounced and long‐lasting nocturnal precipitation peaks in both the SCB and GZ, with SCB precipitation primarily associated with a low‐level vortex. The findings of this study provide a new perspective for understanding fine‐scale precipitation characteristics over SWC.

Persistent site-scale warming associated with solar photovoltaic installations - Chao Zhang; Wanjiao Li; Junjie Tang; Zhe Shi; Fanyu Suo; Shujie Zhang; Yulu Ke; Hongxing Hu; Ning Ai; Yong Gao; Ping Gong; Guo Yu Qiu (Journal of Environmental Management, 2026)

Upgrading oxygen vacancy and reducibility for enhancing synchronous abatement of Hg0 and toluene over Co-Mn-Ce trimetallic oxides fortified biochar catalysts - Jiaqing Li; Yanyan Feng; Lei Gao; Ping Fang; Yunqing Wang; Caiting Li; Jinke Xie; Yukai Quan; Siyou Li (Journal of Environmental Chemical Engineering, 2026)

The transepithelial transport and membrane diffusion pathways of the walnut meal-derived antioxidant peptide YR-10 were investigated using Caco-2 monolayer cells and DPPC liposome models - Hui Ouyang; Jiaying Huo; Xiaojuan Xin; Ying Gao; Ping Wang; Xiongwei Yu; Shugang Li (Food Bioscience, 2026)

Cyflumetofen induces hepatic steatosis and disrupts lipid metabolism in zebrafish larvae - Wei-Guo Wang; Yi-Min Duan; Da-Wei Yan; Lan Xu; Wen-Ping Xu; Li-Ming Tao; Yang Zhang; Jia-Gao Cheng (Chemico-Biological Interactions, 2026)

Soil aggregate-mediated dynamics of microbial necromass under contrasting cropland management practices - Wen-Jun He; Jie-Yu Gao; Xin-Xin Jing; Peng Chen; Lu-Ping Ye; Zhi-Guo Li; Yi Liu; Chen-Hao Lyu (Plant and Soil, 2026)

Rapid selection of early-maturing and low-ear position maize hybrids suitable for China using genomic prediction - Ping Luo; Wenzhe Li; Lin Zhang; Jie Yang; Houwen Wang; Fei Wang; Ruisi Yang; Xinlong Xu; Ke Yang; Hongjun Yong; Mingshun Li; Jianfeng Weng; et al. (Plant Molecular Biology, 2026)

Surveillance reveals a prevalent pediatric A(H1N1)pdm09 virus with hemagglutinin substitutions S137P-R142K-V152I that diminish vaccine efficacy - Lifeng Zhao; Jing Wang; Jihong Xu; Jiane Guo; Ping Zhang; Xiaofang Guo; Zhihong Zuo; Ruihong Gao; Li Gao; Jitao Wang (Virus Genes, 2026)

DrPISA: Deep eutectic solvent-assisted reverse proteome-integrated solubility alteration for high-sensitivity drug target identification - Liu Yang; Tian-Bo Ma; Chen-Wan Guo; Run-Bo Yu; Ping Li; Hua Yang; Wen Gao (Analytica Chimica Acta, 2026)

New α-pyranone derivatives from Diaporthe sp. WLM-Y1 - Xiang Li; Xue-Kai Zhao; Xu-Ping Zhang; Wei-Guang Wang; Qian-Qian Yin; Lu Gao (Natural Product Research, 2026)

Who is the best allogeneic hematopoietic stem cell transplant donor for severe aplastic anemia? Data from the Chinese Bone Marrow Transplantation Registry Group (CBMTRG) - Zheng-Li Xu; Lan-Ping Xu; Shun-Qing Wang; De-Pei Wu; Xi Zhang; Su-Jun Gao; Ling-Hui Xia; Rui Xi; Jian-Min Yang; Qi-Fa Liu; Ming Jiang; Xiao-Sheng Fang; et al. (Science Bulletin, 2026)

Corrigendum to “Sources of organic carbon and environmental response characteristics in the mangrove region of Trat Province, Thailand, over the past 1,019 years” [Mar. Environ. Res. 213 (2026) 107628] - Yuanqin Xu; Ping Li; Jie Liu; Wei Gao; Wenjie Yu; Yao Zhang; Somkiat Khokiattiwong; Narumol Kornkanitnan (Marine Environmental Research, 2026)

Cyflumetofen disrupts the blood-brain barrier and induces neurotoxicity in zebrafish larvae - Wei-Guo Wang; Yi-Min Duan; Wen-Ping Xu; Li-Ming Tao; Yang Zhang; Jia-Gao Cheng (Chemico-Biological Interactions, 2026)

Coupled effects of straw return practices on soil microbial functional potential and agricultural productivity in Semi-Arid Region - Rui-Zhi Liu; Xiao-Ya Zhao; Li-Jie Wang; Xing Zhang; Shu‑Ping Hu; Ju‑Lin Gao; Xiao‑Fang Yu; Qinggeer Borjigin (Plant and Soil, 2026)

UAV-SfM coupled PBD simulation of graded rockfall fragmentation and air resistance: validation at Bijiashan, Chongqing - Jian Ping Pan; Lu Li; Wei Gao; Dan Huang; Jia Shu Liao (Bulletin of Engineering Geology and the Environment, 2026)

Drag reduction and shear stress saturation caused by tide-induced high suspended sediment concentration in the bottom boundary layer - Ya Ping Wang; Jin Li; Renzhi Li; Jingdong Chen; Yan Li; Yining Chen; Shu Gao; Aijun Wang; Benwei Shi; Jianhua Gao; Yang Yang (Geo-Marine Letters, 2026)

Transgenerational Effects of Elevated Temperature on Life History and Lambda-Cyhalothrin Sensitivity in Cydia Pomonella - Kang-Wu Zheng; Zi-Han Wei; Zi-Nan Xia; Bo-Kun Wang; Ping Gao; Yu-Ting Li; Xue-Qing Yang (Neotropical Entomology, 2026)

Breaking the antimicrobial resistance dilemma: marine natural products, a treasure trove for the development of new anti-Staphylococcus aureus drugs - Peng-Jie Li; Liu-Xia Lv; Xi-Zhen Cao; Jian-Yu Liu; Ji-Xiu Gao; Hao-Ran Li; Gulab Said; Dan Chen; Bo Yao; Xin Liu; Mei-Yan Wei; Xiao-Ping Yang; et al. (Marine Life Science & Technology, 2026)
Antimicrobial resistance (AMR) affects multiple fields, including medicine, pharmacy, food safety, and animal husbandry, and poses a major threat to public health and economic development. Staphylococcus aureus has emerged as one of the most critical bacterial pathogens due to its widespread prevalence and significant genetic plasticity. This review outlines currently approved small-molecule drugs for clinical use and their mechanisms in controlling bacterial infections and antimicrobial resistance, highlighting the development of novel agents as an effective strategy to combat AMR. Special emphasis is placed on the antibacterial activity of marine-derived natural products (MNPs) against S. aureus , and a systematic analysis is presented for the first time on the structures, origins, activities, and structure–activity relationships of 1,192 compounds reported in 468 publications from 1977 to 2025. Among these, 36 MNPs exhibited significant activity against both methicillin-sensitive S. aureus and methicillin-resistant S. aureus (MIC ≤ 1 µg/mL). Macrolides and peptides represented the most prevalent structural classes, with compounds displaying potent activity accounting for 24% and 27% of the total active compounds, respectively. Further drug-likeness analysis shows that MNPs have promising therapeutic potential. Among the 160 highly active MNPs, over 80% have suitable lipid-water partition coefficients, and 41% fully meet Lipinski's Rule of Five. Structural analysis reveals tetrahydrofuran, tetrahydropyran, and sugar units as the most common motifs, present in 20, 16, and 14 compounds, respectively. Technologies and strategies to accelerate the development of marine-derived antibacterial drugs are also proposed. This will serve stakeholders across diverse sectors by supporting cross-sectoral coordination to address AMR.

Correction: The spatiotemporal changes and influencing mechanisms of the coastline in the Yellow River Delta, China - Zhuo Yang; Wei Gao; Wenjie Yu; Jie Liu; Jun Du; Ping Li; Yuanqin Xu; Ping Li (Frontiers in Marine Science, 2026)

A mixed mushroom poisoning in humans associated with the ingestion of Collybiopsis orientisubnuda - Xiu-Juan Li; Chang Xu; Wen-Hao Zhang; Jing Ma; Han-Chi Lei; Jia Li; Yu-Xian Gao; Xing Xia; Ping Wei; Yi Liu; Li-Ping Tang (Toxicon, 2026)

Tumor microenvironment-driven ST6Gal-Ⅰ activation promotes aggressiveness in gastric signet-ring cell carcinoma via ITGβ1/FAK/Paxillin signaling - Shuhong Zeng; Lihuiping Tao; Yingjie Gao; Xueying Yang; Zhiyu Li; Ziwen Li; Luhua Wu; Zhengchen Ping; Qian Zhao; Jiayi Gu; Liu Li; Dongdong Sun; et al. (Tissue and Cell, 2026)

New Pachyportax fossils from the Late Miocene Shuitangba locality, Yunnan, revealing the early Bovini evolution and radiation - Ding-Ge Guo; Sayyed Ghyour Abbas; Qi-Gao Jiangzuo; Chun-Xiao Li; Yan-Wu Yang; Jia-Yong Cao; Bin Zou; Shi-Qi Wang; Xue-Ping Ji (Palaeoworld, 2026)

MsTIFY10a gene from alfalfa negatively regulates drought and salt tolerance in transgenic tobacco - Qi Chen; Yan Zhang; Ying Tian; Jing Xu; Qing-Wen Fu; Zhen-Yi Li; Feng-Ling Shi; Cui-Ping Gao; Zhi-Qiang Zhang (Journal of Plant Physiology, 2026)

Nanopore characteristics of lower Cambrian shale based on gas adsorption and multifractal analysis: Implications for gas development and CO2 storage - Wei Liu; Xianming Xiao; Ping Gao; Yanming Zhao; Yijie Xing; Qizhang Fan; Guangming Meng; Jinku Li; Qin Zhou; Tengfei Li; Siyi Liu (Fuel, 2026)

Origin and forming mechanism of coking substance in ester aviation lubricating oil - Teng Chen; Huashuai Gao; Ping Qi; Shizhao Yang; Xin Xu; Jun Ma; Li Guo; Jingpei Cao; Jianqiang Hu (Fuel, 2026)

Prenatal organophosphate esters exposure impacts placental structure and inflammatory markers in a trimester-specific manner - Yuan Liu; Ping Lv; Xing Wang; Mengqian Zhang; Yifan Wang; Sheng Wang; Mengjuan Lu; Han Li; Hong Gan; Juan Tong; Hui Gao; Fangbiao Tao (Environmental Research, 2026)

PbrRALF5/10 prevents incompatible pollen tube death by reconstructing the methyl-esterified pectin and reactive oxygen species metabolism of pear in vitro - Xiao-Xiong Kong; Tao Chen; Li-Yu Gao; Xu Huang; Xiao Liu; Jing Zhang; Zhi-Ping Zhang; Chun-Lei Wang (Plant Molecular Biology, 2026)

Whole-body RNA Sequencing Analysis of the Post-larval Reveals the Sex-biased Gene and MiRNA in the Prawn Macrobrachium rosenbergii - Kun Xie; Yu-Meng Shi; Jin-Xia Yang; Jia-Yan Chen; Xu Huang; Xin-Yu Liu; Li-Ping Chen; Jie Chen; Chao-Ping Lu; Gao-Feng Qiu (Marine Biotechnology, 2026)

Performance, metabolism, and resistance of an SMX-stressed continuous-flow AGS-MBR system: Microscopic mechanism of macroscopic instability phenomena - Yu Zeng; Haowei Gao; Huiya Huang; Wenqiang Xiong; Liying Bin; Bingda Liao; Weirui Chen; Xinyi Chen; Shanglong Wen; Ping Li; Shaosong Huang; Bing Tang (Water Research, 2026)

An interpretable machine learning model for predicting p-y curves of monopiles in clay - Biao Li; Wen-Gang Qi; Yi-Fa Wang; Fu-Ping Gao; Lu Jing; Shun-Yi Wang; Ben He (Ocean Engineering, 2026)

Sources of organic carbon and environmental response characteristics in the mangrove region of Trat Province, Thailand, over the past 1,019 years - Yuanqin Xu; Ping Li; Jie Liu; Wei Gao; Wenjie Yu; Yao Zhang; Somkiat Khokiattiwong; Narumol Kornkanitnan (Marine Environmental Research, 2026)

Pinoresinol diglucoside alleviates hindlimb unloading-induced bone loss in mice - Ying-Ying Xuan; Liang Li; Yi Wu; Zhen-Long Wei; Mei Zhang; Min-Na Liu; Dong-Shuai Shen; Yu-Hai Gao; Cory J Xian; Hui-Ping Ma; Ke-Ming Chen (Life Sciences in Space Research, 2026)

Water flooding patterns combined with fissure conductivity transition in sandy soil: insights from physical model tests - Hui Dong; Xiuzi Jiang; Hui Li; Qianfeng Gao; Ping Xu; Song Ouyang (Journal of Hydrology, 2026)

Iron-driven synergism among microbial functional taxa facilitates recovery from denitrification toxicity - Yongzhi Zhang; Xiaoxiao Li; Linjun Gao; Ping Ye; Rui Wang; En Zhou; Tian Sun; Miaoqing Xu; Rui Wan; Xiang Li (Journal of Environmental Management, 2026)

Nitrate reduction of dissolved organic carbon exported by episodic upwelling: A novel explanation for negative carbon isotope excursions during the Ediacaran–Cambrian transition - Guangming Meng; Haifeng Gai; Yaowen Wu; Ping Gao; Chengang Lu; Qin Zhou; Tengfei Li; Qizhang Fan; Wei Liu; Yanming Zhao; Yijie Xing; Jinku Li; et al. (Global and Planetary Change, 2026)

High-resolution mapping decouples hydrodynamic sorting and sediment transport as primary drivers of PAH distribution in the East China Sea inner shelf - Xiaoyong Duan; Ping Yin; Ke Cao; Fei Gao; Bin Chen; Meina Li; Shenghua Lv; Xiaoying Chen (Environmental Pollution, 2026)

Ti3C2-Cl-Bi12O17Cl2/Bi12O17Cl2 Mott-Schottky heterojunction with mixed noncovalent/covalent type to boost ultra-sensitive photoelectrochemical sensing of ciprofloxacin - Chu-Chu Hu; Qi-E Zhang; Shao-Peng Shi; Guo-Qing Zhao; Yan-Sha Gao; Ping Liu; Xun-Kuan Ye; Yan Pan; Hui-Qing Lv; Li-Min Lu (Chemical Engineering Journal, 2026)

Longitudinal decoupling between sedimentary phosphorus concentrations and sediment sorting in the Three Gorges Reservoir, China - Jinlin Li; Pingsheng He; Xiubin He; Jie Wei; Qiang Tang; Xiaoya Tang; Xin Gao; Ziqiang Mao; Ping Huang; Shengjun Wu (CATENA, 2026)

Physics-based unified formulation for predicting clear-water equilibrium scour depth and scour threshold velocity around piles - Wen-Gang Qi; Biao Li; Shun-Yi Wang; Yong Wan; Pei-Qing Zhao; Fu-Ping Gao (Coastal Engineering, 2026)

Deciphering mechanisms of stress-induced metabolic shifts in Corynebacterium glutamicum by transcriptomics and contextualised modelling - Xiaomeng Ni; Ning Gao; Wenjing Hu; Xuan Guo; Jiao Liu; Jiuzhou Chen; Ningyun Cai; Xiaojia Zhao; Jibin Sun; Yu Li; Yan Zhu; Ping Zheng (Bioresource Technology, 2026)

Core microbiomes of Cd-hyperaccumulators are shaped by host selection and compartment identity and drive plant performance - Jipeng Luo; Yuanfan Wang; Wenzhe Gao; Yongchao Liang; He-Ping Zhao; Shaohua Gu; Tingqiang Li (Plant and Soil, 2026)

Inhibition of the Microglial cGAS-STING Pathway Improves Neurological Deficits and Long-Term Hydrocephalus Symptoms in Mice with Intraventricular Hemorrhage - Hao-Xiang Wang; Hua-Jiang Deng; Kun-Hong Zhong; Zi-Ang Deng; Bao-Cheng Gao; Xin Tang; Yuan-You Li; Ke-Ru Huang; Ai-Ping Tong; Da-Xiong Feng; Liang-Xue Zhou (Molecular Neurobiology, 2026)

Oral Administrations of Short-Chain Fatty Acids or Probiotics Extend the Survival Times and Mitigate the Neuropathological Damages in the Scrapie-Infected Hamsters - Yuan Wang; Dong-Lin Liang; Run-Dong Cao; Ruhan A.; Jia-Feng Zeng; Bing Xu; Ju-Zheng Li; Wei-Wei Zhang; Li-Ping Gao; Kang Xiao; Xiao-Ping Dong; Qi Shi (Molecular Neurobiology, 2026)

Breaking the Alzheimer’s Treatment Stalemate: Synergistic Application Strategies of Nanomaterials and Pharmaceutical Agents - Han Gao; Fangyuan Cheng; Zihan Zhang; Bo Yan; Pan Liao; Shishuang Zhang; Dai Li; Fanglian Chen; Ping Lei (Molecular Neurobiology, 2026)

Sedimentary characteristics at the bottom of Qiongdongnan continental slope during the past 40 ka: comparison between hemipelagic and turbidite deposition - Jie Liu; Wei Gao; Yuanqin Xu; Ping Li (Acta Oceanologica Sinica, 2026)

Susceptibility of five thrips pests to spinetoram and the frequency of G275E target-site mutation in a major vegetable production region of China - Hong-Ping Tian; Hong-Xia Tian; Jin-Cui Chen; Fu-Jun Li; Jing-Jing Kang; Hui-Juan Li; Jin-Peng Gao; Guo-Cai Lu; Ya-Jun Gong; Shu-Jun Wei (Crop Protection, 2025)

Different detoxification strategies of fruit borers adaptation to quercetin - Bing Bai; Huan-Juan Zhao; Bo-Kun Wang; Yu-Ting Li; Ping Gao; Yun-Tong Lv; Xue-Qing Yang (Pesticide Biochemistry and Physiology, 2025)

Evaluation of carrying capacity of agricultural water and soil resources and targeted regional management in Northwest China - Yun Gao; Dawei Ding; Youming Zhang; Ping Li; Kaiyang Li; Tianhao Ruan; Yang Han; Chunya Ma (Journal of Environmental Management, 2025)

Evolution of water-soluble organic aerosol composition from clean days to haze episodes in rural area of North China Plain - Chun Chen; Long Jia; Zhiqiang Zhang; Jian Gao; Yanmei Qiu; Junling Li; Rui Gao; Ping Li; Qun Zhang; Zhijie Li; Jiaxing Sun; Nan Ma; et al. (Journal of Environmental Sciences, 2025)

Simultaneously regulating the content of pores and carbon microcrystallites in carbon blocks via coal tar pitch oxygen functionalization for improved mechanical and wear resisting performance - Yixing Chen; Sihan Gao; Pei Gong; Ping Liu; Jiao Tan; Xun He; Hong Luo; Run Li; Chuanjun Tu (Fuel, 2025)

Quercetin alleviates ethanol-induced hepatocyte senescence by interacting with glycinamide ribonucleotide transformylase - Chen Huimin; Peng Shufen; Cui Zhaoyu; Liu Jiaxin; Chen Li; Yin Xingzhu; Wu Bangfu; Zhao Ying; Wang Yu; Mo Li; Liang Chanhua; Li Dongyan; et al. (Food Research International, 2025)

A high safety composite separator for powerful battery with ultra-long lifespan over 14,000 cycles at 10C - Ke Fang; Yan-yan Chen; Jian-wei Ji; Tian-kun Gao; Mei-qi Hu; Lian-li Zou; Ying Liu; Li-ping Zhou; Ming-quan Liu; Mao-xiang Jing (Chemical Engineering Journal, 2025)

A new 2-arylbenzofuran derivative and other constituents from Smilax china L. and their chemotaxonomic significance - Li-Juan Hu; Xian-Sheng Ye; Kuan Lin; Jie Gao; De-Sen Yang; Guo-Ping Gan; Xi-Ji Shu; Wei Liu; You-Hua Yang (Biochemical Systematics and Ecology, 2025)

DPP4, a potential tumor biomarker, and tumor therapeutic target: review - Lu Sun; Yuhui Ma; Chenchen Geng; Xiaoqian Gao; Xinbing Li; Qi Ru; Shuzhen Zhu; Ping Zhang (Molecular Biology Reports, 2025)

Granulated Organic Amendment Enhances Soil Fertility, Alleviates Microbial Metabolic Limitation, and Increases Rice Yield in a Medium and Low-Yield Paddy Fields of Subtropical China - Yingnan Xian; Yan Li; Zhe Li; Mingxia Wang; Yuting Dai; Baozhen Li; Ping Zhou; Wei Gao; Xiaobin Guo; Jinshui Wu (Journal of Soil Science and Plant Nutrition, 2025)

Sex- and Age-Specific Inverted U-Shaped Links between Dietary Iron Intake and Serum α‑Klotho in Chinese Adults - Baodi Xing; Jie Yu; Yiwen Liu; Qi Gao; Xinyue Chen; Shuli He; Fan Ping; Lingling Xu; Wei Li; Huabing Zhang; Yuxiu Li (Biological Trace Element Research, 2025)

Identification and characterization of the first G8P[1] sheep rotavirus strain in China: Genetic similarity to human rotavirus and zoonotic potential - DengShuai Zhao; Ping Li; Junyan Fu; YuanHang Zhang; MiaoMiao Zhang; TianYu Wang; DiXi Yu; Han Gao; LiMei Qin; MengMeng Zhao; Feng Wen; ShengFeng Chen; et al. (Veterinary Microbiology, 2025)

The cotton gene family encoding translationally controlled tumor proteins and the role of GhTCTP5 in salt tolerance - Bo Pang; Jialin Chen; Ping Luo; Ru Zhang; Jing Li; Weiwei Liang; Wenwei Gao; Shengmei Li (Plant Science, 2025)

Overexpression of G protein-coupled receptors (GPCRs) contributing to lambda-cyhalothrin resistance in Cydia pomonella - Yu-Xi Liu; Chao Hu; Zi-Nan Xia; Yan Wang; Yu-Ting Li; Ping Gao; Yun-Tong Lv; Jia Li; Xue-Qing Yang (Pesticide Biochemistry and Physiology, 2025)

The pleiotropic odorant binding protein CaspOBP12 involved in perception of Ceutorhynchus asper for plant volatiles and pesticides - Xinghao Li; Fangjing Hu; Rufan Li; Danhao Peng; Ping Gao; Fuqiang Rao; Yonghong Li; Deguang Liu (Pesticide Biochemistry and Physiology, 2025)

Effect of apparent pore-fluid compressibility and degree of saturation with atmospheric pressure on wave-induced transient pore pressure response - Wen-Gang Qi; Pei-Qing Zhao; Li-Jing Yang; Mo-Zhen Zhou; Fu-Ping Gao; Dong-Sheng Jeng (Ocean Engineering, 2025)

High-throughput discrimination of chlorogenic acid isomers in Lonicerae Japonicae Flos by U-shaped mobility analyzer-mass spectrometer - Meng Ding; Luwei Zheng; Ao Zhou; Yuling Li; Yiming Wang; Xiaoqiang Zhang; Wenjian Sun; Wen Gao; Ping Li; Hua Yang (Food Chemistry, 2025)

Elucidating flavor compounds in Chinese steamed bread via glutinous rice wine-fermented dough technique: A triangulated analysis combining electronic tongue, SPME-GC-MS, and quantitative descriptive analysis - Jia-Xuan Li; Feng-Ping Qin; Meng-Ting Chen; Yu-Yu Liu; Xiao-Na Guo; Ke-Xue Zhu; Fei Gao; Jun-Jie Xing (Food Bioscience, 2025)

Novel umami peptides from Grass Carp marinated with Red Yeast Rice Flour and their taste presentation mechanisms characterized by in silico approach and sensory evaluation - Qiaohui Zeng; Miaoshan Zhou; Lifang Gao; Ping Qi; Shilin Cao; Jian Li; Xinan Zeng; Jingjing Wang (Food Bioscience, 2025)

Sedimentation substantially buries more carbon than nitrogen or phosphorus in the Three Gorges Reservoir, China - Jinlin Li; Xiubin He; Jie Wei; Qiang Tang; Yuhai Bao; Xin Gao; Ziqiang Mao; Xiaoya Tang; Ping Huang; Shengjun Wu (Environmental Research, 2025)

Chlorchinaldol: A promising antiviral agent against iridoviruses in fish - Jia-Cheng Qin; Xiao-Ping Tan; Ying-Jie Jin; Guang-Shuo Wang; Shen-Ye Qu; Peng-Fei Li; Gao-Xue Wang; Fei Ling (Aquaculture, 2025)

Rational design of CdS/Ce-UiO-66 heterostructure for high-efficiency photocatalytic oxidation of amines to imines - Huan Zhang; Cai-Yong Zhu; Wen-Qi Jin; Zi-Yu Li; Peng Li; Wei Gao; Ping Zhang; Xiu-Mei Zhang (Journal of Environmental Chemical Engineering, 2025)

Protein engineering and flow reactor design for anchored peptide-mediated continuous biocatalysis - Huan Li; Chun-Jiang Ma; Ya-Ting Gao; Qing-qing Zhou; Huan Chen; Feng Cheng; Ya-Ping Xue; Yu-Guo Zheng (Chemical Engineering Journal, 2025)

All-in-one wearable electronic based on bacterial cellulose composite: Integrating strain sensing and energy harvesting - Ping Sun; Zongxue Gu; Duo Xu; Bin Yu; Hui Sun; Juan Li; Nan Zhou; Jing Li; Keshuai Liu; Yingcun Liu; Chong Gao; Weilin Xu (Chemical Engineering Journal, 2025)

Surface chlorine doping activates highly stable Cu2O(111) facets for enhanced CO2 photoreduction - Ning Li; Ping Zhang; Reyila Tuerhong; Yongchong Yu; Yapeng Lan; Yu Zhang; Xiaoping Su; Lianbiao Zhao; Lijuan Han; Xiaotian Wang; Hengjiao Gao (Chemical Engineering Journal, 2025)

A multifunctional wearable patch based on hydrogel for strain sensing and epidermal sweat-analyzing - Shihao Wu; Jingwei Lu; Hongxiao Gao; Yuemeng Yang; Na He; Gan Miao; Li-Ping Xu (Chemical Engineering Journal, 2025)

Economical and efficient production of l-norvaline using whole cells of Escherichia coli with an enzymatic cascade - Zimai Li; Qiaoyue Yang; Mingyuan Liu; Hairong Yu; Qihang Du; Hongxu Zhang; Jinglong Deng; Xiaoxu Tan; Weikang Sun; Tianyi Jiang; Qianjin Kang; Wensi Meng; et al. (Bioresource Technology, 2025)

Unlocking the power of sesquiterpenoids: phytochemistry and bioactivities in Artemisia (2017–2023) - Li Ping Tang; Tao Liu; Xiao Yu Han; Bin Li; Hong Dong Liu; Xue Mei Gao (Phytochemistry Reviews, 2025)

Therapeutic effects of Scutellaria baicalensis total flavonoids on metabolic syndrome in rats via modulation of PPARα and PPARγ signaling - Yang Zhou; Zhi-Ping Li; Yu-Hang Lian; Xin Gao; Song-He Yin; Yu-Mei Zhao (Journal of Molecular Histology, 2025)

Rice-duck farming enhances phosphorus use and grain yield via altering soil phosphorus fractions in the Yangtze River Delta of eastern China - Hui Gao; Qingnan Chu; Xiangyu Liu; Liang Zheng; Shuhan Xu; Linkui Cao; Detian Li; Shuai Yin; Ping He; Chengrong Chen; Zhimin Sha (Agriculture, Ecosystems & Environment, 2025)

DEHP and its metabolite MEHP exposure impairs endometrial decidualization during early pregnancy via up-regulation of Mtmr6 - Li-Ping Tan; Liu Yuan; Yan Zhang; Jun-Lin He; Xin Yin; Yi-Dan Ma; Xue-Mei Chen; Wei-Ke Li; Fang-Fang Li; Ru-Fei Gao (Reproductive Toxicology, 2025)

The advantages in crop yields and carbon footprints of maize-soybean relay strip intercropping - Zhidan Fu; Ping Chen; Ping Lin; Yiling Li; Kai Luo; Chao Gao; Tian Pu; Yuze Li; Yushan Wu; Xiaochun Wang; Taiwen Yong; Wenyu Yang (Journal of Environmental Management, 2025)

A flexible and efficient UNITID-based access control (UBAC) model for environmental monitoring data - Jinku Huang; Changxiu Cheng; Bin Li; Yang Gao; Ping Li; Jiawei Wan; Jadunandan Dash (Environmental Modelling & Software, 2025)

Nanoparticles co-delivering double-stranded RNA and insecticide enhance control efficacy and overcome pest resistance - Chao Hu; Chang Yu; Jiaqing Li; Yuxi Liu; Qinghong Zeng; Hu Wan; Shun He; Yuting Li; Ping Gao; Yuntong Lv; Kunyan Zhu; Subba Reddy Palli; et al. (Chemical Engineering Journal, 2025)

Deciphering dissolved inorganic carbon dynamics in Xiangshan Bay: isotopic constraints on sources, hydrodynamic controls, and anthropogenic influences - Xue Li; Xiaoyong Duan; Gang Tong; Ping Yin; Fei Gao; Ke Cao; Bin Chen (Acta Oceanologica Sinica, 2025)

Mycorrhizal Network and Symbiotic N‐Fixer Jointly Enhance the Interplant Nitrogen Sharing - Yuxuan Gao; Yuntao Wu; Pengfei Chang; Ping Li; Shuijin Hu; Lingli Liu (Ecology Letters, 2025)
Symbioses with mycorrhizal fungi and nitrogen‐fixing bacteria (NFB) enhance nitrogen (N) acquisition in host plants and may promote N transfer to neighbouring plants through mycorrhizal networks (MN). Nevertheless, the extent and mechanisms of this transfer remain unclear. On the basis of a synthesis of 15 N labeling studies, we show that MN and NFB synergistically enhanced interplant N sharing. In the presence of MN, N transfer from N‐fixing donors to non‐N‐fixing receivers increased by an average of 9.7‐fold, accounting for 5.61% of the total N in receiver plants. Moreover, greater amounts of N were transferred from N‐fixing plants towards their phylogenetically distant plants. Source‐sink gradients driven by differences in N content between neighbouring plants further promoted N transfer. Together, our findings highlight the ecological significance of an expanded MN framework in explaining interplant N sharing and provide new insights into how symbiotic guild interactions promote species coexistence and biodiversity maintenance.

Gas Hydrate Exploration Using Deep-Towed Controlled-Source Electromagnetics in the Shenhu Area, South China Sea - Jianping Li; Zhongliang Wu; Xi Chen; Jian’en Jing; Ping Yu; Xianhu Luo; Mingming Wen; Pibo Su; Kai Chen; Meng Wang; Yan Gao; Yao Zhang (Journal of Marine Science and Engineering, 2025)
This study presents the first application of a deep-towed transmitter–receiver marine controlled-source electromagnetic (TTR-MCSEM) system for gas hydrate exploration in the Shenhu area of the South China Sea. High-resolution electromagnetic data were acquired along a 13 km transect using dynamic source–receiver offsets and a 500 A transmitter. The results reveal the following: (1) unprecedented near-seafloor resolution (20~100 m) for the precise delineation of hydrate-bearing caprock, surpassing conventional ocean-bottom electromagnetic systems; (2) laterally continuous high-resistivity anomalies (~10 Ω·m) extending from the base of the gas hydrate stability zone to the seafloor, which correlate with seismic bottom-simulating reflector (BSR) distributions and suggest heterogeneous hydrate saturation; and (3) fault-controlled fluid migration pathways that supply hydrate reservoirs and lead to seabed methane seepage at structural highs. Through 2D inversion, we show that the inverted resistivity values (~10 Ω·m) are slightly higher than those obtained from resistivity logs (~5 Ω·m). Saturation values derived from inverted resistivity exhibit remarkable consistency with well-log-based measurements. The high efficiency of the system confirms its potential for the transformative quantitative assessment of hydrate systems, seafloor massive sulfides, and marine geohazards.

The role of lactate metabolism in retinoblastoma tumorigenesis and ferroptosis resistance - Zhihui Zhang; Junjie Tang; Yaoming Liu; Yinghao Wang; Jinmiao Li; Yang Gao; Chao Cheng; Shicai Su; Shuxia Chen; Siming Ai; Ping Zhang; Rong Lu (Tissue and Cell, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Bioluminescent fungi-inspired room temperature phosphorescence mycelia - Xin Li; Jin-Xin Ma; Ping Wu; Qian Gao; Hao Wang; Lu-Xin Tang; Feng Peng; Bao-Zhong Lü; Jing Si; Bao-Kai Cui (Chemical Engineering Journal, 2025)

Complete genome analysis of a novel phenui-like virus in Morus alba - Hanze Zheng; Yangwei Gao; Xiaodi Hu; Zhongtian Xu; Jian-Ping Chen; Yiyuan Li (Archives of Virology, 2025)

Leaf and Root Traits Show Contrasting Resource Exploitation Strategies, but Converge Along Elevation in the Hengduan Mountain Forests - Jie Song; Sebastian Seibold; Liang‐Liang Ma; Jia‐Yun Zou; Jie Liu; Ming‐Shu Zhu; Wei Zheng; Zhi‐Qiong Mo; Sheng‐Ping Ming; Jin Li; Kun Xu; De‐Zhu Li; et al. (Journal of Biogeography, 2025)
Aim The variations of leaf and root traits in communities are associated with above‐ and below‐ground resource exploitation strategies and are used to infer community assembly processes along environmental gradients. However, little is known about variations in leaf and root traits and their drivers along elevations in mountain forests. Location Yulong Mountain, southeastern Hengduan Mountains, Southwest China. Taxon Seed plants. Methods We measured six leaf traits and seven root traits across 47 woody species and collected environmental variables from forest plots along a 1200 m elevational gradient. We employed linear mixed models to examine how resource exploitation strategies (community‐weighted mean, CWM) and functional diversity (standardised effect size of RaoQ, SES.RaoQ) associated with leaf and root traits varied along elevations. Furthermore, we determined the relative effects of environmental variables on these metrics. Results We observed that the resource exploitation strategy of leaves shifted from an acquisitive to a conservative strategy (higher leaf carbon concentration) with increasing elevation. Conversely, root trait variation exhibited an opposite trend, shifting from a conservative to an acquisitive strategy (higher root branching intensity but lower root diameter and root tissue density) along elevations, potentially influenced by mycorrhizal interactions. We detected functional convergence for leaf and root traits across elevations, with a greater degree of functional convergence at high elevations. Leaf trait convergence was closely linked to soil nitrogen conditions, whereas root trait convergence was associated with soil organic carbon levels. Main Conclusions Our results highlight that the patterns of resource exploitation strategies along elevational gradients are decoupled for leaf and root traits, with distinct environmental factors shaping the convergence of root and leaf traits. We argue that forest communities in mountain ecosystems may modify their resource exploitation strategies and functional diversity through varying combinations of leaf and root traits to improve resilience to future global change.

Long-term settlement of deepsea pipelines on a soft clayey seabed: Poro-elasto-viscoplastic modeling - Jun Cheng; Jian Li; Fu-Ping Gao; Zhen-Yu Yin (Ocean Engineering, 2025)

Mineralized degradation of bisphenol A by novel photoenzyme-metal catalyst FCAP@Ag3PO4/Lac-Pd beads - Linmeng Ma; Ping Xue; Zhiguo Gao; Chongrui Xu; Peng Li (Journal of Environmental Management, 2025)

Catalytic-difference elucidating of hesperidin and naringin by Rhamnosidase and prunin production enhancing through enzyme mutation - Xinpeng Li; Ping Chen; Lin Chen; Sheng Gao; Zhendong Wang; Siming Zhu (Food Bioscience, 2025)

A green-solvent processed multifunctional bamboo composite with high strength, robust fire retardancy, and dimensional stability - Xiangyu Ren; Huijun Zhang; Weibing Xue; Tongda Liu; Rong Liu; Xin Ran; Ping Wang; Wei Gao; Yanmei Li; Guanben Du; Long Yang (Chemical Engineering Journal, 2025)

GWAS and GS analysis revealed the selection and prediction efficiency for yield, plant morphological, and fiber quality in Gossypium barbadense - Tao Yang; Honggang Wang; Jikun Song; Kang Zhao; Bo Pang; Yongpan Wang; Ping Luo; Weiwei Liang; Shunyu Shi; Jie Wang; Yifeng Lin; Jing Li; et al. (Theoretical and Applied Genetics, 2025)

Dynamics of Suspended Sediment Variability Over Various Timescales: A Quantitative Analysis Using Remote Sensing Data - Zhiyun Du; Hangjie Lin; Qian Yu; Yunwei Wang; Yun Peng; Li Wang; Shu Gao; Ya Ping Wang (Estuaries and Coasts, 2025)

Lithofacies Types and Pore Structure Characteristics of Marine Shale in the Lower Cambrian Shuijingtuo Formation, Middle Yangtze Region, China - Jialin Fan; Wei Liu; Yujing Qian; Jinku Li; Qin Zhou; Ping Gao (Journal of Marine Science and Engineering, 2025)
The lithofacies and pore structural characteristics of shale reservoirs directly affect the exploration and development of shale gas. To clarify the exploration and development potential of the Lower Cambrian Shuijingtuo Formation (SJT) shale in the Middle Yangtze region, China, this study employs integrated experimental approaches, including optical and scanning electron microscopy (SEM) observations, X-ray diffraction (XRD) mineralogical analysis, and low-pressure gas (N2/CO2) adsorption, to classify mudstone lithofacies within the SJT and elucidate pore structural characteristics and dominant geological control across different lithofacies. The research results show that (1) Six main types of shale lithofacies are found in the STJ, including low-TOC massive calcareous mudstone (LMCM), low-TOC laminated mixed mudstone (LLMM), medium-TOC massive mixed mudstone (MMMM), high-TOC massive mixed mudstone (HMMM), high-TOC laminated siliceous mudstone (HLSM), and laminated argillaceous mudstone (LAM). (2) The pore types of SJT mudstone primarily include organic pores, intragranular clay mineral pores, and microfractures. The pore structure of mudstone is mainly controlled by clay mineral content and TOC content. However, the controlling factors of pore structure vary among different mudstone lithofacies. LMCM and LLMM are dominated by intragranular clay mineral pores, with their pore structures mainly controlled by clay mineral content. The pore types of HLMM and HLSM are organic pores, with pore structures predominantly controlled by TOC content. (3) The SJT mudstone gas reservoir exhibits diverse types, including HLSM, LAM, and LLMM. HLSM is characterized by the highest brittleness index and elevated pore volume (PV) and it can be considered the optimum lithofacies in the study area. Additionally, LLMM has the highest PV and relatively high brittleness index, positioning it as another significant reservoir target in the study area. Therefore, the Lower Cambrian shale gas reservoirs in the Middle Yangtze region exhibit diverse reservoir types. These research findings provide a scientific basis for the next phase of shale gas exploration planning in the Lower Cambrian.

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

Tanshinone IIA inhibits neuronal ferroptosis and relieves cerebral ischemia‒reperfusion injury by regulating miR-449a/ACSL4 - Huimin Yu; Yili Li; Yuehong Yang; Yanjin Qian; Xia Gao; Xichan Wang; Ping Zhan; Dekun Tang; Mei Qin; Yan Qian (Metabolic Brain Disease, 2025)

Impact of the Yangtze River on Sediment source-to-sink processes in estuarine bays: a study of the Oujiang River Estuary, SE China - Xia Guang; Ping Yin; Ke Cao; Fei Gao; Yuan Tian; Xiangtong Huang; Bin Chen; Meina Li; Jinqing Liu (Frontiers in Marine Science, 2025)
Our study was designed to unravel the provenance signals of sediments from various sediment source-to-sink processes. To achieve this, we systematically collected samples from river basins, estuaries, and offshore waters of the Oujiang River estuary. Analyses of clay minerals and trace geochemical elements (Cr, Th, Sc) were then conducted. Our findings revealed a dynamic pattern of sediment distribution, with the predominant clay minerals in the surface sediment of the offshore area being illite, followed by kaolinite and chlorite, with a minor smectite content. Notably, we observed a gradual increase in the proportions of illite and smectite from the upstream to the estuary, while kaolinite decreased accordingly. The ratios of Cr/Th and Sc/Th in the small mountain rivers also showed a gradual increase, indicating a rising influence of fine-grained sediment from the Yangtze River. Furthermore, we utilized a robust nonlinear mathematical model to determine and quantify the sources and provenance contributions of the clay fraction sediment in the Oujiang River estuary. Our model results revealed that the majority (64%) of the clay fraction sediment in the offshore region of the estuary originates from the Yangtze River. In contrast, sediments from small mountain rivers, including the Oujiang River, contribute an average of 29%, but this can increase to 40% within the Oujiang River estuary and its southern areas. Coastal currents and tides influence the sediment distribution in coastal areas. The Zhe-Min Coastal Current plays a significant role in transporting sediments from the Yangtze River to the estuaries of Zhejiang Province, where they settle in the downstream areas of the current. Moreover, sediment from the Oujiang River is carried southward by the coastal current, most of which is deposited in the estuary and the nearby coastal waters to the south. In conclusion, our study underscores the significant influence of sediments from the Yangtze River on the surface sediments in small mountain rivers and offshore regions near the Zhejiang coastline.

Dress me an outfit: advanced probiotics hybrid systems for intelligent IBD therapy - Yonglu Li; Yadi Wang; Yapeng Li; Shihai Yan; Xin Gao; Ping Li; Xiaodong Zheng; Qing Gu (Critical Reviews in Food Science and Nutrition, 2025)

Cepharanthine mitigates NIBV-induced pyroptosis via the MDA5/NF-κB/NLRP3 signaling pathway - Zhenni Liu; Ruoyun Tang; Mengbing Ding; Meiqin Wu; Ying Li; Cheng Huang; Qiurong Qi; Ping Liu; Xiaona Gao; Xiaoquan Guo (Veterinary Microbiology, 2025)

High-value use of whole plants of Eupatorium Adenophora Spreng for aluminium in hydrochloric acid anti-corrosion - Yun Gao; Ping Zhu; Xianghong Li; Liqing Tang; Yongqiang Chen; Yi Zhang; Juan Xu (Sustainable Chemistry and Pharmacy, 2025)

Long-term effects of cropping regimes on soil organic carbon and aggregate stability in a Mollisol of Northeast China - Cuilan LI; Zhiyuan CAO; Mo ZHU; Hongjun GAO; Xiuzhi ZHANG; Ping ZHU; Jinjing ZHANG (Pedosphere, 2025)

Advancing autotrophic nitrogen removal in low C/N ratio wastewater: Innovative application of supercapacitor to enhance microbial electrolysis cells - Sen Fan; Yuhan Song; Decong Zheng; Xinyuan Peng; Sitao Li; Ping Gao; Daping Li (Journal of Environmental Sciences, 2025)

Ripening-stage variations in small metabolites across six banana cultivars: A metabolomic perspective - Huijun Gao; Ping Liu; Weidi He; Fangcheng Bi; Chunhua Hu; Guiming Deng; Tongxin Dou; Qiaosong Yang; Chunyu Li; Ganjun Yi; Ou Sheng; Tao Dong (Food Chemistry, 2025)

Characterization of GR-14 peptide from Cordyceps militaris mycelial albumin and its mechanism of heat protection on Lactobacillus fermentum J26 - Ping-Ping Gao; Han-Qing Liu; Qian-Wang Zheng; Zhi-Wei Ye; Li-Qiong Guo; Yuan Zou; Jun-Fang Lin (Food Bioscience, 2025)

Energy transfer strategy inspired by TADF molecules for efficient and UV-Robust perovskite solar cells - Ping Hu; Liujiang Zhang; Ruoxin Yang; Rongen Guo; Xingyu Gao; Mingdeng Wei; Yafeng Li (Chemical Engineering Journal, 2025)

Graph Neural Networks and Multimodal DTI Features for Schizophrenia Classification: Insights from Brain Network Analysis and Gene Expression - Jingjing Gao; Heping Tang; Zhengning Wang; Yanling Li; Na Luo; Ming Song; Sangma Xie; Weiyang Shi; Hao Yan; Lin Lu; Jun Yan; Peng Li; et al. (Neuroscience Bulletin, 2025)

Three-Dimensional Shallow P-wave Velocity Distribution in the Source Area of the 2021 MS6.0 Luxian Earthquake from Dense Array Seismic Imaging - Jian-xun Yang; Qi-yan Yang; Da-hu Li; Yong-ming Lu; Ping-ping Wu; Hui-li Guo; Ning-bo Jiang; Mi Gao; Heng Pan (Applied Geophysics, 2025)

Spatial variability of lacustrine groundwater discharge and pollutant fluxes in the sandy-land lake group basins: Influence from land use types - Shen Qu; Xiangwei Li; Ao Gao; Yuanzhen Zhao; Keyi Zhang; Yiwei Zhang; Dongchao Huo; Bowen Ye; Zongbao Yue; Renpu Wang; Hongli Ma; Ping Miao; et al. (Journal of Environmental Management, 2025)

Tracing the Changjiang-derived sediments along the southeast coast of China during the Holocene - Yalong Li; Xin Shan; Xiangtong Huang; Zhanghua Wang; Jianhua Gao; Ping Yin; Quanhong Zhao; Juan Xu; Zhen Song; Shouye Yang (Global and Planetary Change, 2025)

RsWRKY44 participated in anthocyanin biosynthesis regulation in radish through interaction with RsMYB1a - Biao Lai; Chenxi Gao; Li jiang; Li Wen; Xushuo Zhang; Wei Shen; Yanling Yu; Hanbing Yang; Fabo Chen; Ping Fang; Lina Du (Plant Cell Reports, 2025)

Moisture–Microbial Interaction Amplifies N 2 O Emission Hot Moments Under Deepened Snow in Grasslands - Jie Luo; Yong Peng; Zhou Jia; Yuntao Wu; Yuxuan Gao; Nairsag Jalaid; Xingming Zhang; Heng Ge; Bowen Qing; Hongyi Chen; Yanxin Zhan; Ping Li; et al. (Global Change Biology, 2025)
Freeze–thaw‐induced N 2 O pulses could account for nearly half of annual N 2 O fluxes in cold climates, but their episodic nature, sensitivity to snow cover dynamics, and the challenges of cold‐season monitoring complicate their accurate estimation and representation in global models. To address these challenges, we combined in situ automated high‐frequency flux measurements with cross‐ecoregion soil core incubations to investigate the mechanisms driving freeze–thaw‐induced N 2 O emissions. We found that deepened snow significantly amplified freeze–thaw N 2 O pulses, with these ~50‐day episodes contributing over 50% of annual fluxes. Additionally, freeze–thaw‐induced N 2 O pulses exhibited significant spatial heterogeneity, ranging from 3.4 to 1184.1 μg N m −2 h −1 depending on site conditions. Despite significant spatiotemporal variation, our results indicated that 68%–86% of this variation can be explained by shifts in controlling factors: from water‐filled pore space (WFPS), which drove anaerobic conditions, to microbial constraints as snow depth increases. Below 43% WFPS, soil moisture was the overwhelmingly dominant driver of emissions; between 43% and 66% WFPS, moisture and microbial attributes (including denitrifying gene abundance, nitrogen enzyme kinetics, and microbial biomass) jointly triggered N 2 O emissions pulses; above 66% WFPS, microbial attributes, particularly nitrogen enzyme kinetics, prevailed. These findings suggested that maintaining higher soil moisture served as a trigger for activating microbial activity, particularly enhancing nitrogen cycling. Furthermore, we showed that hotspots of freeze–thaw‐induced N 2 O emissions were linked to high root production and microbial activity in cold and humid grasslands. Overall, our study highlighted the hierarchical control of WFPS and microbial processes in driving freeze–thaw‐induced N 2 O emission pulses. The easily measurable WFPS and microbial attributes predictable from plant and soil properties could forecast the magnitude and spatial distribution of N 2 O emission “hot moments” under changing climate. Integrating these hot moments, particularly the dynamics of WFPS, into process‐based models could refine N 2 O emission modeling and enhance the accuracy of global N 2 O budget prediction.

Anti-hypoxia polyacetylenes and sesquiterpenoids from Codonopsis pilosula (Franch.) Nannf - Zhuo-Yang Cheng; Jun-Ge Jin; Meng Yan; Xin-Yue Chen; Jian-Kuan Li; Jian-Ping Gao; Jiang-Tao Zhou (Natural Product Research, 2025)

Penicipyrrolidines A−N, pyrrolidine derivatives with inhibitory effects on EMT and fibroblast activation from the mangrove-derived fungus Penicillium sp. DM27 - Li-Ming He; Xuan Deng; Li-Hua Ni; Shi-Qi Cai; Jinhu Chen; Zejin Liao; Mengke Zhang; Hua Shui; Kong-Kai Zhu; Song Wu; Ping Gao; Ariel M. Sarotti; et al. (Marine Life Science & Technology, 2025)

Dynamic effects of Aeromonas sobria infection on intestinal morphology, microbiota and goblet cells of rainbow trout (Oncorhynchus mykiss) - Li-Ping Liu; Peng-Tian Kang; Feng-Yuan Ding; Dong-Hong Shao; Bao-Shan Wang; Juan Yang; Wen-Hui Gao; Wang-Dong Zhang; Wen-Hui Wang; Ji-Xing Liu (Aquaculture, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Dry season dominance of salinity’s impact on hydrogen isotope fractionation in Aegiceras corniculatum mangrove lipids - Yao-Ping Wang; Zhiguang Song; Jia Xia; Zhao-Wen Zhan; Alex L. Sessions; Shaelyn N. Silverman; Yuan Gao; Guopeng Li; Ding He (Geochimica et Cosmochimica Acta, 2025)

Screening, identification, and mechanism of novel antioxidant peptides in walnut meal under aerobic stress - Hui Ouyang; Xiaolong Liu; Jiaying Huo; Ping Wang; Tingting Xie; Xiongwei Yu; Shugang Li; Ying Gao (Food Chemistry, 2025)

High-Voltage aqueous supercapacitors based on l-lysine pH Self-Buffering Coating-modified carbon cloth electrode - Ang Xu; Jie Gao; Huan Li; Xiyu Song; Bo Xu; Ying Liu; Yuanyuan Yu; Ping Wang; Qiang Wang; Man Zhou (Chemical Engineering Journal, 2025)

Experimental investigation of scour effects on regular and breaking wave loads on a monopile - Biao Li; Wen-Gang Qi; Fu-Ping Gao; Ben He; Li-Jing Yang (Coastal Engineering, 2025)

Aberrance of GAP43/p-GAP43 Closely Associates with the Pathology of Neuron Loss in Prion-Infected Rodent Models - Xiao-Xi Jia; Cao Chen; Chao Hu; Yue-Zhang Wu; Zhi-Yue Chao; Jia-Feng Zeng; Ru-Han A.; Dong-Hua Zhou; Yuan Wang; Wei-Wei Zhang; Kang Xiao; Li-Ping Gao; et al. (Molecular Neurobiology, 2025)

RIPK3 activation of CaMKII triggers mitochondrial apoptosis in NIBV-infected renal tubular epithelial cells - Ying Li; Qiurong Qi; Yifei Chen; Mengbing Ding; Manzi Huang; Cheng Huang; Ping Liu; Xiaona Gao; Xiaoquan Guo; Zhanhong Zheng (Veterinary Microbiology, 2025)

Study on the efficiency and mechanism of anaerobic biological treatment coupled with micro-electric field - Zhongchen Yu; Jiangshan Xiang; Qiushi Zhao; Ping Chen; Xigui Dong; Ke Li; Song Wang; Shengxiao Gao (Journal of Water Process Engineering, 2025)

Environmental factors ultraviolet a and ozone exacerbate the repeated inhalation toxicity of 6PPD in mice via accelerating the aging reaction - Xianjie Li; Caixia Wu; Ping Yang; Yanxi Li; Shuai Wang; Dan Cai; Ran Wei; Jinfeng Gao; Xuemei Wen; Jieping Luo; Rui Wang; Xueyuan Bai; et al. (Journal of Hazardous Materials, 2025)

Molecular networking and Paterno-Büchi reaction guided glycerides characterization and antioxidant activity assessment of Ganoderma lucidum spore oil - Qing-Xuan Ren; Rui Wang; Qin-Ru Mu; Ling Chen; Min Chen; Li-Jiang Wang; Ping Li; Hua Yang; Wen Gao (Food Chemistry, 2025)

Defective Zn1-xCuxS nanosheet as efficient and durable cathode catalyst for photo-assisted Li-O2 batteries - Cong-Cong Dang; Yi-Ping Liu; Yu-Xin Huang; Xin-Yi Zhang; Zhen-Yi Gu; Jun-Ming Cao; Jin-Zhi Guo; Li-Ming Gao; Xing-Long Wu; Yi-Chun Liu (Chemical Engineering Journal, 2025)

Sulfurized anthracene as a new cathode material for highly reversible magnesium storage - Xi Chen; Sibylle Riedel; Sirshendu Dinda; Ting Wang; Fangfang He; Xiaojian Tu; Jinfeng Peng; Hans Joachim Räder; Björn Schmidt; Raiker Witter; Zhenyou Li; Maximilian Fichtner; et al. (Chemical Engineering Journal, 2025)

Effect of Particle Size, Sphericity, and Distribution on Seepage in Granular Porous Media - Bo-bo Xiong; Rui Kuang; Ping Zhang; Bin Tian; Hong-hu Gao; Qian Zheng; Yu-qin Li (Geotechnical and Geological Engineering, 2025)

Simulation study of the production efficiency of family-type agricultural management entities under regulation measures on farmland: Three-stage super-SBM model considering greenhouse gas emissions - Shuqi Dong; Renjie Hou; Tianxiao Li; Qiang Fu; Ping Xue; Yu Gao; Zhaoqiang Zhou; Qinglin Li (Agricultural Systems, 2025)

Forest Microclimate as a Driver of Epiphytic Bryophyte Diversity Along a Subtropical Elevational Gradient - Zun Dai; Shi‐chen Xing; S. Robbert Gradstein; Min Li; Shu‐wen Tu; Xing Chen; Xue Yao; Shuang Gao; Rui‐ping Shi; Lu‐yan Tang; Ran Zhang; Zhao‐chen Zhang; et al. (Journal of Biogeography, 2025)
Aim Considering the importance of microclimate in maintaining the diversity of epiphytic bryophytes, we investigated epiphytic bryophytes along an elevational gradient in the subtropical forest of eastern China to unravel the diversity patterns of epiphytic liverworts and mosses along the elevational gradients and the roles of forest microclimates, topographic variables and host plant composition attributes in shaping these elevational diversity patterns. Location Tianmushan National Nature Reserve, Zhejiang, China. Taxon Epiphytic bryophytes. Methods Species diversity patterns of liverworts and mosses were compared based on an inventory of 16 plots along an elevational gradient from 367 to 1470 m. In situ microclimatic data of air temperature and moisture were collected under constant monitoring for over 3 years. Spatial linear models and structural equation models were used to assess the relative roles of the environmental variables in shaping the patterns of species diversity along elevation. Results We found that epiphytic liverwort and moss richness showed different elevational patterns; overall richness patterns of epiphytic bryophytes were largely driven by mosses. Epiphytic mosses exhibited a decline, followed by a hump‐shaped pattern of species richness with increasing elevation, while epiphytic liverworts showed a mid‐elevation plateau with a richness maximum between 800 and 1300 m. Forest microclimate, topography and host plant composition attributes influence epiphytic moss and liverwort patterns differently and interact in a complex way. Overall, species richness of epiphytic liverworts was most strongly affected by microclimate (mean annual air temperature of growing season) and of epiphytic mosses richness by topography (slope). Further, epiphytic liverwort species richness was more influenced by temperature than moisture. Main Conclusions This study highlights the importance of collecting climatic factors at a fine scale (microhabitats) for understanding the patterns and drivers of bryophyte diversity. Further, our findings demonstrate the differences between liverworts and mosses in terms of their response to different environments in the forest ecosystem.

Active polysaccharides: a new roadmap for the prevention and treatment of food allergy - Hongge Yu; Tian Yu; Xin Li; Ping Tong; Jinyan Gao; Xuanyi Meng; Juanli Yuan; Zhihua Wu; Anshu Yang; Xueling Jin; Yong Wu; Hongbing Chen (Critical Reviews in Food Science and Nutrition, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Barley2035: A decadal vision for barley research and breeding - Congcong Jiang; Jinhong Kan; Guangqi Gao; Christoph Dockter; Chengdao Li; Wenxue Wu; Ping Yang; Nils Stein (Molecular Plant, 2025)

Mangrove flourishing/deterioration under the control of the Indian Summer Monsoon over the past ∼3,195 years in Phang Nga Province, Thailand - Yuanqin Xu; Wenjie Yu; Ping Li; Jie Liu; Somkiat Khokiattiwong; Narumol Kornkanitnan; Wei Gao (Marine Environmental Research, 2025)

Greenhouse gas fluxes and their determining factors in salt marsh wetlands along the south shore of Hangzhou Bay, East China Sea - Fei Wang; Xiaoyong Duan; Gang Tong; Xue Li; Ke Cao; Xingliang He; Bin Chen; Fei Gao; Ping Yin; Xianguo Li; Dahai Zhang (Journal of Environmental Management, 2025)

Cu/TiO2 adsorbents modified by air plasma for adsorption–oxidation of H2S - Yongqi Yan; Xinyu Yang; Ping Ning; Chi Wang; Xin Sun; Fei Wang; Peng Gao; Kai Li (Journal of Environmental Sciences, 2025)

CRISPR/Cas9-mediated knockout of Tektin 4-like gene (TEKT4L) causes male sterility of Cydia pomonella - Zihan Wei; Chang Wang; Xinyue Zhang; Yuntong Lv; Yuting Li; Ping Gao; Xueqing Yang (Insect Biochemistry and Molecular Biology, 2025)

A smartphone-integrated bimetallic ratiometric fluorescent probe for specific visual detection of tetracycline antibiotics in food samples and latent fingerprinting - Yin-Xia Sun; Bo-Tao Ji; Jiang-Hai Chen; Li-Ping Liu; Lu-Lu Gao; Zhe-Peng Deng; Yu Sun; Jian-Jun Wang; Biao Zhao; Jin-Guo Li (Food Chemistry, 2025)

Optimization of Melliodendron xylocarpum multiplication medium formulation using response surface methodology - Yiting Gu; Chen Wang; Yifan Leng; Ping Gao; Min Li; Shusheng Wen (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Plasma Ionomic Profile and Interaction Patterns in Coronary Artery Disease Patients - Qing-Qing Zhao; Xian-Long Shu; Zhen Yuan; Qian Gao; Ying Huang; Yuan-Qing Yang; Li-Ming Peng; Guo Wang; Xiao-Ping Chen; Bi-Lian Chen; Jie Tang (Biological Trace Element Research, 2025)

The spatiotemporal changes and influencing mechanisms of the coastline in the Yellow River Delta, China - Zhuo Yang; Wei Gao; Wenjie Yu; Jie Liu; Jun Du; Ping Li; Yuanqin Xu; Ping Li (Frontiers in Marine Science, 2025)
Using remote sensing imagery of the Yellow River Delta (YRD) from 1984 to 2024, the Digital Shoreline Analysis System (DSAS) model was employed to analyze the coastline position, migration rate, and characteristics of four typical coastal sections. The response of the coastline changes in the study area to global climate change and human activities was quantitatively assessed. Over the past 40 years, the modern YRD coastline has generally advanced seaward at an average rate of 109.64 m/a. This progression can be divided into three distinct phases: (i) The rapid transition period from 1984 to 2000, during which the total coastline length reached its maximum of nearly 440.65 km in the last 40 years. In 1986, the proportion of artificial coastline surpassed that of natural coastline for the first time. (ii) A decreasing trend in total coastline length characterized the slow transition period from 2000 to 2015. The transition in coastline types continued the trend of the previous period, with artificial coastlines exceeding 90% for the first time in 2015, marking the highest proportion in the past 40 years. (iii) The stable period from 2015 to the present, during which the total coastline length has shown an increasing trend. The artificial coastline has stabilized, while the growth of the natural coastline has been concentrated around the Yellow River estuary. However, the increase in the natural coastline has gradually slowed due to water and sediment regulation projects from 2001. The evolution of the coastline in the YRD has shifted from early control by river diversions to a current primary influence from human-driven land reclamation projects. Coastal changes in the present estuarine sections are mainly controlled by Yellow River water and sediment inflows, while abandoned northern channels experience pronounced effects from extreme weather, such as cold wave-induced winds. Additionally, factors such as sea-level rise due to global climate change and delta subsidence caused by sediment compaction have lowered the relative elevation of the coastline, further accelerating its erosion and retreat. However, these natural factors have had a lesser impact on coastline evolution than river diversions and human activities.

Molecular fractionation mediates genotoxicity evolution of hydrochar-derived dissolved organic matter at the iron oxyhydroxides-water interface - Yan-Jun Liu; He-Yun Yang; Shu-Xian Gao; Zheng-Hao Li; Yan-Yun Hu; Xing Zheng; Guo-Ping Sheng (Water Research, 2025)

Hydrogeochemical mechanism of Li-Cs-rich thermal springs in the Karakoram Fault, Qinghai-Xizang Plateau: New insights from multiple stable isotopes - Sheng Pan; Ping Zhao; Haichao Zhang; Zhaoying Yang; Yanyan Li; Yahui Yue; Xiaoming Liu; Shaopeng Gao; Yali Sun; Ji Dor (Science of The Total Environment, 2025)

Structurally diversified sesquiterpenoids from Chloranthus henryi and their neuroprotective activities on H2O2 damaged PC12 cells - Meng-Li He; Lian-Lian Xu; Yang Liu; Yan-Ping Gao; Yong-Ming Luo; Rong-Cai Yue; Fang-You Chen (Phytochemistry, 2025)

Penicipyrrolizidinones A−C, three pyrrolizidinone alkaloids with unprecedented skeletons from the mangrove-derived fungus Penicillium sp. DM27 - Zhenling Chen; Jing-Jing Zhang; Cheng-Yun Huang; Wei-Chen Chen; Li-Ming He; Qing-Qing Tang; Kong-Kai Zhu; Jing Li; Ping Gao; Meng-Ke Zhang; You-Sheng Cai (Phytochemistry, 2025)

Analysis of carbon reduction potential from typical municipal solid waste incineration plants under MSW classification - Chenqi Gao; Rongxing Bian; Ping Li; Chengyue Yin; Xiao Teng; Jinran Zhang; Shudan Gao; Yating Niu; Yingjie Sun; Yanan Wang; Huawei Wang (Journal of Environmental Management, 2025)

Effects of reclamation on the distribution and diversity of comammox along the coastal wetlands of China - Dongyao Sun; Yinghui Jiang; Hengchen Wei; Jun Li; Dengzhou Gao; Xianbiao Lin; Cheng Chen; Guoyu Yin; Yifei Zhang; Lijun Hou; Min Liu; Ping Han (International Biodeterioration & Biodegradation, 2025)

PB@COF-derived core–shell Fe/Fe3O4/C composites with excellent electromagnetic wave absorption performance for the entire Ku band - Gang Li; Ruiyang Tan; Bohong Gao; Xinli Liu; Mingyuan Zhang; Ping Chen; Xinyi Wang (Chemical Engineering Journal, 2025)

The beneficial potential of protein hydrolysates as prebiotic for probiotics and its biological activity: a review - Ping-Ping Gao; Han-Qing Liu; Zhi-Wei Ye; Qian-Wang Zheng; Yuan Zou; Tao Wei; Li-Qiong Guo; Jun-Fang Lin (Critical Reviews in Food Science and Nutrition, 2024)

Combined effect of polystyrene nanoparticles and chlorpyrifos to Daphnia magna - Yu-Hang Zhang; Rong-Yao Gao; Few Zhu; Li-Min Fu; Jian-Ping Zhang (Chemosphere, 2024)

Promotion of antibiotic-resistant genes dissemination by the micro/nanoplastics in the gut of snail Achatina fulica - Yan-Mei Da; Xiao-Ru Yang; Ming-Jun Li; Shun-Shun Li; Ze-Ping Gao; Ying Zhang; Jian-Qiang Su; Guo-Wei Zhou (Science of The Total Environment, 2024)

Regulation of freshwater filamentous green algae (Cladophora) and its impact on malodorous volatile organic sulfur compound (DMS) by biomanipulation - Yutai Dai; Yu Lin; Ping Deng; Jiping Chen; Weijie Li; Qiang Gao; Hong Shen; Qiutong Peng; Mo Chen; Xuwei Deng (Science of The Total Environment, 2024)

Widespread coastal upwelling along the marginal Yangtze Platform (South China) during the early Cambrian: Implications for hyper-enrichment of organic matter - Jinku Li; Ping Gao; Xianming Xiao; Gary G. Lash; Shuangjian Li; Wei Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Eco-friendly, stable, and high-performance biochar prepared by a twice-modification scheme: Saccharification of raw materials & thermal air oxidation of biochar - Yundong Liu; Bu Li; Wang Kai Tong; Han Tang; Zhaoli Ping; Wenjuan Wang; Min-tian Gao; Chaomeng Dai; Nan Liu; Jiajun Hu; Jixiang Li (Journal of Environmental Management, 2024)

Snow depth retrieval method for PolSAR data using multi-parameters snow backscattering model - Haiwei Qiao; Ping Zhang; Zhen Li; Lei Huang; Zhipeng Wu; Shuo Gao; Chang Liu; Shuang Liang; Jianmin Zhou; Wei Sun (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Green fabrication of modified lignin/zeolite/chitosan-based composite membranes for preservation of perishable foods - Zhan-Chao Li; Meng-Yao Su; Xiao-Yu Yuan; Hai-Qing Lv; Rui Feng; Li-Jie Wu; Xiao-Ping Gao; Yan-Xia An; Zhan-Wei Li; Miao-Yun Li; Gai-Ming Zhao; Xiao-Peng Wang (Food Chemistry, 2024)

Quality improvement of threadfin bream (Nemipterus virgatus) surimi-gel using soy protein as a natural food additive - Yi-Li Gao; Asami Yoshida; Jin-Yang Liu; Jing Yuan; Shinnosuke Maeda; Youjun Wang; Yan-Rong Jiang; Xiao-Mi Sun; Chao-Ping Chen; Yajun Wang; Tetsuhiko Okajima; Kiyoshi Osatomi (Food Chemistry, 2024)

Dendrobium huoshanense stem polysaccharide exhibits gastroprotective effect via regulating PI3K/AKT, NF-κB and Nrf-2 signaling in high-salt diet-induced gastritis mice - Hui-Yu Ye; Zhen-Zi Shang; Xin Gao; Xue-Qiang Zha; Feng-Yun Zhang; Qiang-Ming Li; Jian Liu; Jian-Ping Luo (Food Bioscience, 2024)

Unlocking superior preservation: The synergy of lignin and zeolite in chitosan-based composite films for perishable foods - Zhan-Chao Li; Xi Chen; Jia-Li Zhang; Xiao-Ping Gao; Yan-Xia An; Li-Jie Wu; Miao-Yun Li; Gai-Ming Zhao; Xiao-Peng Wang (Food Packaging and Shelf Life, 2024)

Multiple NADPH-cytochrome P450 reductases from Lycoris radiata involved in Amaryllidaceae alkaloids biosynthesis - Yuqing Wu; Yifeng Zhang; Haitong Fan; Jie Gao; Siyu Shen; Jifan Jia; Rong Liu; Ping Su; Yating Hu; Wei Gao; Dan Li (Plant Molecular Biology, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

Accumulation of Prion Triggers the Enhanced Glycolysis via Activation of AMKP Pathway in Prion-Infected Rodent and Cell Models - Qin Fan; Kang Xiao; Ruhan A; Li-Ping Gao; Yue-Zhang Wu; Dong-Dong Chen; Chao Hu; Xiao-Xi Jia; Chu-Mou Liu; Xin Liu; Cao Chen; Qi Shi; et al. (Molecular Neurobiology, 2024)

Polymorphisms of PRKAA1 and FABP4 genes and their association with feed efficiency in Hu sheep - Mengru Pu; Deyin Zhang; Liming Zhao; Dan Xu; Zongwu Ma; Kunchao Han; Lijuan He; Chengqi Yan; Qi Zhang; Lianjun Feng; Ziyue Xiao; Lei Gao; et al. (Small Ruminant Research, 2024)

Optimal extraction of polysaccharides from Stevia rebaudiana roots for protection against hydrogen peroxide-induced oxidative damage in RAW264.7 cells - Zhiyan Tang; Mingrui Zhang; Lan Gao; Yulong Bao; Ping Li; Ming Wang; Taili Shao; Guodong Wang; Chunyan Liu (Natural Product Research, 2024)

Aberrant Enhanced NLRP3 Inflammasomes and Cell Pyroptosis in the Brains of Prion-Infected Rodent Models Are Largely Associated with the Proliferative Astrocytes - Dong-Hua Zhou; Xiao-Xi Jia; Yue-Zhang Wu; Wei-Wei Zhang; Yuan Wang; Dong-Lin Liang; Li-Ping Gao; Kang Xiao; Cao Chen; Xiao-Ping Dong; Qi Shi (Molecular Neurobiology, 2024)

Rosgen stream classification and fluvial processes of the Shiyang River, China - Ping Li; Hongshan Gao; Zongmeng Li; Yajie Wu; Fenliang Liu; Tianqi Yan; Yingying Chen (Journal of Mountain Science, 2024)

Microplastics stress alters microorganism community structure and reduces the production of biogenic dimethylated sulfur compounds - Qian Liu; Xu‐Xu Gao; Yan Li; Yong Jiang; Juan Yu; Shan‐Shan Liu; Xiao‐Ping Lang; Gui‐Peng Yang (Limnology and Oceanography, 2024)
Dimethylsulfoniopropionate (DMSP) is a plentiful organic sulfur metabolite and the primary precursor for dimethyl sulfide (DMS), which plays a crucial role in global sulfur cycling, the formation of clouds, and cooling the warming earth. The origin and fate of DMSP are intricately linked to marine microorganisms, making the variation of the microorganism community crucial for DMSP dynamics. Nonetheless, the impact of pervasive marine microplastics on microorganisms and processes related to DMSP synthesis and degradation remains insufficiently investigated. To bridge this gap, a 14‐d deck‐based microcosm experiment was conducted, revealing that microplastics significantly altered the composition of microorganism communities and dramatically inhibited the release of DMS and DMSP. Furthermore, multivariate analysis demonstrated that the variations both in environmental variables and microorganism communities caused by microplastics were forcing factors in reducing DMS and DMSP release. In addition, the predicted function of the bacterial community showed a significant reduction in the presence of dddP and dmdA genes when exposed to microplastics, which directly disrupted both the demethylation and cleavage pathways of DMSP. These results indicate that the release of DMS and DMSP in marine ecosystems can be significantly affected by microplastics through influencing microorganisms. Thus, it is imperative to conduct research on controlling the synthesis and degradation of DMSP in the ocean, particularly in response to these environmental pollution issues. Such research can help discern new patterns from specific phenomena and identify crucial processes.

Exploring the material basis and molecular targets of Changma Xifeng tablet in treating Tourette syndrome: an integrative approach of network pharmacology and miRNA analysis - Jing Peng; Qiaoling Li; Linhui Liu; Ping Gao; Lipeng Xing; Li Chen; Hui Liu; Zhisheng Liu (Metabolic Brain Disease, 2024)

Divergent chemical compositions of soil organic matter size fractions under long-term amendments across a climate gradient - Fanbo Song; Ning Hu; Yilai Lou; Huimin Zhang; Ping Zhu; Dongchu Li; Hongjun Gao; Shuiqing Zhang; Yidong Wang (Soil and Tillage Research, 2024)

Occurrence and maturation transformation of organic and inorganic nitrogen in the Lower Cambrian shelf–slope facies shale: Implications for overmature N2-rich shale reservoirs in Southern China - Guangming Meng; Haifeng Gai; Xiumin Yang; Ping Gao; Qin Zhou; Chengang Lu; Gang Li; Xing Wang; Peng Cheng (Marine and Petroleum Geology, 2024)

Discovery of anti-melanogenic components in persimmon (Diospyros kaki) leaf using LC-MS/MS-MN, AlphaFold2-enabled virtual screening and biological validation - Jiazheng Liu; Ting Xu; Jianjun Ding; Haoyue Wen; Jieru Meng; Qing Liu; Xiaomei Liu; Wei Zhang; Guo-Yuan Zhu; Zhi-Hong Jiang; Jin Gao; Li-Ping Bai (Food Chemistry, 2024)

Exploring the lipid oxidation mechanisms during pumpkin seed kernels storage based on lipidomics: From phenomena, substances, and metabolic mechanisms - Li Pan; Weijian Xu; Ying Gao; Hui Ouyang; Xiaolong Liu; Ping Wang; Xiongwei Yu; Tingting Xie; Shugang Li (Food Chemistry, 2024)

Positively charged loose nanofiltration membranes via the assembly of amino-quinone networks for efficient dye/salt separation - Tian Gao; Ping Fu; Wan-Long Li; Wan-Ting Lin; Yuan-Hui Yu; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Desalination, 2024)

Scour-induced unloading effects on lateral response of large–diameter monopiles in dense sand - Li Biao; Qi Wen-Gang; Wang Yifa; Gao Fu-Ping; Wang Shun-Yi (Computers and Geotechnics, 2024)

Microbial metabolism strengths carbon sequestration and crop yield in upland red soil after long-term ex situ incorporation of straw - Li Tang; Xiaobin Guo; Daoyou Huang; Xiaomeng Wei; Hao Sheng; Pei Luo; Ping Zhou; Wei Gao; Yan Li; Miaomiao Zhang; Wei Zheng; Jinshui Wu (Journal of Soils and Sediments, 2024)

Modeling the Impacts of Land Reclamation on Sediment Dynamics in a Semi-Enclosed Bay - Yi Zhong; Jun Du; Yongzhi Wang; Ping Li; Guoqiang Xu; Hongbin Miu; Peiyu Zhang; Shenghui Jiang; Wei Gao (Journal of Marine Science and Engineering, 2024)
Semi-enclosed bays are significantly influenced by the interactions between land and sea, as well as human activities. One notable human activity, land reclamation, impacts water exchange within these bays. However, the variability of sediment transport and cross-bay transport following reclamation remains poorly understood. This study aims to enhance the understanding of sediment dynamics and the responses of cross-bay transport to reclamation. A well-validated three-dimensional numerical model was developed in the Laizhou Bay (LB). Following reclamation, tidal currents suspended sediment concentration, and erosion increased seaward, while these factors decreased landward. In LB, surface and bottom subtidal currents flowed in opposite directions, with the direction of volume transport primarily determined by bottom currents. In the western LB, volume and sediment transport exhibited an anticyclonic pattern, with pronounced seasonal variations observed elsewhere. During summer, volume and sediment transport predominantly occurred from the northeast to the southwest. In winter, volume transport in northern LB was directed westward, while it was eastward in the southern part; sediment transport was primarily eastward. Advection played a significant role in sediment transport dynamics. The pathway of cross-bay sediment transport was primarily located in the central part of the bay. Notably, the cross-bay sediment transport flux in winter was approximately 3.5 times greater than in summer, with reclamation resulting in a reduction in cross-bay transport flux by about 22.17%.

Seasonal changes of plankton community and its influencing factors in subtropical coastal marine areas revealed by eDNA-based network analysis - Xiaoqi Lin; Kunhuan Li; Hancheng Zhao; Yan Gao; Zonghang Zhang; Lin Wang; Xinjie Wang; Edmond Sanganyado; Zhao Zheng; Qilin Gutang; Sailan Liu; Ping Li; et al. (Frontiers in Marine Science, 2024)
Introduction Coastal marine ecosystems are among the most ecologically and socio-economically dynamic regions on Earth, and the study of eukaryotic planktonic communities is an important aspect of aquatic ecology. It is essential to monitor plankton biodiversity and identify influencing factors in order to measure human effects on coastal waters and help contribute to ecosystem preservation. Environmental DNA (eDNA) metabarcoding analysis is an advanced toolfor detecting the presence of aquatic organisms, which has revolutionary significance for biodiversity monitoring and real-time detection of wild environments. Methods In this study, eDNA metabarcoding was used to study seasonal changes in eukaryotic plankton communities in subtropical coastal waters of the northern South China Sea, to explore how various trophic groups affect the complexity and stability of the species network. Results The results showed that the summer interaction network is looser and had has reduce biodiversitycompared to the spring interaction network. As an important part of the planktonic community, the abundance and diversity of algae reflect the interactions between different species and the influence of environmental factors on the dominant species, particularly temperature and nutrients. In addition, producer diversity set the basis for species network complexity and indirectly affected network stability, while consumer diversity and its flexible predation strategies may directly lead to differences in network stability across seasons. There were close correlations among species interaction, environmental factors and species diversity. Discussion This study can help us understand the ecosystem functions throughout the year and the complex interactions of planktonic communities from a multiple trophic level perspective, and provide effective methods for sustainable resource utilization and ecological environmental protection in the future.

Avermectin induced vascular damage in zebrafish larvae: association with mitochondria-mediated apoptosis and VEGF/Notch signaling pathway - Wei-Guo Wang; Xu-Feng Jiang; Cheng Zhang; Xiu-Ping Zhan; Jia-Gao Cheng; Li-Ming Tao; Wen-Ping Xu; Zhong Li; Yang Zhang (Journal of Hazardous Materials, 2024)

Trade-offs of reproductive growth and Cd remobilization regulated Cd accumulation in wheat grains (Triticum aestivum L.) - Ying Wang; Pei-Pei Gao; Yu-Meng Shang; Rong-Rong Jia; Yu-Cheng Wang; Xiang-Yu Li; Li-Ping Geng; Yong Zhao; Joshua Walrath; Wen-Ju Liu (Journal of Hazardous Materials, 2024)

The role of hydrogen-rich water in delaying the pulp breakdown of litchi fruit during postharvest storage - Huijun Gao; Feiyan Li; Xi Chen; Ziming You; Lei Wei; Yuanlong Liu; Ping Liu; Mingyang He; Min Hong; Hong Zhu; Xuewu Duan; Yueming Jiang; et al. (Food Chemistry, 2024)

Rapid evaluation of the quality of Smilax glabra Roxb. using QADS based on FT-NIR combined with multiple intelligent algorithms - Geng-zhi Zhan; Xin-yue Guo; Zi-chao Qiu; Lu-yao Cai; Qian Hu; Ye Gao; Shu-wan Tang; Cun-yu Li; Yun-feng Zheng; Guo-ping Peng (Food Chemistry, 2024)

Lipid matrix-specific pretreatment method for enhancing the extractability and allergenicity maintenance of bovine milk allergens in ELISA detection - Wei Hu; Ziyi Xiong; Xuanyi Meng; Yong Wu; Ping Tong; Jinyan Gao; Xin Li; Hongbing Chen (Food Chemistry, 2024)

Real-time PCR method based on single-copy nuclear DNA sequences for the quantitative detection of pork adulteration in processed beef products - Lijuan Chang; Ping Huang; Jikai Liu; Chengping Fu; Wenjuan Liu; Yongfeng Gao; Yuanhong Li; Yongling Liu; Ailin Long (Food Control, 2024)

Ocean acidification alters microeukaryotic and bacterial food web interactions in a eutrophic subtropical mesocosm - Ruiping Huang; Ping Zhang; Xu Zhang; Shouchang Chen; Jiazhen Sun; Xiaowen Jiang; Di Zhang; He Li; Xiangqi Yi; Liming Qu; Tifeng Wang; Kunshan Gao; et al. (Environmental Research, 2024)

Facilitating proton-coupled electron transfer for energy-efficient CO2 desorption by C@ZrO2 hollow composites - Yao Shen; Ke Wang; Lu Li; Jingkai Zhao; Jiexu Ye; Ping Chen; Xiang Gao; Shihan Zhang (Chemical Engineering Journal, 2024)

Antibacterial and gut health effects of Amomum tsao‐ko in aquatic feed: A sustainable alternative to chemical antibiotics - Weiyao Peng; Guohui Liao; Lianzhang Wu; Jian Zhang; Juncai He; Penghui Gao; Yunsheng Cha; Shengjun You; Mei Huang; Jilan Zhou; Yuqiu He; Yi Yang; et al. (Journal of Fish Biology, 2024)
Amomum tsao‐ko Crevost et Lemarie (Zingiberaceae), an aromatic plant, has been considered to have diverse medicinal values and economic significance. It has been reported to possess antibacterial, antioxidant, and antidiabetic effects. With the increasing risk of diseases in aquaculture, there is a need for alternative solutions to chemical antibiotics. Plant extracts have shown promise as natural feed additives for aquatic animals. In this study, the antibacterial effect of Amomum tsao‐ko crude extracts was evaluated using the Oxford cup method. The extracts exhibited significant antimicrobial activity against Salmonella typhimurium and Salmonella enteritidis . Furthermore, the addition of Amomum tsao‐ko to fish feed resulted in notable changes in the gut structure of zebrafish and tilapia. The length and morphology of intestinal villi were enhanced, promoting improved digestion. Analysis of the gut microbial community revealed that Amomum tsao‐ko supplementation induced key changes in the gut microbial community composition of both zebrafish and tilapia. Notably, a 1% inclusion of Amomum tsao‐ko resulted in a marked rise in Proteobacteria levels in zebrafish, which diminished at 10% dosage. The supplement elicited mixed reactions among other bacterial phyla like Actinobacteria and Verrucomicrobiota. Fluctuations were also observed at the genus level, pointing to the concentration of Amomum tsao‐ko playing a pivotal role in influencing the structure of intestinal bacteria. The findings of this study suggest that Amomum tsao‐ko has antibacterial properties and can positively influence the gut health of fish. The potential use of Amomum tsao‐ko as a natural feed additive holds promise for improving aquaculture practices and reducing reliance on chemical antibiotics. Further research is needed to explore the full potential and applications of Amomum tsao‐ko in fish feed development.

T Cells Trafficking into the Brain in Aging and Alzheimer’s Disease - Yue-Zhang Ma; Jia-Xin Cao; Yi-Shu Zhang; Xiao-Mei Su; Yu-Hong Jing; Li-Ping Gao (Journal of Neuroimmune Pharmacology, 2024)

Microbial metabolic capacity regulates the accrual of mineral-associated organic carbon in subtropical paddy soils - Zhe Li; Xun Duan; Xiaobin Guo; Wei Gao; Yan Li; Ping Zhou; Qihong Zhu; Anthony G. O'Donnell; Ke Dai; Jinshui Wu (Soil Biology and Biochemistry, 2024)

Phase I clinical trial of intracerebral injection of lentiviral-ABCD1 for the treatment of cerebral adrenoleukodystrophy - Qiu-Hong Wang; Jing Wang; Zhi-Pei Ling; Zhi-Qiang Cui; Jie Gong; Rui Zhang; Shi-Jun Li; Yang-Yang Wang; Rui Yang; De-Hui Huang; Wen He; Jing Gao; et al. (Science Bulletin, 2024)

Experimental study on the synergistic strategy of liquid nitrogen and water mist for fire extinguishing and cooling of lithium-ion batteries - Ping Ping; Xinzeng Gao; Depeng Kong; Wei Gao; Zhenkai Feng; Can Yang; Chentong Li; Xinyi Dai (Process Safety and Environmental Protection, 2024)

Extrapolating time development curves of clear-water scour around piles: From empirical fitting to physics-based approach - Shun-Yi Wang; Wen-Gang Qi; Biao Li; Zhan Wang; Fu-Ping Gao (Ocean Engineering, 2024)

Evaluating the effects of laver cultivation on tidal flat erosion: Toward sustainable environmental practices - Dezhi Chen; Gaocong Li; Jieping Tang; Lintao Zhao; Ya Ping Wang; Chao Gao (Journal of Environmental Management, 2024)

Natural aromatic extract of black tea improved the water retention of pork meat batter - Wen-ping Xu; Rui-ling Dong; Ao-jing Lv; Yu-cong Li; Li-ting Zeng; Xue-ling Gao; Jun Qi; Zhou Lin; Hui-min Yan; Chun-hui Zhang; Guo-yuan Xiong (Food Research International, 2024)

Potential of Cordyceps militaris protein hydrolysates as prebiotic and thermo-protectants of Lactobacillus fermentum J26 - Ping-Ping Gao; Han-Qing Liu; Qian-Wang Zheng; Yuan Zou; Zhi-Wei Ye; Tao Wei; Li-Qiong Guo; Jun-Fang Lin (Food Bioscience, 2024)

Cactus-inspired moisture harvesting for sustainable and efficient high salinity desalination - Can Ge; Xianzhang Wu; Jiugang Li; Keshuai Liu; Duo Xu; Chong Gao; Yingcun Liu; Ping Sun; Ze Chen; Jian Fang (Desalination, 2024)

Negative rejection phenomenon in the mixed salt nanofiltration: Law and mechanism - Gao Xuerui; Li Ping; Qin Yuan; Bai Chengling; Gu Zhengyang; Yu Shuili (Desalination, 2024)

Tidal currents-induced scour development around pile foundations: Effects of flow velocity hydrograph - Shun-Yi Wang; Wen-Gang Qi; Biao Li; Chen Wang; Fu-Ping Gao (Coastal Engineering, 2024)

Mining for QTL controlling maize low-phosphorus response genes combined with deep resequencing of RIL parental genomes and in silico GWAS analysis - Bowen Luo; Peng Ma; Chong Zhang; Xiao Zhang; Jing Li; Junchi Ma; Zheng Han; Shuhao Zhang; Ting Yu; Guidi Zhang; Hongkai Zhang; Haiying Zhang; et al. (Theoretical and Applied Genetics, 2024)

Adenylate kinase phosphate energy shuttle underlies energetic communication in flagellar axonemes - Huan Wu; Yanman Zhang; Yuqian Li; Shuya Sun; Jintao Zhang; Qingsong Xie; Yue Dong; Shushu Zhou; Xuan Sha; Kuokuo Li; Jinyi Chen; Xin Zhang; et al. (Science China Life Sciences, 2024)

Effects of miR-204-5p and Target Gene EphB2 on Cognitive Impairment Induced by Aluminum Exposure in Rats - Wei Liu; Jie Gao; Niping Hao; Jing Li; Jing Pei; Danfeng Zou; Shuo Yang; Yuhua Yin; Xiaoming Yang; Ping Mu; Lifeng Zhang (Biological Trace Element Research, 2024)

Investigation of the mutual crosstalk between ER stress and PI3K/AKT/mTOR signaling pathway in iron overload-induced liver injury in chicks - Xiang-Long Lv; Wen-Lei Li; Feng-Jiao Sun; Yu-Zhi An; Ning Sun; Xiao-Ping Lv; Xue-Li Gao (BioMetals, 2024)

Energy-saving design of underground metro vertical alignment with deep reinforcement learning - Shuangting Xu; Tianci Gao; Dongying Yang; Xiaoyun Feng; Paul Schonfeld; Huailong Li; Ying Zhu; Ping Wang; Qing He (Tunnelling and Underground Space Technology, 2024)

Multiple stresses induced by chronic exposure to flupyradifurone affect honey bee physiological states - Jin Chen; Yong-Jun Liu; Qiang Wang; Li Zhang; Sa Yang; Wang-Jiang Feng; Min Shi; Jing Gao; Ping-Li Dai; Yan-Yan Wu (Science of The Total Environment, 2024)

Foliar uptake screening: A promising strategy for identifying wheat varieties with low lead accumulation - Liu-Xu Feng; Yu-Ning Li; Li-Ping Geng; Pei-Pei Gao; Xiang-Yu Li; Ding-Hao Li; Gui-Li Hua; Quan-Li Zhao; Wen-Ju Liu; Pei-Ying Xue (Science of The Total Environment, 2024)

Sediment dynamics on a subtidal reef flat of an atoll in the South China Sea - Jin Li; Andrew D. Ashton; Ya Ping Wang; Xiaomei Xu; Shu Gao (Marine Geology, 2024)

The fabrication of Mn single atoms/clusters on Al2O3 for enhanced catalytic NO oxidation - Xiao-Ke Hou; Hui-Xin Zhang; Yi-Bo Wang; Jin-Ping Zhang; Xin Gao; Lei Chen; Chao Li; Hong-Mei Jing; Chi He; Qiang Lu; Chun-Ran Chang (Fuel, 2024)

Thermostability-assisted limited proteolysis-coupled mass spectrometry for capturing drug target proteins and sites - Liu Yang; Chen-Wan Guo; Qi-Ming Luo; Zi-Fan Guo; Ling Chen; Yasushi Ishihama; Ping Li; Hua Yang; Wen Gao (Analytica Chimica Acta, 2024)

A simple and green offline-online capillary electrophoresis stacking strategy for the simultaneous determination of hydrophobic compounds in complicated samples using sodium dodecyl sulfate as the solubilizer and pseudophase - Yaxin Qin; Wei Gao; Jian Xu; Li Ping; Shengqiang Tong; Biao Liu; Chu Chu (Analytica Chimica Acta, 2024)

How extreme hydrological events correspond to climate extremes in the context of global warming: A case study in the Luanhe River Basin of North China - Ge Gao; Jianzhu Li; Ping Feng; Jia Liu; Yicheng Wang (International Journal of Climatology, 2024)
The consensus on climate warming is well‐established, and extreme values inherently encapsulate more information than averages. Against the backdrop of frequent extreme climate events, studying extreme values holds profound significance. This study aims to reveal the characteristics of extreme climate events and their role in triggering extreme hydrological events in the typical North China basin, that is, the Luanhe River Basin. Trends of 25 extreme climate indices during 1960–2018 are analysed using the Sen's slope and MK significance test to study the changing characteristics of extreme climate. Characteristics of extreme flood and dry events are examined, encompassing trend analyses at different time scales (seasonal, interannual, decadal) and concentration analysis. Finally, and most significantly, correlation analysis is conducted on extreme climate indices and features of extreme hydrological events, followed by principal component analysis of extreme climate indices, to precisely quantify the impact of extreme climate on the occurrence of extreme hydrological events. The results indicate a warming trend in extreme temperature indices, with a more significant rise in minimum temperatures compared to maximum temperatures. There is a significant decrease in precipitation, but precipitation at higher magnitudes is less affected by the overall reduction in total precipitation. Extreme dry events have markedly increased, particularly concentrated in winter with delayed occurrences, primarily induced by extreme temperature events, that is, warming effects. Conversely, extreme flood events have significantly decreased, mainly concentrated in summer and early autumn, predominantly caused by extreme precipitation and extreme high‐temperature events. The climate and hydrological conditions in the study area have become more extreme and complex. Severe river droughts may occur more frequently in winter, while extreme flooding may happen in summer. Therefore, it is necessary to pay more attention to these developments.

The origins of odor (β-cyclocitral) under different water nutrient conditions: Algae or submerged plants? - Yu Lin; Chaoyue Cheng; Yutai Dai; Weijie Li; Jiping Chen; Mo Chen; Ping Xie; Qiang Gao; Xiaoyue Fan; Xuwei Deng (Science of The Total Environment, 2024)

Evaluating the influence of high-temperature sterilization and pasteurization on volatile organic compounds in tomato stewed beef brisket: An analysis using gas chromatography-ion mobility spectrometry and multivariate statistical visualization - Jicai Bi; Chunyuan Ping; Zhuo Chen; Zhen Yang; Bian Li; Yueyue Gao; Yao Zhang; Hongju He (International Journal of Gastronomy and Food Science, 2024)

Environmentally relevant concentrations of benzophenones exposure disrupt intestinal homeostasis, impair the intestinal barrier, and induce inflammation in mice - Yu-Jia Lin; Hong-Mei Li; Yan-Rong Gao; Ping-Fan Wu; Bin Cheng; Chen-Long Yu; Yu-Xin Sheng; Hai-Ming Xu (Environmental Pollution, 2024)

Time development of clear-water scour around a pile foundation: Phenomenological theory of turbulence-based approach - Shun-Yi Wang; Wen-Gang Qi; Fu-Ping Gao; Biao Li; Ben He (Coastal Engineering, 2024)

Research and application progress of microbial β-mannanases: a mini-review - Ping Wang; Xiaohui Pei; Weiqiang Zhou; Yue Zhao; Pengfei Gu; Yumei Li; Juan Gao (World Journal of Microbiology and Biotechnology, 2024)

Severe nitrogen leaching and marked decline of nitrogen cycle-related genes during the cultivation of apple orchard on barren mountain - Yuwen Shen; Haining Chen; Haitao Lin; Ping Liu; Xiaozong Song; Yanan Ma; Mingli Li; Wensheng Gao; Lingling Song (Agriculture, Ecosystems & Environment, 2024)

Medial amygdala NRG1 signaling mediates adolescent social isolation-induced autistic-like behaviors - Lian-Hong Lin; Qian-Yun Wu; Kai Zeng; Zi-Yu Chen; Zi-Ping Wang; Wei-Min Li; Bin Zhang; Tian-Ming Gao; Ji-Hong Liu (Science Bulletin, 2024)

Spatio-temporal patterns of intense tropical cyclones in the Western North Pacific over the past 1600 years - Liang Zhou; Rumeng Hao; Mingchen Li; Yan Su; Shu Gao; Yang Yang; Zhixiong Shen; Jianjun Jia; Ya Ping Wang (Marine Geology, 2024)

Water distribution in pore systems and its influences on gas-bearing property of deep shale: A case study of the Longmaxi Formation in the Luzhou area, southern Sichuan Basin - Yue Feng; Xianming Xiao; Ping Gao; Dongfeng Hu; Ruobing Liu; Gang Li; Chengang Lu; Qin Zhou (Marine and Petroleum Geology, 2024)

High efficiency removal of NO using waste calcium carbide slag by facile KOH modification - Fang Wang; Hui Li; Jiyun Gao; Na Geng; Enzhu Jiang; Futing Xia; Mingwu Xiang; Lijuan Jia; Ping Ning (Journal of Environmental Sciences, 2024)

Three-dimensional multi-channel structure NiCo alloy used for boosting efficient overall water splitting - Fan Yang; Zelin Li; Fei Zhu; Xiaolong Chen; Songwei Ge; Fei Yin; Fairy Fan Yang; Rui Yang; Yanjing Liu; Lili Gao; Qiang Wang; Rui Feng; et al. (Fuel, 2024)

Improving flood forecasts capability of Taihang Piedmont basin by optimizing WRF parameter combination and coupling with HEC-HMS - Ting Zhang; Ya Gao; Ping Yu; Jianzhu Li; Ping Feng; Huixin Ma (Theoretical and Applied Climatology, 2024)

A New Perspective on the Semi-quantitative Meso-structural Failure Mechanism of Deep Weak Interlayer Zone Under Different Stress Paths - Shu-Qian Duan; Po Gao; Ding-Ping Xu; Bei Cao; Guo-feng Liu; Quan Jiang; Shi-Li Qiu; Jie-Cheng Xiong (Rock Mechanics and Rock Engineering, 2024)

Bakuchiol regulates TLR4/MyD88/NF-κB and Keap1/Nrf2/HO-1 pathways to protect against LPS-induced acute lung injury in vitro and in vivo - Li Zhao; Zhengliang Zhang; Ping Li; Yanxia Gao; Yu Shi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Complete genome analysis of a novel narnavirus in sweet viburnum (Viburnum odoratissimum) - Yangwei Gao; Zhongtian Xu; Ping Li; Xiaodi Hu; Jian-Ping Chen; Chuan-Xi Zhang; Yiyuan Li (Archives of Virology, 2024)

Exploring the release mechanism of micro/nanoplastics from different layers of masks in water: towards reduction of plastic contamination in masks - Wei Ge; Hao Liang; Ping Gao; Yan Li; Ningning Song; Juan Wu; Chao Chai (Environmental Science and Pollution Research, 2024)

Cevanine-type alkaloids from the bulbs of Fritillaria unibracteata var. wabuensis and their antifibrotic activities in vitro - Lu Fu; Wenyue Tian; Meng-Yu Bao; Zhiyan Liu; Wen-Jing Ren; Jiazheng Liu; Wei Zhang; Zhifeng Zhang; Jin Gao; Li-Ping Bai; Zhi-Hong Jiang; Guo-Yuan Zhu (Phytochemistry, 2024)

The removal mechanisms of HF and HCl gases using Mg-Al adsorbent prepared by sol-gel synthesis method - Peng Gao; Jiayu Feng; Yuxuan Xie; Xinyu Yang; Ping Ning; Xin Sun; Fei Wang; Lei Shi; Jie Zhao; Kai Li (Journal of Environmental Chemical Engineering, 2024)

Characterization of a pseudohemocyanin gene (PtPhc1) and its immunity function in response to Vibrio parahaemolyticus infection in the swimming crab Portunus trituberculatus - Yukun Li; Jianjian Lv; Dongfang Sun; Junyang Guo; Ping Liu; Baoquan Gao (Fish & Shellfish Immunology, 2024)

Hydro-meteorological factors and inflowing nutrients drive water quality in an impounded lake of China’s South-to-North Water Diversion Project - You Zhang; Mingyuan Gao; Rongkun Liu; Ping Cai; Junfeng Gao; Kuanyi Li; Yongjiu Cai (Environmental Science and Pollution Research, 2024)

The relationships between vertical variations of shallow gas and pore water geochemical characteristics in boreholes from the inner shelf of the East China Sea - Xue Li; Xiaoyong Duan; Xingliang He; Yongqing Xie; Lei Yang; Ping Yin; Ke Cao; Bin Chen; Fei Gao; Feng Li (Frontiers in Marine Science, 2024)
Shallow gas was widely recognized in the coastal region, especially in the estuarine delta areas with high organic matter (OM) burial flux. In this study, the vertical variations of shallow gas and the related geochemical indicators from two boreholes in the coastal region of the East China Sea (ECS) were investigated. Two gas-bearing layers were identified in the sediments from the Holocene and late Pleistocene series. Both boreholes exhibit a “typical” and an “inverse” Sulfate Methane Transition Zone (SMTZ). The “typical” SMTZs (SMTZ1 and SMTZ3) were in the upper part of the gas-bearing layers, where sulfate levels decrease and methane levels increase with depth. Conversely, the “inverse” SMTZs (SMTZ2 and SMTZ4) were in the lower part of the gas-bearing layers, exhibiting an increase in sulfate levels and a decrease in methane levels with depth, a phenomenon rarely documented in previous research. The downward variations of pore water geochemical characteristics indicates that these ions were related to Anaerobic Oxidation of Methane (AOM) processes. The increase in Ca 2+ and Ba 2+ concentrations and the gradual decrease in sulfate at the SMTZ reflect a series of biogeochemical processes resulting from the dissolution of carbonate and other minerals by AOM. The research indicates that sulfate in AOM may originate from multiple sources. Through analyzing the vertical distribution of shallow gas and the geochemical properties of pore water, this study elucidates the shallow gas formation mechanism and the features of the SMTZ, laying the groundwork for further investigations.

In situ hydrodynamic observations on three reef flats in the Nansha Islands, South China Sea - Jin Li; Ya Ping Wang; Shu Gao (Frontiers in Marine Science, 2024)
Waves and currents are responsible for sediment movement around and off coral reefs, affecting reef growth at both geological and modern timescales. Given the wide distribution and limited hydrodynamic information of reefs in the South China Sea, we carried out observations on tidal-cycle hydrodynamics in the Nansha Islands with tripod stationary instruments on the seafloor in order to fill the gap in our understanding of these processes. It was found that the magnitudes of near-bed orbital velocity were comparable with that of the mean tidal current, despite generally calm wave conditions. Waves dominated the combined wave-current skin-friction shear velocities acting on reef sediment, which were significantly higher than those generated by currents alone. Due to the large physical roughness of reef, drag coefficient and hydrodynamic roughness length estimated from logarithmic velocity profiles were two orders of magnitude higher than that in macro-tidal-estuary or inner shelf areas covered with siliceous muds or sands. The combined sinusoidal wave and asymmetric tidal current, along with the physical reef roughness, shaped velocity profile structures in the bottom boundary layer, which exhibited a logarithmic profile during the flood tide and a potential flow during the ebb. In absence of wave breaking, strong turbulence dissipation was observed across the rough reef, promoting strong mixing of water, which is crucial for delivering nutrients for coral growth. These findings imply the need to consider the unique characteristics of rough reef structure and combined effects of waves and currents to model the hydrodynamics in reef environment correctly. This understanding is critical for predicting energy and material transport in reef environments, which is essential for maintaining healthy coral ecosystems, and opens new paths for managing and preserving coral reefs in the face of environmental change.

Exploring the antiviral potential of paeonol from medicinal plants: A promising strategy for controlling white spot syndrome virus - Cheng Chen; Chang-Shuai Liang; Xiang-Yu Qu; Peng-Fei Li; Xiao-Ping Tan; Fei Ling; Gao-Xue Wang (Aquaculture, 2024)

Long-term cadmium exposure induces epithelial-mesenchymal transition in breast cancer cells by activating CYP1B1-mediated glutamine metabolic reprogramming in BT474 cells and MMTV-Erbb2 mice - Jingdian Li; Peng Gao; Mingke Qin; Junhua Wang; Yan Luo; Ping Deng; Rongrong Hao; Lei Zhang; Mindi He; Chunhai Chen; Yonghui Lu; Qinlong Ma; et al. (Science of The Total Environment, 2024)

Microbial colony sequencing combined with metabolomics revealed the effects of chronic hexavalent chromium and nickel combined exposure on intestinal inflammation in mice - Yueming Gu; Shuangyan Zheng; Cheng Huang; Xianhong Cao; Ping Liu; Yu Zhuang; Guyue Li; Guoliang Hu; Xiaona Gao; Xiaoquan Guo (Science of The Total Environment, 2024)

Impact of microplastics on nicosulfuron accumulation and bacteria community in soil-earthworms system - Qingchuan Gao; Xiaohui Lu; Jinfeng Li; Ping Wang; Ming Li (Journal of Hazardous Materials, 2024)

Response of mangrove development to paleoclimate variation over the past 3,550 years in Phang Nga Province, Thailand - Yuanqin Xu; Ping Li; Jie Liu; Yao Zhang; Somkiat Khokiattiwong; Narumol Kornkanitnan; Wei Gao (Journal of Asian Earth Sciences, 2024)

Comparative study of volatile flavor compounds in green onion (Allium fistulosum L.) processed with different cooking methods - Jicai Bi; Bian Li; Zhuo Chen; Zhen Yang; Chunyuan Ping; Yueyue Gao; Yao Zhang; Lingwen Zhang (International Journal of Gastronomy and Food Science, 2024)

Deep plowing increases soil water storage and wheat yield in a semiarid region of Loess Plateau in China: A simulation study - Xinrui Shi; Chao Li; Ping Li; Yuzheng Zong; Dongsheng Zhang; Zhiqiang Gao; Xingyu Hao; Jing Wang; Shu Kee Lam (Field Crops Research, 2024)

Methyl jasmonate regulation of pectin polysaccharides in Cosmos bipinnatus roots: A mechanistic insight into alleviating cadmium toxicity - Chun-Yu Fan; Xiao-Fang Yu; Yu-Jia Liu; Xiao-Xuan Zeng; Fu-Wen Luo; Xian-Tong Wang; Xuan Yang; Xiao-Yu Wang; Xiao Xue; Li-Juan Yang; Ting Lei; Ming-Yan Jiang; et al. (Environmental Pollution, 2024)

Evolution of suspended sediment concentration profiles in the partially and periodically stratified Changjiang Estuary during dry season - Zhanhai Li; Jianjun Jia; Fan Zhang; Ya Ping Wang; Shu Gao (Estuarine, Coastal and Shelf Science, 2024)

Charge-reversal biodegradable nanoplatform with ferroptosis and ICD induction for tumor synergistic treatment - Ping Sun; Li Huang; Zimu Li; Yao Yang; Shiman Lu; Nansha Gao; Hongzhong Chen; Xiaowei Zeng; Zhongjian Xie (Chemical Engineering Journal, 2024)

Effects of Fractionation Methods on Soil Aggregate Microbial Community Composition: Settling vs. Wet Sieving - Xin Gao; Rui Wang; Yaxian Hu; Weijia Li; Lanlan Du; Shengli Guo; Shengjun Wu; Ping Huang (Journal of Soil Science and Plant Nutrition, 2024)

Long-term Fertilizer Application Induces Changes in Carbon Storage and Distribution, and the Consequent Color of Black soil - Jichao Gao; Lichun Wang; Jiafa Luo; Hongjun Gao; Weiwen Qiu; Qiang Li; Xiuzhi Zhang; Ping Zhu; Chang Peng; Yunfei Jiao; Lingying Xu (Journal of Soil Science and Plant Nutrition, 2024)

Dissection and validation of quantitative trait loci (QTLs) conferring grain size and grain weight in rice - Ping Sun; Yuanyuan Zheng; Pingbo Li; Hong Ye; Hao Zhou; Guanjun Gao; Qinglu Zhang; Yuqing He (Euphytica, 2024)

Brittleness ductility transition depth of new fracture in the Baodi Miaozhuang Uplift - He Li; Yi-Bing Dong; Yi-Xi Wang; Wu-Ping Gao; Cheng-Guo Yan; Ling-Ling Cai; Bo-Yang Wu; Peng Zhao (Applied Geophysics, 2024)

Quercetin stimulates an accelerated burst of oviposition-based reproductive strategy in codling moth controlled by juvenile hormone signaling pathway - Bing Bai; Shi-Pan Zhang; Yu-Ting Li; Ping Gao; Xue-Qing Yang (Science of The Total Environment, 2024)

Effects of nitrogen supply on hydrogen-oxidizing bacterial enrichment to produce microbial protein: Comparing nitrogen fixation and ammonium assimilation - Haoran Wang; Lixia Zhang; Chang Tian; Sen Fan; Decong Zheng; Yuhan Song; Ping Gao; Daping Li (Bioresource Technology, 2024)

Phycoremediation and valorization of hypersaline pickled mustard wastewater via Chaetoceros muelleri and indigenous bacteria - Kai Zhang; Shuqin Jiang; Juan Zhang; Jishu Zheng; Ping Li; Song Wang; Ru Bi; Lihong Gao (Bioresource Technology, 2024)

Human Bone Marrow Derived-Mesenchymal Stem Cells Treatment for Autoimmune Premature Ovarian Insufficiency - Wen-Qing Ma; Ai-Ping Zhuo; Yuan-Ling Xiao; Meng Gao; Yu-Tao Yang; Li-Chao Tang; Yan-Hong Wu; Dan Tian; Xia-Fei Fu (Stem Cell Reviews and Reports, 2024)

Histone methyltransferase KMT2D inhibits ENKTL carcinogenesis by epigenetically activating SGK1 and SOCS1 - Yue-Hua Zhang; Qing Tao; Wen-Yan Zhang; Sha Zhao; Wei-Ping Liu; Li-Min Gao (Genes & Genomics, 2024)

Effects of different ratios of organic and inorganic fertilizer on rice yield and soil physicochemical properties under conventional and controlled irrigation conditions - Yuanyuan Li; Ping He; Shah Jahan Leghari; Yanbin Li; Shikai Gao; Daoxi Li (Irrigation and Drainage, 2024)
Water and fertilizer management practices are critical in rice fields. Excessive application of fertilizer adversely affects soil physicochemical properties, consequently decreasing yield. A greenhouse experiment was conducted to determine the effect of high (L1), medium (L2) and low organic fertilizer ratios (L3) as well as chemical fertilizer alone (L4) and no fertilization (L5) under conventional (C) and controlled irrigation (M) on rice yield and soil characteristics. Statistically, the regression equation was developed by using principal component analysis to clarify the influence of different soil quality factors on rice yield. The results showed that controlled irrigation could increase soil temperature (ST), electrical conductivity (EC) and nitrogen content while decreasing soil pH. The application of organic fertilizer enhanced ST and decreased EC. Under equal nitrogen application conditions, rice yield increased with organic fertilizer application, and it was highest under L1, which was 2.7% higher than L4 and 22% higher than L5. In the case of irrigation methods, controlled irrigation application increased yield by 6% compared to conventional irrigation. The multiple linear regression equation showed that the cumulative contribution of variance of the two principal component eigenvalues reached 75%, among which soil pH, total nitrogen (TN) content and nitrate nitrogen (NO 3 − ‐N) contributed positively to yield, while ammonium nitrogen (NH 4 + ‐N), soil organic carbon (SOC), EC and ST showed negative effects on rice yield. Thus, our study findings can provide a scientific basis for improving management practices.

Metazoan diversity and community assemblages in sediments across a Western Pacific Trench-Arc-Basin system: insights from eDNA metabarcoding - Jing Mo; Xinlong Li; Anning Mou; Ping Gao; Xuetao Wang; Xuelei Zhang; Qinzeng Xu (Frontiers in Marine Science, 2024)
Trench-arc-basin (TAB) systems are widely distributed in the deep sea, yet our understanding of their biodiversity patterns and community assemblages remains limited. In this study, we collected sediment samples from 22 stations across a Western Pacific TAB system and identified 85 families of marine benthos from 15 phyla by using eDNA metabarcoding with the 18S rRNA gene V4 region. Nematodes were the most dominant metazoan taxa followed by echinoderms, arthropods, and annelids. The highest biodiversity and species specificity were observed at stations located near seamounts. The community assemblages were highly heterogeneous in this TAB system, likely induced by the large geographic barriers and the high habitat heterogeneity. Furthermore, the total organic carbon content and median grain size of the sediment drive the overall community composition, and the water depth exerts a significant influence on species richness and abundance. Our results provide insight into benthos diversity and distribution across a TAB system and data for further comparisons and modeling studies.

Multiomics analyses of two Leonurus species illuminate leonurine biosynthesis and its evolution - Peng Li; Meng-Xiao Yan; Pan Liu; Dan-Jie Yang; Ze-Kun He; Yun Gao; Yan Jiang; Yu Kong; Xin Zhong; Sheng Wu; Jun Yang; Hong-Xia Wang; et al. (Molecular Plant, 2024)

A new snow depth retrieval method by improved hybrid DEM differencing and coherence amplitude algorithm for PolInSAR - Haiwei Qiao; Ping Zhang; Zhen Li; Lei Huang; Shuo Gao; Chang Liu; Zhipeng Wu; Shuang Liang; Jianmin Zhou; Wei Sun; Jian Wang (Journal of Hydrology, 2024)

Flexible catabolism of monoaromatic hydrocarbons by anaerobic microbiota adapting to oxygen exposure - Zhiming Wu; Xin Yu; Yanhan Ji; Guiping Liu; Ping Gao; Lei Xia; Pengfa Li; Bin Liang; Shiri Freilich; Lifeng Gu; Wenjing Qiao; Jiandong Jiang (Journal of Hazardous Materials, 2024)

Evolution of sandy shores under the combined impact of global climate change and anthropogenic activities in Shandong Peninsula, East China - Wei Gao; Jie Liu; Yuanqin Xu; Ping Li (Journal of Asian Earth Sciences, 2024)

Variable depositional environments and organic matter enrichment of Early Cambrian shales in the Middle Yangtze region, South China - Wei Liu; Ping Gao; Xianming Xiao; Yanming Zhao; Yijie Xing; Jinku Li (Journal of Asian Earth Sciences, 2024)

Exploring the formation and retention of aroma compounds in ready-to-eat roasted pork from four thermal methods: A lipidomics and heat transfer analysis - Huan Liu; Qianli Ma; Jiangtao Xing; Pi Li; Peng Gao; Nazimah Hamid; Zhongshuai Wang; Ping Wang; Hansheng Gong (Food Chemistry, 2024)

Technological diversity in the tropical-subtropical zone of Southwest China during the terminal Pleistocene: excavations at Fodongdi Cave - Fa-Xiang Huan; Shi-Xia Yang; Feng Gao; Xin-Ying Zhou; Jian-Ping Yue; Yu-Xiu Zhang; Jin-Xu Wu; Qi-Jun Ruan; Kai-Wei Qiu; Jing-wen Xu; Nai-Ru Lin; Yi-Ren Wang; et al. (Archaeological and Anthropological Sciences, 2024)

The effects of Spinosad on zebrafish larvae and THP-1 cells: Associated with immune cell damage and NF-kappa B signaling pathway activation - Wei-Guo Wang; Shou-Qian Xiong; Jin Lu; Lian-Hua Zhu; Cheng Zhang; Jia-Gao Cheng; Zhong Li; Wen-Ping Xu; Li-Ming Tao; Yang Zhang (Chemosphere, 2023)

Chronic cadmium exposure triggered ferroptosis by perturbing the STEAP3-mediated glutathione redox balance linked to altered metabolomic signatures in humans - Ping Deng; Jingdian Li; Yonghui Lu; Rongrong Hao; Mindi He; Min Li; Miduo Tan; Peng Gao; Liting Wang; Huihui Hong; Jiawen Tao; Muxue Lu; et al. (Science of The Total Environment, 2023)

Sediment depth-related variations of comammox Nitrospira: Evidence in the Three Gorges Reservoir, China - Baohong Yu; Quanchao Zeng; Jinlin Li; Jun Li; Xun Tan; Xin Gao; Ziqiang Mao; Ping Huang; Shengjun Wu (Science of The Total Environment, 2023)

Ascendancy of pyraclostrobin nanocapsule formulation against Rhizoctonia solani: From a perspective of fungus - Li Ma; Meng Yu; Yingjian Ma; Linying Gao; Shouhe Pan; Xuefeng Li; Xuemin Wu; Yong Xu; Sen Pang; Ping Wang (Pesticide Biochemistry and Physiology, 2023)

Beyond filterability: Understanding the complexities of sludge dewatering through typical coagulation and advanced oxidation - Wen-Hui Liu; Hao Zhang; Ya-Li Zhang; Ping Sun; Yuan-Ping Zeng; Yun-Yan Gao; Hou-Feng Wang; Raymond Jianxiong Zeng (Journal of Cleaner Production, 2023)

A Strategy for Reducing Nitrogen Fertilizer Application Based on Application of Biochar: A Case in Northeast China Black Soil Region (Mollisols) - Qinglin Li; Qiang Fu; Tianxiao Li; Renjie Hou; Shuqi Dong; Ping Xue; Xuechen Yang; Yu Gao (Journal of Soil Science and Plant Nutrition, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Role of APR3 in cancer: apoptosis, autophagy, oxidative stress, and cancer therapy - Ping Zhang; Chaoting Zhou; Qiangan Jing; Yan Gao; Lei Yang; Yanchun Li; Jing Du; Xiangmin Tong; Ying Wang (Apoptosis, 2023)

Establishment and characterization of a novel hilar cholangiocarcinoma cell line, CBC3T-1 - Mingzhen Bai; Ningzu Jiang; Wenkang Fu; Chongfei Huang; Liang Tian; Ningning Mi; Long Gao; Haidong Ma; Yawen Lu; Jie Cao; Chao Zhang; Ping Yue; et al. (Human Cell, 2023)
Cholangiocarcinoma (CCA) is a group of malignant heterogeneous cancer arising from the biliary tree. The tumor is characterized by insidious onset, high degree of malignancy, poor prognosis, and high recurrence rate. Immortalized cancer cell lines are the best and easiest models for in vitro cancer research. Here, we established a naturally immortalized highly tumorigenic hilar cholangiocarcinoma (hCCA) cell line, CBC3T-1. The CBC3T-1 cell line was cultured for over 60 passages. Thorough analysis showed that CBC3T-1 cells share characteristics similar to original tumor cells from patients with cholangiocarcinoma and display a stable phenotype, including features of epithelial origin, stem cell-like properties, as well as a high invasive and migratory capability and tumorigenicity in mice. Furthermore, this cell line showed the best sensitivity to paclitaxel, followed by gemcitabine. RNA sequencing and whole‑exome sequencing showed that cancer-associated pathways and somatic mutations played a dominant role in the development of CCA. We established and characterized a new hCCA cell line, CBC3T-1, which contributes to a better understanding of bile duct cancer, and can be used to study tumorigenesis and progression and the role of anticancer drugs.

Factors affecting the accumulation of organotins by wild fish: A case study in the Three Gorges Reservoir, China - Jun-min Gao; Jia You; Jing-cheng Wu; Jin-song Guo; Ping-ting Fu; Li-xia Zhang (Environmental Science and Pollution Research, 2023)

Baicalin mitigates nephropathogenic infectious bronchitis virus infection-induced spleen injury via modulation of mitophagy and macrophage polarization in Hy-Line chick - Guanming Tian; Cheng Huang; Zhengqing Li; Zhihua Lu; Chenlu Feng; Yu Zhuang; Guyue Li; Ping Liu; Guoliang Hu; Xiaona Gao; Xiaoquan Guo (Veterinary Microbiology, 2023)

Extraction and characterization of anti-virus anthraquinones from Nicotiana tabacum-derived Aspergillus oryzae YNCA1220 - Feng-Xian Yang; Yue-Yu Ma; Yu-Ping Wu; Gao-Kun Zhao; Yong-Ping Li; Zhen-Jie Li; Xue-Mei Li; Yin-Ke Li; Wei-Guang Wang; Min Zhou; Guang-Hui Kong; Qiu-Fen Hu (Pesticide Biochemistry and Physiology, 2023)

Enhancing catalytic hydrolysis activity of ZnNiAl hydrotalcite-like compounds-derived oxides using rare earth metals - Kunlin Li; Yu Tian; Xie Tang; Peng Gao; Xiao Peng; Ping Ning; Chi Wang; Fei Wang; Xin Sun; Kai Li (Journal of Cleaner Production, 2023)

Enhancing data reliability in quantitative characterization of moisture distribution in sludge using DSC: Impact of sample attributes and test parameters - Ya-Li Zhang; Hao Zhang; Wen-Hui Liu; Ping Sun; Shao-Ming Zheng; Yun-Yan Gao; Yuan-Ping Zeng; Hou-Feng Wang; Raymond Jianxiong Zeng (Journal of Environmental Management, 2023)

Treating waste with waste: Facile KHCO3-modified calcium carbide slag for simultaneous removal of NO and SO2 - Fang Wang; Hui Li; Jiyun Gao; Chenhui Liu; Lijuan Jia; Jiayu Feng; Ping Ning (Fuel, 2023)

Understanding the role of lipids in aroma formation of circulating non-fried roasted chicken using UHPLC-HRMS-based lipidomics and heat transfer analysis - Huan Liu; Dengyong Liu; Raheel Suleman; Peng Gao; Pi Li; Jiangtao Xing; Qianli Ma; Nazimah Hamid; Ping Wang; Hansheng Gong (Food Research International, 2023)

Genetic variations of CYP3A4 on the metabolism of itraconazole in vitro - Sai-li Xie; Xiayan Zhu; Nanyong Gao; Qianmeng Lin; Chaojie Chen; Yun-jun Yang; Jian-ping Cai; Guo-xin Hu; Ren-ai Xu (Food and Chemical Toxicology, 2023)

Vertical variation in prokaryotic community composition and co-occurrence patterns in sediments of the Three Gorges Reservoir, China - Baohong Yu; Quanchao Zeng; Jinlin Li; Jun Li; Xun Tan; Xin Gao; Ping Huang; Shengjun Wu (Environmental Research, 2023)

Uniform lithium deposition regulated by lithiophilic Mo3N2/MoN heterojunction nanobelts interlayer for stable lithium metal batteries - Xiaojuan Zhang; Liang Zhou; Kunpeng Hu; Dandan Gao; Shuo Tang; Li He; Yuanfu Chen; Ping Zhang; Zhigang Zhang (Chemical Engineering Journal, 2023)

The effects of boundary layer vertical turbulent diffusivity on the tropical cyclone intensity - Lei Ye; Yubin Li; Ping Zhu; Zhiqiu Gao (Atmospheric Research, 2023)

Spatial differentiation and dynamic mechanism of micro-geomorphology based on acoustic spectrum data of the Huanghe (Yellow) River Delta - Ping Li; Yongde Jin; Wei Gao; Xiaolong Zhao (Journal of Oceanology and Limnology, 2023)

Bi0·5Na0·5TiO3/ZnO Z-scheme heterojunction for piezo-photocatalytic water remediation: Mechanical energy harvesting and energy band configuration - Peng Wang; Wanqian Cai; Fangyuan Yu; Ping Zhou; Mei Lin; Cong Lin; Tengfei Lin; Min Gao; Chunlin Zhao; Xiangqi Li; Xiao Wu (Chemosphere, 2023)

Systematic evaluation of ramie (Boehmeria nivea L.) for phytoremediation of cadmium contaminated soil and the mechanism of microbial regulation - Kunmei Chen; Yulan Li; Chunming Yu; Ping Chen; Jikang Chen; Gang Gao; Xiaofei Wang; Heping Xiong; Aiguo Zhu (Chemosphere, 2023)

Quartz types and origins of the Upper Permian Dalong Formation shale of the Sichuan Basin: Implications for pore preservation in deep shale reservoirs - Ping Gao; Xianming Xiao; Guangming Meng; Gary G. Lash; Shuangjian Li; Yueqing Han (Marine and Petroleum Geology, 2023)

Theoretical study of H-abstraction reactions of di-n-propyl ether oxidation by H, CH3, HO2 and OH radicals - Mengjiao Gao; Jiuning He; Shunping Shi; Xuefeng Liu; Yanhao Duan; Lei Chen; Changhua Zhang; Ping Li; Deliang Chen (Fuel, 2023)

The chemistry and activity-orientedcharacterization of isoflavones difference between roots of Pueraria lobata and P. thomsonii guided by feature-based molecular networking - Ye Zhang; Dong Xu; Xue Xing; Hua Yang; Wen Gao; Ping Li (Food Chemistry, 2023)

Nitrogen removal performances and metabolic mechanisms of denitrification systems using different volatile fatty acids as external carbon sources - Xin Li; Xiangzhen Li; Chaonan Li; Na Li; Ping Zou; Xiaolong Gao; Qin Cao (Chemical Engineering Journal, 2023)

Near-infrared-triggered chirality-dependent photodynamic therapy based on hybrid upconversion nanoparticle hydrogels - Tianyong Guan; Yan Liu; Jiayao Li; Mingmao Chen; Xiaoying Shang; Ping Hu; Renfu Li; Hang Gao; Datao Tu; Wei Zheng; Xueyuan Chen (Chemical Engineering Journal, 2023)

Land-Use Change and Driving Force Analysis of Wetland in Poyang Lake Based on Remote Sensing - Zhili Xu; Bin Dong; Xiang Gao; Ping Wang; Chunqiu Ren; Sheng Li; Haifeng Xu; Fang Lei; Zezhu Wei; Zhipeng Lu; Xiao Liu (Journal of the Indian Society of Remote Sensing, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Effects of insulin-like growth factor 1, leukemia inhibitory factor, and basic fibroblast growth factor on goat oocyte maturation and early embryonic development in vitro - Zhao Gao-Ping; Shi Pei-Xin; Chang Qing; Wang Zi-Xin; Li Yun-Xia; Zhao Li-Xia; Sun Wei; Wu Meng; Bao Si-Qin; Cao Gui-Fang; Li Xi-He (Small Ruminant Research, 2023)

A novel global snow depth retrieval method considering snow metamorphism and forest influence - Shuo Gao; Zhen Li; Ping Zhang; Quan Chen; Lei Huang; Jianmin Zhou; Changjun Zhao; Haiwei Qiao; Zhaojun Zheng (Remote Sensing of Environment, 2023)

Remobilization characteristics and diffusion kinetic processes of sediment zinc (Zn) in a tidal reach of the Pearl River Estuary, South China - Lei Gao; Rui Li; Zuobing Liang; Chenchen Yang; Zaizhi Yang; Lei Hou; Lei Ouyang; Xiuhua Zhao; Jianyao Chen; Ping Zhao (Journal of Hazardous Materials, 2023)

Hierarchical microsphere Flower-like SnIn4S8 with active sulfur sites for adsorption and removal of mercury from coal-fired flue gas - Yuanqin Xue; Xu Fang; Haoyu Jiang; Jiang Wu; Hailong Liu; Xin Li; Ping He; Fangqin Li; Yongfeng Qi; Qihang Gao; Yilin Fan (Chemical Engineering Journal, 2023)

Energy savings and thermal comfort in a zero energy office building with fans in Singapore - Michael G. Kent; Nam Khoa Huynh; Asit Kumar Mishra; Federico Tartarini; Aleksandra Lipczynska; Jiayu Li; Zurami Sultan; Edwin Goh; Giridharan Karunagaran; Arulmani Natarajan; Asiri Indrajith; Ivanna Hendri; et al. (Building and Environment, 2023)

Nitidine chloride regulates cell function of bladder cancer in vitro through downregulating Lymphocyte antigen 75 - Shi-shuo Wang; Gao-qiang Zhai; Zhi-guang Huang; Jia-yuan Luo; Juan He; Jie-zhuang Huang; Ling Yang; Chu-nan Xiao; Su-li Li; Kai-rong Chen; Yan-yu Chen; Han-chu Ji; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Schizophrenia in the genetic era: a review from development history, clinical features and genomic research approaches to insights of susceptibility genes - Ye Lv; Lin Wen; Wen-Juan Hu; Chong Deng; Hui-Wen Ren; Ya-Nan Bao; Bo-Wei Su; Ping Gao; Zi-Yue Man; Yi-Yang Luo; Cheng-Jie Li; Zhi-Xin Xiang; et al. (Metabolic Brain Disease, 2023)

Identification of new conserved linear B-cell epitopes in the 3AB and 3C protein of Senecavirus A - Jian Li; Junfang Yan; Yanni Gao; Xing Liu; Haifeng Sun; Juan Bai; Ping Jiang (Veterinary Microbiology, 2023)

UGT2B13 and UGT2C1 are involved in lambda-cyhalothrin resistance in Rhopalosiphum padi - Suji Wang; Xi Liu; Hongcheng Tang; Mengtian Li; Ping Gao; Xiong Peng; Maohua Chen (Pesticide Biochemistry and Physiology, 2023)

Acute and chronic effects of sublethal neonicotinoid thiacloprid to Asian honey bee (Apis cerana cerana) - Min Shi; Yi Guo; Yan-Yan Wu; Ping-Li Dai; Shao-Jun Dai; Qing-Yun Diao; Jing Gao (Pesticide Biochemistry and Physiology, 2023)

Temperate phage influence virulence and biofilm-forming of Salmonella Typhimurium and enhance the ability to contaminate food product - Shuang Wang; Seyyed Danial Mirmiran; Xiangmin Li; Xinxin Li; Fenqiang Zhang; Xiaochao Duan; Dongyang Gao; Yibao Chen; Huanchun Chen; Ping Qian (International Journal of Food Microbiology, 2023)

Preparation of carbon foam from depolymerization-reforming lignin for capacitive deionization - Chun-Ping Li; Ya-Qi Wu; Jia-Jia An; Li-Xin Gao; Da-Quan Zhang; Jin Li; Zhong-Xun An (Desalination, 2023)

Porphyrin-based donor with asymmetric ending groups enables 16.31% efficiency for ternary all-small-molecule organic solar cells - Haojiang Shen; Yixuan Xu; Wentao Zou; Wenqing Zhang; Jianfeng Li; Ping Cai; Yuan Guo; Huajun Xu; Xiaotao Hao; Yanna Sun; Yuanyuan Kan; Yingguo Yang; et al. (Chemical Engineering Journal, 2023)

Naturally and chemically acetylated polysaccharides: Structural characteristics, synthesis, activities, and applications in the delivery system: A review - Hongyu Li; Yingping Wang; Ping Zhao; Lanping Guo; Luqi Huang; Xia Li; Wenyuan Gao (Carbohydrate Polymers, 2023)

Irisin Attenuates Apoptosis Following Ischemia–Reperfusion Injury Through Improved Mitochondria Dynamics and ROS Suppression Mediated Through the PI3K/Akt/mTOR Axis - Ji-fei Liu; Gang Su; Li-xia Chen; Juan-ping Zhou; Juan Gao; Jia-jia Zhang; Qiong-hui Wu; Wei Chen; De-yi Chen; Zhen-chang Zhang (Molecular Neurobiology, 2023)

Constructed a self-powered sensing platform based on nitrogen-doped hollow carbon nanospheres for ultra-sensitive detection and real-time tracking of double markers - Yong-ping Gao; Ke-jing Huang; Bo-ya Wang; Qianyue Xu; Honglei Shuai; Guoqiang Li (Analytica Chimica Acta, 2023)

Exploring the migration and transformation behaviors of heavy metals and ammonia nitrogen from electrolytic manganese residue to agricultural soils through column leaching test - Xianwei Zhang; Ping Wang; Jiangshan Li; Yonghong Gao; Shiyu Liu; Saiou Fu; Chikezie Chimere Onyekwena; Xuewen Lei (Environmental Science and Pollution Research, 2023)

Determinants affecting the blood mercury levels of preschool children in Shanghai, China: A cross-sectional study - Xi Xu; Yu-Qing Wang; Chen-Yin Dong; Chun-Ping Hu; Li-Na Zhang; Zhen-Yan Gao; Min-Ming Li; Su-Su Wang; Chong-Huai Yan (Environmental Science and Pollution Research, 2023)

A comprehensive SERS, SEM and EDX study of individual atmospheric PM2.5 particles in Chengdu, China - Dongxian Li; Weisheng Yue; Tiancheng Gong; Ping Gao; Tao Zhang; Yunfei Luo; Changtao Wang (Science of The Total Environment, 2023)

Sinomenine ameliorates rheumatoid arthritis by modulating tryptophan metabolism and activating aryl hydrocarbon receptor via gut microbiota regulation - Zheng-Meng Jiang; Su-Ling Zeng; Tian-Qing Huang; Yang Lin; Fang-Fang Wang; Xing-Jiao Gao; Jing Li; Ping Li; E-Hu Liu (Science Bulletin, 2023)

Response spectra for transient pore-pressure in a sandy seabed under random waves: Frequency-filtering effect - Jia-Hao Yu; Fu-Ping Gao; Chang-Fei Li (Ocean Engineering, 2023)

Ultra-stable, sensitive and broadband photodetector based on large-area 2D bismuth oxyselenide film for multiband image sensing - Shuai Ren; Shiyong Gao; Ping Rong; Lin Li; Mingyi Zhang; Huiqing Lu; Jun Yan; Duoduo Ling; Shujie Jiao; Jinzhong Wang (Chemical Engineering Journal, 2023)

Saltwater incursion regulates N2O emission pathways and potential nitrification and denitrification in intertidal wetland - Yinghui Jiang; Guoyu Yin; Ye Li; Lijun Hou; Min Liu; Cheng Chen; Dongsheng Zheng; Han Wu; Dengzhou Gao; Yanling Zheng; Ping Han (Biology and Fertility of Soils, 2023)

Fluorescence Properties and Chemical Composition of Fine Particles in the Background Atmosphere of North China - Ping Li; Siyao Yue; Xiaoyang Yang; Di Liu; Qiang Zhang; Wei Hu; Shengjie Hou; Wanyu Zhao; Hong Ren; Gang Li; Yuanguan Gao; Junjun Deng; et al. (Advances in Atmospheric Sciences, 2023)

Daphnia magna uptake and excretion of luminescence‐labelled polystyrene nanoparticle as visualized by high sensitivity real-time optical imaging - Yu-Hang Zhang; Rong-Yao Gao; Ze-Jun Wang; Qian-Qian Shao; Ya-Wen Hu; Hua-Bing Jia; Xiao-Jing Liu; Feng-Qin Dong; Li-Min Fu; Jian-Ping Zhang (Chemosphere, 2023)

TRIM7 inhibits encephalomyocarditis virus replication by activating interferon-β signaling pathway - Minjing Li; Junfang Yan; Huixin Zhu; Chengyi Guo; Xiaolin Jiang; Yanni Gao; Xing Liu; Ping Jiang; Juan Bai (Veterinary Microbiology, 2023)

SOV sensitizes gastric cancer cells to radiation by suppressing radiation-induced autophagy in vitro and in vivo - Wen Wang; Xiao-gan Jiang; Ya-ping Bai; Heng Li; Ling-xi Gao; Teng Zhang; Fang-yi Dong; Wen-ping Ding; Yan Zhang (Tissue and Cell, 2023)

Transcriptomic and physiological analysis of the effect of octanoic acid on Meloidogyne incognita - Jian-Yu Wang; Qiu-Yue Li; Li Ren; Cheng Guo; Jian-Ping Qu; Zheng Gao; Hui-Fang Wang; Qian Zhang; Bo Zhou (Pesticide Biochemistry and Physiology, 2023)

Assessment of agricultural water resources carrying capacity and analysis of its spatio-temporal variation in Henan Province, China - Youming Zhang; Yun Gao; Yan Zhang; Zhijie Liang; Zulin Zhang; Yulong Zhao; Ping Li (Journal of Cleaner Production, 2023)

Mining of kokumi peptides in chicken broth with peptidomics - Yang Li; Jicai Bi; Zeyuan Lin; Zhen Yang; Yueyue Gao; Chunyuan Ping; Zhuo Chen (International Journal of Gastronomy and Food Science, 2023)

Stellate ganglion block suppresses hippocampal ferroptosis to attenuate cerebral ischemia-reperfusion injury via the Hippo pathway - Chunwang Zhou; Mengyuan Li; Yingxin Chu; Liyan Zheng; Shubo Zhang; Xiujiang Gao; Ping Gao (Metabolic Brain Disease, 2023)

Southern Ocean warming and its climatic impacts - Wenju Cai; Libao Gao; Yiyong Luo; Xichen Li; Xiaotong Zheng; Xuebin Zhang; Xuhua Cheng; Fan Jia; Ariaan Purich; Agus Santoso; Yan Du; David M. Holland; et al. (Science Bulletin, 2023)

Chemosensory proteins are associated with thiamethoxam tolerance in bird cherry-oat aphid Rhopalosiphum padi - Ping Gao; Siqian Zhang; Junjie Tan; Xinghao Li; Maohua Chen (Pesticide Biochemistry and Physiology, 2023)

Low-dose ionizing radiation: Effects on the proliferation and migration of lens epithelial cells via activation of the Wnt/β-catenin pathway - Ping Wang; Yu-Wen Li; Xue Lu; Ya Liu; Xue-Lei Tian; Ling Gao; Qing-Jie Liu; Li Fan; Mei Tian (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2023)

Restoration of sedimentary environment and geochemical features of deep marine Longmaxi shale and its significance for shale gas: A case study of the Dingshan area in the Sichuan Basin, South China - Yue Feng; Xianming Xiao; Ping Gao; Enze Wang; Dongfeng Hu; Ruobing Liu; Gang Li; Chengang Lu (Marine and Petroleum Geology, 2023)

Assessing the algal population dynamics using multiple machine learning approaches: Application to Macao reservoirs - Zhejun Li; Sin Neng Chio; Liang Gao; Ping Zhang (Journal of Environmental Management, 2023)

Melatonin inhibits senescence-associated melanin pigmentation through the p53-TYR pathway in human primary melanocytes and the skin of C57BL/6 J mice after UVB irradiation - Li-Ping Ma; Meng-Meng Liu; Fang Liu; Bo Sun; Si-Nian Wang; Jie Chen; Hui-Jie Yu; Juan Yan; Mei Tian; Ling Gao; Qing-Jie Liu (Journal of Molecular Medicine, 2023)
UVB exposure accelerates skin aging and pigmentation. Melatonin effectively regulates tyrosinase (TYR) activity and aging. The purpose of this study was to determine the association between premature senescence and pigmentation, and the mechanism of melanin synthesis effected by melatonin. Primary melanocytes were extracted and identified from the male foreskin. To inhibit TYR expression, primary melanocytes were transduced with the lentivirus pLKD-CMV-EGFP-2A-Puro-U6-TYR. The wild-type TYR ( + / + ) and TYR (–/–) or TYR ( + /–) knockout C57BL/6 J mice were used to determine the role of TYR on melanin synthesis in vivo. Results showed that UVB-induced melanin synthesis is dependent on TYR in primary melanocytes and mice. Furthermore, in primary melanocytes pretreated with Nutlin-3 or PFT-α to up or downregulate p53, results showed that premature senescence and melanin synthesis increased in primary melanocytes after UVB irradiation at 80 mJ/cm 2 , and further increased after being treated with Nutlin-3, while significantly decreased with PFT-α. In addition, melatonin inhibited UVB-induced premature senescence associated with inactivation of p53 and phosphorylation of p53 on Ser15 (ser-15), a decrease of melanin synthesis accompanied by reduced TYR expression. Moreover, skin erythema and pigmentation induced by UVB were reduced in the dorsal and ear skin of mice topically pretreated with 2.5% melatonin. These indicate that melatonin inhibits UVB-induced senescence-associated pigmentation via the p53-TYR pathway in primary melanocytes and prevents pigmentation obviously in the dorsal and ear skin of C57BL/6 J mice after UVB irradiation. Key messages P53 links UVB irradiation-induced senescence and senescence-associated pigmentation and regulates TYR in primary melanocytes after UVB irradiation. Melatonin inhibits senescence-associated pigmentation through the p53-TYR pathway in primary melanocytes. Melatonin prevents skin erythema and melanin pigmentation induced by UVB irradiation in the dorsal and ear skin of C57BL/6J mice.

Association between the NEP rs701109 polymorphism and the clinical efficacy and safety of sacubitril/valsartan in Chinese patients with heart failure - Hong-Yu Luo; Li-Chen Gao; Hui-Zhi Long; Zi-Wei Zhou; Shuo-Guo Xu; Feng-Jiao Li; Hong-Li Li; Yan Cheng; Cai-Xia Li; Xing-Yu Peng; Liang Li; Ran Chen; et al. (European Journal of Clinical Pharmacology, 2023)

Survival, Energy Status, and Cellular Stress Responses of the Juvenile Swimming Crab Portunus trituberculatus under Acute Nitrite Stress - Xiaochen Liu; Daixia Wang; Yan Shang; Xuee Yu; Baoquan Gao; Jianjian Lv; Jitao Li; Ping Liu; Jian Li; Xianliang Meng (Fishes, 2023)
Nitrite is a common pollutant encountered in aquaculture systems. During intensive hatchery, accumulation of nitrite can cause massive mortality of juvenile crustaceans. However, the nitrite toxicity and cellular stress responses in juvenile crustaceans is not clearly understood. Here, we investigate the survival, energy metabolism, and cellular stress responses in juvenile P. trituberculatus, an important aquaculture species in China, under acute nitrite stress. The results revealed nitrite resulted in a significant decrease in survival rate of juvenile swimming crab. After nitrite exposure, the activity of catabolic enzymes, such as HK, PK, CS, and CPT-1, were initially enhanced, and then they showed significant decrease at the late stage of exposure, accompanied by reduction in ATP and adenylate energy charge (AEC). The impaired energy homeostasis was possibly associated with disturbed AMPK signaling and enhanced anaerobic metabolism, which was indicated by the high levels of LDH activity and HIF-1α expression. Furthermore, we found that nitrite stress can depress antioxidant systems and unfold protein responses, causing oxidative damage and endoplasmic reticulum (ER) stress, and this, in turn, can trigger autophagy and apoptosis through both caspase-dependent and caspase-independent pathways. The results of the present study improve our understanding regarding adverse effects of nitrite on P. trituberculatus and provide valuable information for hatchery management.

Metabonomic Analysis of Macrobrachium rosenbergii with Iron Prawn Syndrome (IPS) - Xi-Lian Li; Pei-Jing Shen; Wen-Ping Jiang; Ji-Lun Meng; Hai-Hua Cheng; Qiang Gao (Fishes, 2023)
We previously reported on the comparison of proteomic data between seven tissue types of a novel “iron prawn” species. However, no transcripts or metabolic information are available for this species. We therefore performed shotgun LC–MS/MS metabonomic and RNA-seq analyses of the total protein from “iron prawns”. KEGG analysis revealed that the largest group consisted of a total of 114 KEGG pathway proteins, comparing the “iron prawns” with the normal prawns. A total of 423 peptides, corresponding to metabolic pathways, ABC transporters, starch and sucrose metabolism, insulin resistance/secretion, fatty digestion and absorption, and lipid metabolism, were identified. The pathways of carbohydrate and amino acid metabolism decreased in female iron prawns, while organic acid and its derivatives increased. However, the pathway of organic acid and its derivatives decreased and lipid metabolism increased in the male iron prawns. The pathways of choline metabolism in cancer and glycerophospholipid/histidine/propanoate metabolism have been significantly affected in iron prawns. Our work provides insight into the understanding of the formation mechanism of the “iron prawn”.

Lignin-based covalent organic polymers with improved crystallinity for non-targeted analysis of chemical hazards in food samples - Zhan-Chao Li; Wei Li; Rui Wang; Dong-Xia Wang; An-Na Tang; Xiao-Peng Wang; Xiao-Ping Gao; Gai-Ming Zhao; De-Ming Kong (Journal of Hazardous Materials, 2023)

Polycyclic aromatic hydrocarbon exposure burden: Individual and mixture analyses of associations with chronic obstructive pulmonary disease risk - Kun Peng; Zhao Li; Tian-Rui Gao; Jia Lv; Wen-Jing Wang; Ping Zhan; Wen-Cong Yao; Hui Zhao; Hua Wang; De-Xiang Xu; Yichao Huang; Zhu-Xia Tan (Environmental Research, 2023)

Better or worse food: Nutrition value of the prey fishes and the potential health implications for Indo-Pacific humpback dolphins - Jianqing Lin; Yan Liang; Hancheng Zhao; Qilin Gutang; Zonghuan Wu; Yan Gao; Sailan Liu; Kunhuan Li; Yinglin Wu; Zonghang Zhang; Ping Li; Wenhua Liu (Frontiers in Marine Science, 2023)
Introduction Overfishing and climate change have combined to cause fishery stocks to decline and fish community composition to change, further threatening the predation and nutritional health of marine mammals. Methods In this study, we collected potential prey fishes catched by fishermen in six habitats of Indo-Pacific humpback dolphins and analyzed their proximate composition (moisture, water, fat and protein), the fatty acid composition and the amino acid composition to evaluate the possible health effect on humpback dolphins. Results The results showed that the nutritional composition varied significantly with species and locations. Fishes in the families Sciaenidae and Engraulidae displayed richer fatty acid composition, while those in the family Clupeidae had the highest value of amino acid quality index. In Zhuhai, home to the largest Indo-Pacific humpback dolphin population, pelagic/neritic prey fishes possessed lower energy density, PUFA content, PUFA/SFA ratio, DHA content, and EAA content compared to demersal fish, suggesting nutritional stress when there is a dietary switch from demersal to pelagic/neritic fishes in Zhuhai population. Discussion Our study provided a framework, with energy density and fatty acid composition as its most important indicator, for assessment of the marine top predators based on the nutritional composition of their prey fishes and revealed the potential threats. Data here is expected to facilitate the development of scientific programs for successful conservation of not only the Indo-Pacific humpback dolphins, but also other marine top predators, possibly through reconstructing their prey fish’s quantity and quality.

Corrigendum: Shoreline change due to global climate change and human activity at the Shandong Peninsula from 2007 to 2020 - Wei Gao; Jun Du; Shan Gao; Yuanqin Xu; Bing Li; Xia Wei; Zhuoli Zhang; Jie Liu; Ping Li (Frontiers in Marine Science, 2023)

Associations of blood metals with liver function: Analysis of NHANES from 2011 to 2018 - Wenjie Li; Xinyan Li; Jing Su; Han Chen; Ping Zhao; Haisheng Qian; Xin Gao; Qiang Ye; Guoxin Zhang; Xuan Li (Chemosphere, 2023)

Effects of Reticuloendotheliosis virus on TLR-3/IFN-Β pathway in specific pathogen-free chickens - Wen-Jie Wu; Xiao-Ping Lv; Xiao-Yan Wang; Xue-Li Gao; Chao-Nan Liu; Chen-Hui Zhao; Xian-Zhe Gu; Shi-Min Zheng (Research in Veterinary Science, 2023)

Polyethylene and poly (butyleneadipate-co-terephthalate)-based biodegradable microplastics modulate the bioavailability and speciation of Cd and As in soil: Insights into transformation mechanisms - Chaohang Li; Huarong Sun; Yilan Shi; Zhengxiong Zhao; Zhen Zhang; Ping Zhao; Qiyan Gao; Xian Zhang; Bin Chen; Yongtao Li; Shuran He (Journal of Hazardous Materials, 2023)

Effects of different cooking methods on volatile flavor compounds in garlic - Jicai Bi; Zhen Yang; Yang Li; Bian Li; Yueyue Gao; Chunyuan Ping; Zhuo Chen; Congfa Li (International Journal of Gastronomy and Food Science, 2023)

Accelerated sulfate radical generation from peroxymonosulfate by ZIF-67-derived Co3O4 encapsulated in g-C3N4: A gift from in situ growth - Jinping Liang; Ling Fu; Kai Gao; Ping Zhang; Xiaoguang Duan; Xiaobo Gong; Li Cai (Chemical Engineering Journal, 2023)

Nitrogen loss from anaerobic ammonium oxidation coupled to Iron(III) reduction activity across estuarine and coastal wetlands of China: Spatial variations, controlling factors, and environmental implications - Shuntao Chen; Dengzhou Gao; Xiaofei Li; Dongyao Sun; Yanling Zheng; Hongpo Dong; Xia Liang; Guoyu Yin; Ping Han; Min Liu; Lijun Hou (CATENA, 2023)

Liquid water determination by airborne millimeter cloud radar and in-situ size distribution measurements - Dongfei Zuo; Dantong Liu; Delong Zhao; Ling Yang; Yichen Chen; Wei Zhou; Mengyu Huang; Hui He; Ping Tian; Yuanmou Du; Wei Xiao; Ruijie Li; et al. (Atmospheric Research, 2023)

Gas-in-place and its influence factors of the upper Paleozoic coal-bearing shale in the Qinshui Basin, China - Chengang Lu; Ping Gao; Gang Li; Yue Feng; Xiaorong Qu; Yufei Su; Xianming Xiao (Frontiers of Earth Science, 2023)

Gas in place and its controlling factors of deep shale of the Wufeng-Longmaxi Formations in the Dingshan area, Sichuan Basin - Ping Gao; Xianming Xiao; Dongfeng Hu; Ruobing Liu; Fei Li; Qin Zhou; Yidong Cai; Tao Yuan; Guangming Meng (Frontiers of Earth Science, 2023)

Effects of Internal Waves on Acoustic Temporal Coherence in the South China Sea - Fei Gao; Ping Hu; Fanghua Xu; Zhenglin Li; Jixing Qin (Journal of Marine Science and Engineering, 2023)
An acoustic experiment to measure the sound field during internal wave activity was conducted in the South China Sea. During the experiment, a train of strong internal solitary waves (ISWs) moved from the acoustic source to the receiver array along the acoustic path, and the propagation direction of the ISWs train was almost parallel to the acoustic path. Here, a study of the characteristics and physical mechanisms of the acoustic temporal coherence in this scenario is reported. The temporal coherence was analyzed by using the simulation results and experimental data. The results show that the temporal correlation coefficients oscillate quasi-periodically with both time and time delay, and the predominant oscillation periods are the same as the periods of the ISWs. The predominant fluctuation frequencies of the sound field correspond to some specific modes and lead to the periodicity of the temporal correlation coefficients. In the shallow layer, the spectrum structures of the temporal correlation coefficients are simpler because of the fewer effective modes.

Resistance vs. surrender: Different responses of functional traits of soybean and peanut to intercropping with maize - Wei-Ping Zhang; Zhao-Xin Li; Sai-Nan Gao; Hao Yang; Hua-Sen Xu; Xin Yang; Hong-Xia Fan; Ye Su; Surigaoge; Jacob Weiner; Dario Fornara; Long Li (Field Crops Research, 2023)

Stabilized effects of L-S cement-mixed batter pile composite foundation for existed warm frozen soil subgrade - Gao-chen Sun; Gang Yao; Jian-ming Zhang; Bo Li; Jun-qi Li; Wei-ping Lian; Yi Wei (Journal of Mountain Science, 2023)

Shoreline change due to global climate change and human activity at the Shandong Peninsula from 2007 to 2020 - Wei Gao; Jun Du; Shan Gao; Yuanqin Xu; Bing Li; Xia Wei; Zhuoli Zhang; Jie Liu; Ping Li (Frontiers in Marine Science, 2023)
In this study, how shoreline change responses to global climate change and human activity at the Shandong Peninsula was quantified by analyzing shoreline locations, inshore erosion/accretion rates, and sandy beach profiles for 2007–2020. During the study period, the total shoreline length decreased from 3345.55 km to 3310.18 km, whereas the natural shoreline decreased by 25.41%. As a dominant shore type, the artificial shoreline increased by 827.89 km. Human activities, such as land reclamation and harbor construction, have caused continuous shoreline advance, resulting in a net land increase of 672.40 km 2 . However, natural shores (e.g., sandy shore) receded at an average annual rate of −1.0 m due to ongoing erosion. The inshore waters of the Shandong Peninsula were largely sedimentary as erosion occurred only at a few hotspots. Therefore, seaward sediment deposition dominated the erosion/accretion trends of the inshore areas of the peninsula. However, global climate change and human activities have exacerbated the erosion caused by sea level rise. Specifically, the climate change caused absolute sea level rise and increasing frequency of extreme weather events, whereas the human activity dominated the transport and supply of sediment in the coastal zone. In the short term, the shoreline of the Shandong Peninsula continues to advance toward the sea due to the growing artificial shoreline. However, this disrupts the balance between sediment supply and marine energies in the coastal zone, and the system then rebalance itself by eroding unprotected natural shores. In the long term, main shoreline evolution trends depend on global climate change and sea level rise which plays a decisive role in shoreline retreat in the Shandong Peninsula.

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Impacts of climate change on future hurricane induced rainfall and flooding in a coastal watershed: A case study on Hurricane Harvey - Xudong Li; Dan Fu; John Nielsen-Gammon; Sudershan Gangrade; Shih-Chieh Kao; Ping Chang; Mario Morales Hernández; Nathalie Voisin; Zhe Zhang; Huilin Gao (Journal of Hydrology, 2023)

Photo-rechargeable all-solid-state lithium − sulfur batteries based on perovskite indoor photovoltaic modules - Tian-Tian Li; Yuan-Bo Yang; Bo-Sheng Zhao; Yue Wu; Xiao-Wen Wu; Peng Chen; Xue-Ping Gao (Chemical Engineering Journal, 2023)

Salt Bridge-intermediated three phase decoupling electrolytes for high voltage electrolytic aqueous Zinc-Manganese dioxides battery - Qi Xu; Qi-Xing Xie; Tong Xue; Gao Cheng; Jian-Dong Wu; Lan Ning; Xiang-Hui Yan; You-Jun Lu; Zhong-Li Zou; Bei-Ping Wang; Feng-Lan Han (Chemical Engineering Journal, 2023)

Combined nonlinear wave and current induced instantaneously-liquefied soil depth in a non-cohesive seabed - Li-Jing Yang; Fu-Ping Gao; Chang-fei Li (Coastal Engineering, 2023)

Biomarker selection strategies based on compound stability in wastewater-based epidemiology - Zhihan Gao; Ping Li; Han Lin; Wenting Lin; Yuan Ren (Environmental Science and Pollution Research, 2023)

Evaluation of agricultural water and soil resource matching characteristics considering increased precipitation-derived “green water”: a case study in the Yellow River Basin, China - Yun Gao; Ping Li; Hongyu Hou; Zhijie Liang; Yan Zhang; Xuebin Qi (Mitigation and Adaptation Strategies for Global Change, 2023)

The self-powered electrochemical biosensing platform with multi-amplification strategy for ultrasensitive detection of microRNA-155 - Yong-ping Gao; Ke-jing Huang; Fu-ting Wang; Yang-yang Hou; Lu-di Zhao; Bo-ya Wang; Jing Xu; Honglei Shuai; Guoqiang Li (Analytica Chimica Acta, 2023)

Highly efficient removal of hexavalent chromium by magnetic Fe–C composite from reed straw and electric furnace dust waste - Fu-Ping Wang; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Xi Zhang; Ai-Min Ji; Le-Le Kang; Rui Ji; Qing Yu; Di Gao; Xiao-Man Wang; Zhen Fang (Environmental Science and Pollution Research, 2022)

A Fundamental Role of Slope Aspect and Elevation in Controlling Diversity Patterns of Soil Bacterial Communities: Insights from an Arid-Montane Ecosystem in China - Long-Fei Chen; Jun-Qia Kong; Zhi-Bin He; Wen-Zhi Zhao; Ming-Dan Song; Yue-Mei Li; Yuan Gao; Shu-Ping Yang (Journal of Soil Science and Plant Nutrition, 2022)

An alkali-resistant metal–organic framework as halogen bond donor for efficient and selective removing of ReO4−/TcO4− - Qing-Hua Hu; Yu-Zhen Shi; Xin Gao; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Environmental Science and Pollution Research, 2022)

Proteomic analysis and identification reveal the anti-inflammatory mechanism of clofazimine on lipopolysaccharide-induced acute lung injury in mice - Bo Yang; Zhan Gao; Qi-Shuang Li; Xiang-Ye Zhang; Lan Song; Yi-Ni Wang; Xin-Yue Wang; Lin-Lin Ji; Hong-Liang Xu; Hui Xie; Fu-Kai Feng; Xiao-Ping Li; et al. (Inflammation Research, 2022)

Comparative transcriptome analysis of Portunus trituberculatus in response to Vibrio parahaemolyticus and low salinity - Yukun Li; Jianjian Lv; Jie Wu; Ping Liu; Baoquan Gao (Frontiers in Marine Science, 2022)
Vibrio parahaemolyticus is a common pathogen of marine crustaceans and is responsible for large losses in aquaculture. Salinity is an important environmental factor, and abrupt changes in salinity can affect the immunity of crustaceans. In this study, we carried out a transcriptomic analysis under pathogenic infection and low salt stress, and conducted a comparative analysis of the differentially expressed genes (DEGs) after stimulation by the two factors. Illumina sequencing technology was used for the transcriptome sequencing of 27 hepatopancreas samples, and 178.77 G sequencing data and an average of 44,142,119 clean reads per sample were obtained. A total of 3,047 and 3,710 DEGs were found after V. parahaemolyticus infection and low salt stress, which included a number of innate immunity genes, such as Toll-like receptor (TLR), anti-lipopolysaccharide factor (ALF), lectin, and hemocyanin. In addition, 2,016 common DEGs were found, accounting for 42.52% of the total DEGs. Among these, 169 DEGs were up-regulated after pathogenic infection and down-regulated after low salt stress, and were mainly enriched in starch and sucrose metabolism, nitrogen metabolism, amino sugar and nucleotide sugar processes, and other pathways. Collectively, these results provide data support for the analysis of the immune mechanism of crabs against V. parahaemolyticus and will also help to clarify the molecular mechanism by which salinity affects immunity.

Enhanced M-CSF/CSF1R Signaling Closely Associates with PrPSc Accumulation in the Scrapie-Infected Cell Line and the Brains of Scrapie-Infected Experimental Rodents - Ying Xia; Cao Chen; Jia Chen; Chao Hu; Wei Yang; Lin Wang; Lian Liu; Li-Ping Gao; Yue-Zhang Wu; Dong-Dong Chen; Qi Shi; Zhi-Bao Chen; et al. (Molecular Neurobiology, 2022)

Streptomyces akebiae sp. nov., a novel actinomycete isolated from rhizosphere soil of Akebia trifoliate - Ping Mo; Kaiqin Li; Jinhua Zhou; Fumin Zhou; Yazhi Chen; Xiaojia Lin; Xiaoyu Liu; Kerui Huang; Wansheng Zou; Jian Gao (Antonie van Leeuwenhoek, 2022)

Proteomic Analysis Associated with the Immune Response in Hemocytes of Portunus trituberculatus Challenged with Vibrio parahaemolyticus - Baoquan Gao; Xianyun Ren; Jianjian Lv; Xianliang Meng; Ping Liu; Jian Li (Fishes, 2022)
Vibrio parahaemolyticus belongs to an expanding group of aquatic pathogens that are widely distributed in aquatic environments. This species is a lethal pathogen for a number of economically important marine crabs. However, studies exploring host–vibrio interactions between V. parahaemolyticus and crabs are scarce, and therefore, the underlying molecular mechanisms are unclear. Herein, we performed a comprehensive proteomic analysis to investigate the immune response of Portunus trituberculatus hemocytes to V. parahaemolyticus infection. A total of 4433 proteins were identified using isobaric tags for relative and absolute quantitation (iTRAQ), and 526 differentially expressed proteins (DEPs) were subjected to Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway enrichment analysis, with six DEPs further subjected to quantitative real-time PCR. Several identified DEPs were found to be mainly involved in the immune defense of the crustacean, such as a hemocyanin subunit, C-type lectin, α-2-macroglobulin, Cu/Zn-superoxide dismutase, and heat shock protein 70, playing a key role in the response to V. parahaemolyticus infection. Moreover, many immune-related KEGG pathways were markedly altered, such as cell adhesion molecules, complement and coagulation cascades, and phagosomes. Our results provide insights into how V. parahaemolyticus overcomes the innate immunity of P. trituberculatus to induce pathological alterations in affected tissues. We report the first iTRAQ-based proteomic analysis and highlight the key pathways and proteins involved in the host–vibrio interactions between P. trituberculatus and V. parahaemolyticus. These findings should enhance our understanding of the molecular mechanisms underlying such interactions.

PPARγ alleviates peritoneal fibrosis progression along with promoting GLUT1 expression and suppressing peritoneal mesothelial cell proliferation - Junxia Feng; Meizhi Lu; Wenhao Li; Jingchun Li; Ping Meng; Zukai Li; Xuejuan Gao; Yunfang Zhang (Molecular and Cellular Biochemistry, 2022)
Objective Peritoneal fibrosis (PF) is commonly induced by bioincompatible dialysate exposure during peritoneal dialysis, but the underlying mechanisms remain elusive. This study aimed to investigate the roles of peroxisome proliferator-activated receptor gamma (PPARγ) in PF pathogenesis. Methods Rat and cellular PF models were established by high glucose dialysate and lipopolysaccharide treatments. Serum creatinine, urea nitrogen, and glucose contents were detected by ELISA. Histological evaluation was done through H&E and Masson staining. GLUT1, PPARγ, and other protein expression were measured by qRT-PCR, western blotting, and IHC. PPARγ and GLUT1 subcellular distribution were detected using confocal microscopy. Cell proliferation was assessed by MTT and Edu staining. Results Serum creatinine, urea nitrogen and glucose, and PPARγ and GLUT1 expression in rat PF model were reduced by PPARγ agonists Rosiglitazone or 15d-PGJ2 and elevated by antagonist GW9662. Rosiglitazone or 15d-PGJ2 repressed and GW9662 aggravated peritoneal fibrosis in rat PF model. PPARγ and GLUT1 were mainly localized in nucleus and cytosols of peritoneal mesothelial cells, respectively, which were reduced in cellular PF model, enhanced by Rosiglitazone or 15d-PGJ2, and repressed by GW9662. TGF-β and a-SMA expression was elevated in cellular PF model, which was inhibited by Rosiglitazone or 15d-PGJ2 and promoted by GW9662. PPARγ silencing reduced GLUT1, elevated a-SMA and TGF-b expression, and promoted peritoneal mesothelial cell proliferation, which were oppositely changed by PPARγ overexpression. Conclusion PPARγ inhibited high glucose-induced peritoneal fibrosis progression through elevating GLUT1 expression and repressing peritoneal mesothelial cell proliferation.

Full-Length Transcriptome Construction of the Blue Crab Callinectes sapidus - Baoquan Gao; Jianjian Lv; Xianliang Meng; Jitao Li; Yukun Li; Ping Liu; Jian Li (Frontiers in Marine Science, 2022)

Research on Ecological Security of Shengjin Lake Wetland (Anhui Province of China) Based on TM Images - Zhili Xu; Bin Dong; Xiang Gao; Ping Wang; Qing Wang; Sheng Li; Haifeng Xu; Yaru Liu; Tong Wang; Chunqiu Ren (Journal of the Indian Society of Remote Sensing, 2022)

An IQ Consortium Perspective on Connecting Dissolution Methods to In Vivo Performance: Analysis of an Industrial Database and Case Studies to Propose a Workflow - Aktham Aburub; Yuan Chen; John Chung; Ping Gao; David Good; Simone Hansmann; Michael Hawley; Tycho Heimbach; Martin Hingle; Filippos Kesisoglou; Rong Li; John Rose; et al. (The AAPS Journal, 2022)

Effects of Involuntary and Voluntary Exercise in Combination with Acousto-Optic Stimulation on Adult Neurogenesis in an Alzheimer's Mouse Model - Wan-yi Li; Jun-yan Gao; Su-Yang Lin; Shao-tao Pan; Biao Xiao; Yu-tao Ma; Kai Xie; Wei Shen; Zhi-tao Liu; Guang-yu Li; Jie-jie Guo; Qin-wen Wang; et al. (Molecular Neurobiology, 2022)

Response of xenobiotic biodegradation and metabolic genes in Tribolium castaneum following eugenol exposure - Yonglei Zhang; Shanshan Gao; Ping Zhang; Haidi Sun; Ruixue Lu; Runnan Yu; Yanxiao Li; Kunpeng Zhang; Bin Li (Molecular Genetics and Genomics, 2022)

Two new dammarane-type triterpenoids from the green walnut husks of Juglans mandshurica Maxim - Yuan-Yuan Zhou; Hui-Rui Gao; Hong-Juan Song; Dan-Da Ma; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Xiao-Li Wang; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2022)

Dissection of the practical soybean breeding pipeline by developing ZDX1, a high-throughput functional array - Rujian Sun; Bincheng Sun; Yu Tian; Shanshan Su; Yong Zhang; Wanhai Zhang; Jingshun Wang; Ping Yu; Bingfu Guo; Huihui Li; Yanfei Li; Huawei Gao; et al. (Theoretical and Applied Genetics, 2022)
Key message We developed the ZDX1 high-throughput functional soybean array for high accuracy evaluation and selection of both parents and progeny, which can greatly accelerate soybean breeding. Abstract Microarray technology facilitates rapid, accurate, and economical genotyping. Here, using resequencing data from 2214 representative soybean accessions, we developed the high-throughput functional array ZDX1, containing 158,959 SNPs, covering 90.92% of soybean genes and sites related to important traits. By application of the array, a total of 817 accessions were genotyped, including three subpopulations of candidate parental lines, parental lines and their progeny from practical breeding. The fixed SNPs were identified in progeny, indicating artificial selection during the breeding process. By identifying functional sites of target traits, novel soybean cyst nematode-resistant progeny and maturity-related novel sources were identified by allele combinations, demonstrating that functional sites provide an efficient method for the rapid screening of desirable traits or gene sources. Notably, we found that the breeding index (BI) was a good indicator for progeny selection. Superior progeny were derived from the combination of distantly related parents, with at least one parent having a higher BI. Furthermore, new combinations based on good performance were proposed for further breeding after excluding redundant and closely related parents. Genomic best linear unbiased prediction (GBLUP) analysis was the best analysis method and achieved the highest accuracy in predicting four traits when comparing SNPs in genic regions rather than whole genomic or intergenic SNPs. The prediction accuracy was improved by 32.1% by using progeny to expand the training population. Collectively, a versatile assay demonstrated that the functional ZDX1 array provided efficient information for the design and optimization of a breeding pipeline for accelerated soybean breeding.

Correction to: Spindle‑related brain activation in patients with insomnia disorder: An EEG‑fMRI study - Yan Shao; Guangyuan Zou; Serik Tabarak; Jie Chen; Xuejiao Gao; Ping Yao; Jiayi Liu; Yuezhen Li; Nana Xiong; Wen Pan; Mengying Ma; Shuqin Zhou; et al. (Brain Imaging and Behavior, 2022)

Spindle-related brain activation in patients with insomnia disorder: An EEG-fMRI study - Yan Shao; Guangyuan Zou; Serik Tabarak; Jie Chen; Xuejiao Gao; Ping Yao; Jiayi Liu; Yuezhen Li; Nana Xiong; Wen Pan; Mengying Ma; Shuqin Zhou; et al. (Brain Imaging and Behavior, 2022)

New sesquiterpeniod esters form Blumea balsamifera (L.) DC. and their anti-influenza virus activity - Yan Xiong; Ping Yi; Yuhuan Li; Rongmei Gao; Junlei Chen; Zhanxing Hu; Huayong Lou; Caixia Du; Jiayu Zhang; Yu Zhang; Chunmao Yuan; Liejun Huang; et al. (Natural Product Research, 2022)

Transcriptomic analyses reveal the effect of nitric oxide on the lateral root development and growth of mangrove plant Kandelia obovata - Ming-Yue Wei; Huan Li; You-Hui Zhong; Zhi-Jun Shen; Dong-Na Ma; Chang-Hao Gao; Yi-Ling Liu; Wen-Hua Wang; Jing-Ya Zhang; Yan-Ping You; Hai-Lei Zheng (Plant and Soil, 2022)

Size distributions and dry deposition fluxes of water-soluble inorganic nitrogen in atmospheric aerosols in Xiamen Bay, China - Shui-Ping Wu; Xiang Li; Yang Gao; Mei-Jun Cai; Chao Xu; James J. Schwab; Chung-Shin Yuan (Journal of Atmospheric Chemistry, 2022)

The tyrosine kinase inhibitor LPM4870108 impairs learning and memory and induces transcriptomic and gene‑specific DNA methylation changes in rats - Sijin Duan; Chunmei Li; Yonglin Gao; Ping Meng; Shengmin Ji; Yangyang Xu; Yutong Mao; Hongbo Wang; Jingwei Tian (Archives of Toxicology, 2022)

Cancer metabolism and tumor microenvironment: fostering each other? - Yiyuan Yuan; Huimin Li; Wang Pu; Leilei Chen; Dong Guo; Hongfei Jiang; Bo He; Siyuan Qin; Kui Wang; Na Li; Jingwei Feng; Jing Wen; et al. (Science China Life Sciences, 2022)

Effects of temperature, moisture, substrates and soil coverage on sclerotium germination and hyphal growth of Southern blight of apple in China - Xiang-li Dong; Chang-yan Gao; Ping-liang Li; Sen Lian; Shan-yue Zhou; Bao-hua Li (European Journal of Plant Pathology, 2022)

Comparative Genomic Analysis of Streptococcus pneumoniae Strains: Penicillin Non-susceptible Multi-drug-Resistant Serotype 19A Isolates - Lifeng Li; Juanjuan Zhou; Mingchao Li; Zengyuan Yu; Kaijie Gao; Junwen Yang; Ping Cheng; Junmei Yang; Wancun Zhang; Zhidan Yu; Huiqing Sun (Current Microbiology, 2022)

Cloning of catalase gene and antioxidant genes in Scophthalmus maximus response to metalloprotease of Vibrio anguillarum stress - Hai Ren; Jian Li; Ping Liu; Xianyun Ren; Tao Song; Guisheng Gao; Duwen Li; Shuaiting Liu (Journal of Oceanology and Limnology, 2022)

Integration of metabolomics and transcriptomics revealed the biosynthetic mechanism of anti-parasitic compounds in Salinivibrio proteolyticus strain YCSC6 - Guangxun Du; Lingyun Qu; Ping Gao; Wenhao Huang; Chenghua Li; Dewen Ding (Journal of Oceanology and Limnology, 2022)

Physiological and Molecular Responses in the Gill of the Swimming Crab Portunus trituberculatus During Long-Term Ammonia Stress - Jingyan Zhang; Mengqian Zhang; Nishad Jayasundara; Xianyun Ren; Baoquan Gao; Ping Liu; Jian Li; Xianliang Meng (Frontiers in Marine Science, 2021)
Ammonia is a common environmental stressor encountered during aquaculture, and is a significant concern due to its adverse biological effects on vertebrate and invertebrate including crustaceans. However, little information is available on physiological and molecular responses in crustaceans under long-term ammonia exposure, which often occurs in aquaculture practices. Here, we investigated temporal physiological and molecular responses in the gills, the main ammonia excretion organ, of the swimming crab Portunus trituberculatus following long-term (4 weeks) exposure to three different ammonia nitrogen concentrations (2, 4, and 8 mg l –1 ), in comparison to seawater (ammonia nitrogen below 0.03 mg l –1 ). The results revealed that after ammonia stress, the ammonia excretion and detoxification pathways were initially up-regulated. These processes appear compromised as the exposure duration extended, leading to accumulation of hemolymph ammonia, which coincided with the reduction of adenosine 5′-triphosphate (ATP) and adenylate energy charge (AEC). Considering that ammonia excretion and detoxification are highly energy-consuming, the depression of these pathways are, at least partly, associated with disruption of energy homeostasis in gills after prolonged ammonia exposure. Furthermore, our results indicated that long-term ammonia exposure can impair the antioxidant defense and result in increased lipid peroxidation, as well as induce endoplasmic reticulum stress, which in turn lead to apoptosis through p53-bax pathway in gills of the swimming crab. The findings of the present study further our understanding of adverse effects and underlying mechanisms of long-term ammonia in decapods, and provide valuable information for aquaculture management of P. trituberculatus .

Colchicine-induced tetraploidy influences morphological and cytological characteristics and enhances accumulation of anthocyanins in a red-fleshed radish (Raphanus sativus L.) - Fabo Chen; Jian Gao; Wenbo Li; Yi Liu; Ping Fang; Zhihang Peng (Horticulture, Environment, and Biotechnology, 2021)

Astaxanthin Ameliorates Blood Pressure in Salt-Induced Prehypertensive Rats Through ROS/MAPK/NF-κB Pathways in the Hypothalamic Paraventricular Nucleus - Hong-Li Gao; Xiao-Jing Yu; Yan Zhang; Chen-Long Wang; Yi-Ming Lei; Jia-Yue Yu; Dong-Miao Zong; Kai-Li Liu; Dong-Dong Zhang; Ying Li; Hua Tian; Nian-Ping Zhang; et al. (Cardiovascular Toxicology, 2021)

Genetic Prion Disease: Insight from the Features and Experience of China National Surveillance for Creutzfeldt-Jakob Disease - Qi Shi; Cao Chen; Kang Xiao; Wei Zhou; Li-Ping Gao; Dong-Dong Chen; Yue-Zhang Wu; Yuan Wang; Chao Hu; Chen Gao; Xiao-Ping Dong (Neuroscience Bulletin, 2021)

Two new cephalochromin derivative from the Alternaria sp. ZG22 - Xin-Ming Song; Xue-Ming Zhou; Ya-Ling Li; Li-Bing Huang; Cai-Cui Chen; Yan Gao; Lin He; Xiao-qun Mao; Bing Chen; Jing-Wen Liu; Hui-Jie Liu; Xiao-Ping Song; et al. (Natural Product Research, 2021)

Pleosporalins H and I, two new heptaketides from the endophytic fungus Pleosporales sp. F46 by using OSMAC strategy - Hong-Xia Yang; Xiao-Ping Peng; Han Gao; Hui-Min Zhang; Zi-Ru Wang; Gang Li; Hong-Xiang Lou (Natural Product Research, 2021)

Modulation of Antioxidant Enzymes, Heat Shock Protein, and Intestinal Microbiota of Large Yellow Croaker (Larimichthys crocea) Under Acute Cold Stress - Huirong Lv; Yanli Liu; Haidong Li; Xiaolong Yin; Ping Wang; Xiaoyu Qu; Yang Gao; Weiye Li; Zhangjie Chu (Frontiers in Marine Science, 2021)
The experiment was conducted in a sealed, temperature-controlled room. The initial water temperature of the treatment group was 12°C, lowered by 1°C a day to 8°C using a chiller, and maintained at that temperature for 3 days. The water temperature was then increased by 1°C per day to 12°C using a heater. The control group were the fish that kept at 12°C at the beginning of the experiment; T1 represents the group that sampled on the first day when the water temperature reached 8 from 12°C; T2 represents the group that sampled when the fish had been kept at 8°C for 3 days; T3 represents the group sampled when the water temperature was increased to 12 from 8°C. The antioxidant abilities of the liver, muscle, and intestine of large yellow croaker at different temperatures and times were determined, and the expression of HSP70 and HSP90 in the liver as well as the changes in intestinal microbiota were investigated. The results showed that the activities of SOD, CAT, GSH-Px, and MDA content increased significantly when the water temperature decreased from 12 to 8°C, significantly higher than those in the control group. The gene expression levels of HSP70 and HSP90 in the liver of large yellow croaker significantly increased under low temperature stress and were significantly higher than those in the control group. The diversity and abundance of intestinal microbiota of large yellow croaker were altered when the water temperature was maintained at 8°C, although the change was not obvious. Proteobacteria, Firmicutes, and Bacteroidetes were the dominate phyla in both the 12 and 8°C groups, and the temperature variation did not change the functional pathways of the microbiota. In conclusion, the acute temperature variation affected the antioxidant ability and heat shock protein expression of large yellow croaker but did not affect the diversity or abundance of the intestinal microbiota. These results will provide a theoretical basis for studying the mechanisms of large yellow croaker overwintering and adaptation to low temperatures.

Triterpene saponins from tea seed pomace ( Camellia oleifera Abel) and their cytotoxic activity on MCF-7 cells in vitro - Xin-Fu Zhang; Ying-Ying Han; Tai-Mei Di; Li-Ping Gao; Tao Xia (Natural Product Research, 2021)

Size distributions and health risks of particle-bound toxic elements in the southeast coastland of China - Shui-Ping Wu; Xiang Li; Mei-Jun Cai; Yang Gao; Chao Xu; James J. Schwab; Chung-Shin Yuan (Environmental Science and Pollution Research, 2021)

The rescue and selection of thermally stable type O vaccine candidate strains of foot-and-mouth disease virus - Ya Gao; Pinghua Li; Xueqing Ma; Xingwen Bai; Pu Sun; Ping Du; Hong Yuan; Yimei Cao; Kun Li; Yuanfang Fu; Jing Zhang; Huifang Bao; et al. (Archives of Virology, 2021)

Metabolomics Analysis Reveals the Role of Cyanidin Metabolism in Plumbago auriculata Flower Color - Yurong Li; Wenji Li; Di Hu; Ting Lei; Ping Shen; Jiani Li; Suping Gao (Journal of Plant Biology, 2021)

Nutrigenomics reveals potential genetic underpinning of diverse taste preference of Chinese men - Zhouhai Zhu; Junpu Mei; Silong Sun; Sheming Lu; Meng Li; Ying Guan; Ying Chen; Yuqiong Xu; Tao Zhang; Fengxue Shi; Xuemei Li; Mingming Miao; et al. (Genes & Genomics, 2021)

Study on Microwave Heating Order and Electromagnetic Characteristics of Copper and Gold Ores - Feng Lin; Xia-Ting Feng; Gao-Ming Lu; Xiang-Xin Su; Shi-Ping Li; Jiu-yu Zhang (Rock Mechanics and Rock Engineering, 2021)

PsGRGH, a TOS1 family-like gene, is involved in the vegetative growth, environmental stress response, and pathogenicity of Phytophthora sojae - Dong Liu; Kunyuan Li; Jiulong Hu; Ping Li; Xiao Liu; Zhimou Gao (European Journal of Plant Pathology, 2021)

The nonreciprocal heterostyly and heterotypic self-incompatibility of Ceratostigma willmottianum - Suping Gao; Wenji Li; Meiting Hong; Ting Lei; Ping Shen; Jiani Li; Mingyan Jiang; Yifan Duan; Lisha Shi (Journal of Plant Research, 2021)

Transcriptomic analysis of saffron at different flowering stages using RNA sequencing uncovers cytochrome P450 genes involved in crocin biosynthesis - Guangchun Gao; Jiming Wu; Bai Li; Qi Jiang; Ping Wang; Jun Li (Molecular Biology Reports, 2021)

Increased depression risk for elderly women with high blood levels of strontium and barium - Jia Lv; Yan-ling Li; Wen-qiang Ren; Rong Li; Jian-rong Chen; Chao Bao; Zhi-ping Du; Shun Feng; Ling Gu; Hui Gao; Kai-yong Liu; Lin-sheng Yang; et al. (Environmental Chemistry Letters, 2021)

Sediment Characteristics, Sources, and Transport Patterns in Kompong Som Bay, Cambodia: Indications from Grain Size and Heavy Minerals - Jinqing Liu; Xiaoying Chen; Ping Yin; Ke Cao; Fei Gao; Yuanku Meng; Jiandong Qiu; Meina Li (Journal of Ocean University of China, 2021)

An Insight into the Excavation-Induced Stress Paths on Mechanical Response of Weak Interlayer Zone in Underground Cavern Under High Geostress - Shu-Qian Duan; Quan Jiang; Guo-Feng Liu; Jie-Cheng Xiong; Po Gao; Ding-Ping Xu; Ming-Yu Li (Rock Mechanics and Rock Engineering, 2021)

Comparison of Long-Term Outcomes of Endoscopic and Minimally Invasive Catheter Evacuation for the Treatment of Spontaneous Cerebellar Hemorrhage - Leiyang Li; Haixiao Liu; Jianing Luo; Zhijun Tan; Junmei Gao; Ping Wang; Wenting Jing; Ruixi Fan; Xiaoyang Zhang; Hao Guo; Hao Bai; Wenxing Cui; et al. (Translational Stroke Research, 2021)
Recently, minimally invasive techniques, including endoscopic evacuation and minimally invasive catheter (MIC) evacuation, have been used for the treatment of patients with spontaneous cerebellar hemorrhage (SCH). However, credible evidence is still needed to validate the effects of these techniques. To explore the long-term outcomes of both surgical techniques in the treatment of SCH. Fifty-two patients with SCH who received endoscopic evacuation or MIC evacuation were retrospectively reviewed. Six-month mortality and the modified Rankin Scale (mRS) score were the primary and secondary outcomes, respectively. A multivariate logistic regression model was used to assess the effects of the different surgical techniques on patient outcomes. In the present study, the mortality rate for the entire cohort was 34.6%. Univariate analysis showed that the surgical technique and preoperative Glasgow Coma Scale (GCS) score affected 6-month mortality. However, no variables were found to be correlated with 6-month mRS scores. Further multivariate analysis demonstrated that 6-month mortality in the endoscopic evacuation group was significantly lower than that in the MIC evacuation group (OR = 4.346, 95% CI 1.056 to 17.886). The 6-month mortality rate in the preoperative GCS 9–14 group was significantly lower than that in the GCS 3–8 group (OR = 7.328, 95% CI 1.723 to 31.170). Compared with MIC evacuation, endoscopic evacuation significantly decreased 6-month mortality in SCH patients. These preliminary results warrant further large, prospective, randomized studies.

Genetic diversity analysis of intraspecific hybridization between Plumbago auriculata and Plumbago auriculata f. alba based on horticultural traits and molecular markers - Xi Chen; Suping Gao; Ping Shen; Yingqi Liu; Ting Lei; Lisha Shi; Wenji Li; Yurong Li; Xiaofang Yu; Lijuan Yang; Jiani Li (Acta Physiologiae Plantarum, 2021)

Sesquiterpenoids and meroterpenoids from a mangrove derived fungus Diaporthe sp. SCSIO 41011 - Xiao-Wei Luo; Chun-Mei Chen; Kun-Long Li; Xiu-Ping Lin; Cheng-Hai Gao; Xue-Feng Zhou; Yong-Hong Liu (Natural Product Research, 2021)

New developments in anti-biofilm intervention towards effective management of orthopedic device related infections (ODRI’s) - Ping Li; Zhenwu Gao; Zhenwei Tan; Jun Xiao; Li Wei; Yirui Chen (Biofouling, 2021)

Possible effects of leaf tissue characteristics of oilseed rape Brassica napus on probing and feeding behaviors of cabbage aphids Brevicoryne brassicae - Zhong-Ping Hao; Hai-Xia Zhan; Ling-Ling Gao; Fang Huang; Li-Ni Zhu; Shu-Min Hou (Arthropod-Plant Interactions, 2020)

Zircon U-Pb-Hf isotopes and geochemistry of Jurassic igneous rocks from the southern Zhangguangcai Range, NE China: constraints on magmatism, petrogenesis and tectonic implications - Zuo-Zhen Han; Xiang Ren; Hans-Peter Schertl; Xu-Ping Li; Zhi-Gang Song; Qing-Xiang Du; Chao Han; Wen-Jian Zhong; Li-Hua Gao (International Geology Review, 2020)

Association of ADH7 Gene Polymorphism with Schizophrenia in the Han Population of Northern China: a Case-Control Study - Kuo Zeng; Ya Li; Meng Gao; Yong-ping Liu; Feng-ling Xu; Xi Xia; Jun Yao; Bao-jie Wang (Journal of Molecular Neuroscience, 2020)

What factors determine the mass elevation effect of the Tibetan Plateau? - Fang Han; Li Wan; Hong-zhi Wu; Bai-ping Zhang; Lan Gao; Ge Song (Journal of Mountain Science, 2020)

Pre-symptomatic local brain activity and functional connectivity alterations in nasopharyngeal carcinoma patients who developed radiation encephalopathy following radiotherapy - You-ming Zhang; Jian-ming Gao; Hong Zhou; Li Li; Li-zhi Liu; Zai-de Han; Xiao-ping Yi; Wei-hua Liao (Brain Imaging and Behavior, 2020)

Colletotrichum neorubicola sp. nov., a new leaf anthracnose pathogen of raspberry from northeast China - Li-Ping Liu; Yu Wang; Peng-Lei Qiu; Bo Zhang; Lin Zhang; Na Wang; Yu Li; Jie Gao; Tom Hsiang (Mycological Progress, 2020)

A family cluster of severe acute respiratory syndrome coronavirus 2 infections - Xuesong Gao; Zheng Yuan; Di Yang; Hongjie Li; Yijin Zhang; Ping Gao; Xiaomin Liu; Wenshan Zhao; Te Xiao; Xuefei Duan (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

High throughput solid-phase screening of bacteria with cyclic amino alcohol deamination activity for enantioselective synthesis of chiral cyclic β-amino alcohols - Ya-Wen Chang; Jian-Dong Zhang; Xiao-Xiao Yang; Jing Li; Li-Li Gao; Shuang-Ping Huang; Xing-Mei Guo; Cao-Feng Zhang; Hong-Hong Chang; Jian-He Xu (Biotechnology Letters, 2020)

Serotonin-induced miR-221/222 contribute to the activation of hepatic stellate cells - Yi Xiang; Yu-Shui Ma; Ji-Bin Liu; Zhi-Jun Wu; Xiao-Ping Wang; Li-Ping Liu; Gao-Ren Wang; Da Fu; Wei Shi (Biologia, 2020)

Removal of SO2 and NOx from flue gas using mud-phosphorus slurry - Lijuan Jia; Zizhen Li; Qian Yu; Jiyun Gao; Chenhui Liu; Tiancheng Liu; Ping Ning; Fang Wang (Environmental Science and Pollution Research, 2020)

Research on intelligent prediction and zonation of basin-scale flood risk based on LSTM method - Minzhi Yang; Ping-an Zhong; Jieyu Li; Weifeng Liu; Yinghui Li; Kun Yan; Yinyang Yuan; Yihui Gao (Environmental Monitoring and Assessment, 2020)

Transcriptome profiling of Plumbago auriculata Lam. in response to cold stress - Wenji Li; Suping Gao; Qiao Li; Ping Shen; Yurong Li; Di Hu; Ting Lei; Xi Chen; Jiani Li (Acta Physiologiae Plantarum, 2020)

An Injectable Nanocomposite Hydrogel for Potential Application of Vascularization and Tissue Repair - Yilei Ding; An-sha Zhao; Tianmei Liu; Ya-nan Wang; Yuan Gao; Jing-an Li; Ping Yang (Annals of Biomedical Engineering, 2020)

Study of Directional Declustering for Estimating Extreme Wave Heights in the Yellow Sea - Huijun Gao; Zhuxiao Shao; Guoxiang Wu; Ping Li (Journal of Marine Science and Engineering, 2020)
The study of extreme waves is important for the protection of coastal and ocean structures. In this work, a 22-year (1990–2011) wave hindcast in the Yellow Sea is employed to perform the assessment of extreme significant wave heights in this area. To extract the independent sample from this database, the fixed window method is used, which takes the peak significant wave height within five d. With the selected samples, directional declustering is studied to extract the homogenous sample. The results show that most of the independent samples (especially large samples) are observed in the North. In this direction, the peak over threshold (POT) method is used to extract the extreme sample from the homogenous sample, and then the generalized Pareto distribution model is used to extrapolate the extreme significant wave height. In addition to this combination, the annual maxima method with the Gumbel model is also used for estimating extreme values. The comparisons show that the return significant wave heights of the first combination are reliable, resulting from a flexible sampling window in the POT method. With this conclusion, the extreme significant wave height is extrapolated from the Yellow Sea, which can be used to protect the structure in the main directional bin.

Fupyrones A and B, two new α -pyrones from an endophytic fungus, Fusarium sp. F20 - Han Gao; Gang Li; Xiao-Ping Peng; Hong-Xiang Lou (Natural Product Research, 2020)

Alternative complement pathway is activated in the brains of scrapie-infected rodents - Cao Chen; Yan Lv; Chao Hu; Xiao-Feng Xu; Ren-Qing Zhang; Kang Xiao; Yue Ma; Li-Ping Gao; Jian-Le Li; Qiang Shi; Jing Wang; Qi Shi; et al. (Medical Microbiology and Immunology, 2020)

Identification of rs11615992 as a novel regulatory SNP for human P2RX7 by allele-specific expression - Tao Peng; Li Zhong; Jing Gao; Zhu Wan; Wei-Ping Fu; Chang Sun (Molecular Genetics and Genomics, 2020)

Cloning and expression analysis of the StCUL1 gene in potato - Peng-Xiang Pang; Li Shi; Xiao-Juan Wang; Yan-Nan Chang; Yong-Ping Luo; Jin-Lin Feng; Hemu Eri; Gang Gao (Journal of Plant Biochemistry and Biotechnology, 2019)

Potential role of IL-37 signaling pathway in feedback regulation of autoimmune Hashimoto thyroiditis - Cui-Ping Ren; Li Sun; Feng-Chun Liu; Chun-Lin Zuo; Miao Liu; Wenda Gao; Ji-Jia Shen (Histochemistry and Cell Biology, 2019)

Correction to: Vertical Distributions of Suspended Sediment Concentrations in the Turbidity Maximum Zone of the Periodically and Partially Stratified Changjiang Estuary - Zhanhai Li; Jianjun Jia; Yongsheng Wu; Haibo Zong; Guoan Zhang; Ya Ping Wang; Yang Yang; Liang Zhou; Shu Gao (Estuaries and Coasts, 2019)

Geotechnical properties and stability of the submarine canyon in the northern South China Sea - Jie Liu; Lejun Liu; Ping Li; Shan Gao; Wei Gao; Yuanqin Xu (Acta Oceanologica Sinica, 2019)

Exotic Spartina alterniflora invasion alters soil nitrous oxide emission dynamics in a coastal wetland of China - Dengzhou Gao; Lijun Hou; Xiaofei Li; Min Liu; Yanling Zheng; Guoyu Yin; Yi Yang; Cheng Liu; Ping Han (Plant and Soil, 2019)

Vertical Distributions of Suspended Sediment Concentrations in the Turbidity Maximum Zone of the Periodically and Partially Stratified Changjiang Estuary - Zhanhai Li; Jianjun Jia; Yongsheng Wu; Haibo Zong; Guoan Zhang; Yax Ping Wang; Yang Yang; Liang Zhou; Shu Gao (Estuaries and Coasts, 2019)

Identification of cis-regulatory regions responsible for developmental and hormonal regulation of HbHMGS1 in transgenic Arabidopsis thaliana - Xiao-Xiao Gong; Bing-Yu Yan; Yu-Rong Tan; Xuan Gao; Dan Wang; Heng Zhang; Peng Wang; Shuang-Jiang Li; Yi Wang; Lu-Yao Zhou; Jin-Ping Liu (Biotechnology Letters, 2019)

Water supply risk analysis of Panjiakou reservoir in Luanhe River basin of China and drought impacts under environmental change - Jianzhu Li; Zhenxing Gao; Yuangang Guo; Ting Zhang; Peizhen Ren; Ping Feng (Theoretical and Applied Climatology, 2019)

Comparative Transcriptome Analysis Reveals Differentially Expressed Genes and Signaling Pathways Between Male and Female Red-Tail Catfish (Mystus wyckioides) - Jun-Jie Wu; Yu-Lin Zhou; Zhong-Wei Wang; Guang-Hua Li; Fang-Peng Jin; Li-Li Cui; Hai-Tao Gao; Xin-Ping Li; Li Zhou; Jian-Fang Gui (Marine Biotechnology, 2019)

Temporal profile of illicit drug consumption in Guangzhou, China monitored by wastewater-based epidemiology - Xiaohan Zhang; Riheng Huang; Ping Li; Yuan Ren; Jianfa Gao; Jochen F. Mueller; Phong K Thai (Environmental Science and Pollution Research, 2019)

Evaluation of TIGGE Daily Accumulated Precipitation Forecasts over the Qu River Basin, China - Li Liu; Chao Gao; Qian Zhu; Yue-Ping Xu (Journal of Meteorological Research, 2019)

Transcriptomic analysis provides insight into the mechanism of salinity adjustment in swimming crab Portunus trituberculatus - Baoquan Gao; Dongfang Sun; Jianjian Lv; Xianyun Ren; Ping Liu; Jian Li (Genes & Genomics, 2019)

Identification of SNP markers correlated with the tolerance of low-salinity challenge in swimming crab (Portunus trituberculatus) - Yanyan Feng; Dening Zhang; Jianjian Lv; Baoquan Gao; Jian Li; Ping Liu (Acta Oceanologica Sinica, 2019)

Numerical Analysis on the Effect of Artificial Ventilated Pipe Diameter on Hydrodynamic Performance of a Surface-Piercing Propeller - Zeyang Gao; Dongmei Yang; Ping Li; Yue Dong (Journal of Marine Science and Engineering, 2019)
Under the condition of large water immersion, surface-piercing propellers are inclined to be heavy loaded. In order to improve the hydrodynamic performance of the surface-piercing propeller, the installation of a vent pipe in front of a propeller disc is more widely used in the propulsion device of high speed planning crafts. Based on computational fluid dynamics (CFD) method, this paper studied the influence of diverse vent pipe diameters on hydrodynamic performance of the surface-piercing propeller under full water immersion conditions. The numerical results show that, with the increase of vent pipe diameters, the thrust and torque of the surface-piercing propeller decrease after ventilation, and the efficiency of the propeller increases rapidly; the low pressure area near the back root of the blade becomes smaller and smaller gradually; and the peak of periodic vibration of thrust and torque can be effectively reduced. The numerical results demonstrate that the installation of artificial vent pipe effectively improves the hydrodynamic performance of surface piercing propeller in the field of high speed crafts, and the increase of artificial vent pipe diameter plays an active role in the propulsion efficiency of the surface-piercing propeller.

Effects of AM fungi and grass endophytes on perennial ryegrass Bipolaris sorokiniana leaf spot disease under limited soil nutrients - Yane Guo; Ping Gao; Fang Li; Tingyu Duan (European Journal of Plant Pathology, 2019)

Human Biological Monitoring of Mercury Through Hair Samples in China - Ping Li; Shuhui Guo; Jiating Zhao; Yuxi Gao; Yu-Feng Li (Bulletin of Environmental Contamination and Toxicology, 2019)

Expression of the intrarenal angiotensin receptor and the role of renin-angiotensin system inhibitors in IgA nephropathy - Zheng Zhang; Shi-min Jiang; Ye-ping Ma; Pei-lin Dai; Yi-ning Wang; Gu-ming Zou; Hong-mei Gao; Yue Yang; Wen-ge Li (Molecular and Cellular Biochemistry, 2019)

Habitat selection of wintering cranes (Gruidae) in typical lake wetland in the lower reaches of the Yangtze River, China - Cheng Wang; Bin Dong; Ming Zhu; Hui Huang; Yu-huang Cui; Xiang Gao; Li-ping Liu (Environmental Science and Pollution Research, 2019)

Attribute recognition model for risk assessment of water inrush - Jing Wang; Shu-cai Li; Li-ping Li; Peng Lin; Zhen-hao Xu; Cheng-lu Gao (Bulletin of Engineering Geology and the Environment, 2019)

Plot-scale spatiotemporal variations of CO2 concentration and flux across water–air interfaces at aquaculture shrimp ponds in a subtropical estuary - Yifei Zhang; Ping Yang; Hong Yang; Lishan Tan; Qianqian Guo; Guanghui Zhao; Ling Li; Yuchuan Gao; Chuan Tong (Environmental Science and Pollution Research, 2019)

miR-377-3p regulates adipogenic differentiation of human bone marrow mesenchymal stem cells by regulating LIFR - Xingnuan Li; Yaofang Yang; Ruiqiao Yan; Xiaoyuan Xu; Liyun Gao; Jun Mei; Jianyun Liu; Xinping Wang; Jie Zhang; Ping Wu; Weidong Li; Zhijun Zhao; et al. (Molecular and Cellular Biochemistry, 2018)

The sedimentary facies and dynamic environment of the Diaokou lobe in the modern Huanghe River Delta of China - Wei Gao; Shihao Liu; Jie Liu; Yuanqin Xu; Ping Li (Acta Oceanologica Sinica, 2018)

Molecular insights into brown rust resistance and potential epidemic based on the Bru1 gene in sugarcane varieties and new elite clones - Zhu Li; Ya-Chun Su; Qing Yu; Yun Chen; Shi-Wu Gao; Yong-Gang Zhang; You-Xiong Que; Li-Ping Xu (Euphytica, 2018)

Gram-negative bacilli-derived peptide antibiotics developed since 2000 - Yun Xue; Mengya Wang; Pengchao Zhao; Chunshan Quan; Xin Li; Lina Wang; Weina Gao; Jinghua Li; Xiangyang Zu; Dongliao Fu; Shuxiao Feng; Ping Li (Biotechnology Letters, 2018)

Source identification of PAHs in soils based on stable carbon isotopic signatures - Peng Gao; Hongbo Li; Chris P. Wilson; Timothy G. Townsend; Ping Xiang; Yungen Liu; Lena Q. Ma (Critical Reviews in Environmental Science and Technology, 2018)

Design of a Displacement Monitoring System Based on Optical Grating and Numerical Verification in Geomechanical Model Test of Water Leakage of Tunnel - Shang-qu Sun; Shu-cai Li; Li-ping Li; Shao-shuai Shi; Zong-qing Zhou; Cheng-lu Gao (Geotechnical and Geological Engineering, 2018)

Corn yields with organic and inorganic amendments under changing climate - Ping Liu; Haijun Zhao; Yan Li; Zhaohui Liu; Xinhao Gao; Yingpeng Zhang; Ming Sun; Ziwen Zhong; Jiafa Luo (Nutrient Cycling in Agroecosystems, 2018)

Transcriptome analysis of wheat seedling and spike tissues in the hybrid Jingmai 8 uncovered genes involved in heterosis - Yong-jie Liu; Shi-qing Gao; Yi-miao Tang; Jie Gong; Xiao Zhang; Yong-bo Wang; Li-ping Zhang; Ren-wei Sun; Quan Zhang; Zhao-bo Chen; Xiang Wang; Cai-juan Guo; et al. (Planta, 2018)

Diversity effect of capsaicin on different types of skeletal muscle - Gan Zhou; Lina Wang; Yaqiong Xu; Kelin Yang; Lv Luo; Leshan Wang; Yongxiang Li; Jiawen Wang; Gang Shu; Songbo Wang; Ping Gao; Xiaotong Zhu; et al. (Molecular and Cellular Biochemistry, 2018)

The Risk Assessment of Tunnels Based on Grey Correlation and Entropy Weight Method - Cheng-lu Gao; Shu-cai Li; Jing Wang; Li-ping Li; Peng Lin (Geotechnical and Geological Engineering, 2018)

A new pair of enantiomeric lignans from the fruits of Morinda citrifolia and their absolute configuration - Wen-Jian Liu; Yue-Juan Chen; Dan-Na Chen; Ya-Ping Wu; Yu-Jie Gao; Jing Li; Wen-Jun Zhong; Lin Jiang (Natural Product Research, 2018)

Effects of dual inoculation of AMF and rhizobium on alfalfa (Medicago sativa) root rot caused by Microdochium tabacinum - Ping Gao; Yane Guo; Yingde Li; Tingyu Duan (Australasian Plant Pathology, 2018)

An arbuscular mycorrhizal fungus and Epichloë festucae var. lolii reduce Bipolaris sorokiniana disease incidence and improve perennial ryegrass growth - Fang Li; Yan’e Guo; Michael J. Christensen; Ping Gao; Yanzhong Li; Tingyu Duan (Mycorrhiza, 2018)

Phenolic constituents from Rheum nobile and their antioxidant activity - Ye Fei; Juan Wang; Bing Peng; Jiangnan Peng; Jing-Hong Hu; Zu-Ping Zeng; Jing Chen; Qi-En Li; Zeng-Ping Gao; Xing-Li Yan (Natural Product Research, 2017)

Comorbidity Burden of Dementia: A Hospital-Based Retrospective Study from 2003 to 2012 in Seven Cities in China - Qing-Hua Wang; Xin Wang; Xian-Le Bu; Yan Lian; Yang Xiang; Hong-Bo Luo; Hai-Qiang Zou; Jie Pu; Zhong-He Zhou; Xiao-Ping Cui; Qing-Song Wang; Xiang-Qun Shi; et al. (Neuroscience Bulletin, 2017)

Rapid response to changing environments during biological invasions: DNA methylation perspectives - Xuena Huang; Shiguo Li; Ping Ni; Yangchun Gao; Bei Jiang; Zunchun Zhou; Aibin Zhan (Molecular Ecology, 2017)
Dissecting complex interactions between species and their environments has long been a research hot spot in the fields of ecology and evolutionary biology. The well‐recognized Darwinian evolution has well‐explained long‐term adaptation scenarios; however, “rapid” processes of biological responses to environmental changes remain largely unexplored, particularly molecular mechanisms such as DNA methylation that have recently been proposed to play crucial roles in rapid environmental adaptation. Invasive species, which have capacities to successfully survive rapidly changing environments during biological invasions, provide great opportunities to study molecular mechanisms of rapid environmental adaptation. Here, we used the methylation‐sensitive amplified polymorphism (MSAP) technique in an invasive model ascidian, Ciona savignyi , to investigate how species interact with rapidly changing environments at the whole‐genome level. We detected quite rapid DNA methylation response: significant changes of DNA methylation frequency and epigenetic differentiation between treatment and control groups occurred only after 1 hr of high‐temperature exposure or after 3 hr of low‐salinity challenge. In addition, we detected time‐dependent hemimethylation changes and increased intragroup epigenetic divergence induced by environmental stresses. Interestingly, we found evidence of DNA methylation resilience, as most stress‐induced DNA methylation variation maintained shortly (~48 hr) and quickly returned back to the control levels. Our findings clearly showed that invasive species could rapidly respond to acute environmental changes through DNA methylation modifications, and rapid environmental changes left significant epigenetic signatures at the whole‐genome level. All these results provide fundamental background to deeply investigate the contribution of DNA methylation mechanisms to rapid contemporary environmental adaptation.

Testing of antiviral characteristics of flammutoxin in transgenic tobacco - Li-Ping Wu; Xue-Ling Gao; Yuan-Dan Duan; Ye-Yu Bian; Tao Yang; Ming-Jia Fu (Journal of Plant Diseases and Protection, 2017)

Comparison of infrared canopy temperature in a rubber plantation and tropical rain forest - Qing-Hai Song; Yun Deng; Yi -Ping Zhang; Xiao-Bao Deng; You-Xing Lin; Li-Guo Zhou; Xue-Hai Fei; Li-Qing Sha; Yun-Tong Liu; Wen-Jun Zhou; Jin-Bo Gao (International Journal of Biometeorology, 2017)

Development of Albumin Coupled, Cholesterol Stabilized, Lipid Nanoemulsion of Methotrexate, and TNF-α Inhibitor for Improved In Vivo Efficacy Against Rheumatoid Arthritis - Xiao-yan Li; Hui Li; Yan Zhang; Shan Gao; Chun-ping Dong; Gui-fu Wu (AAPS PharmSciTech, 2017)

Oxidative stress promotes myocardial fibrosis by upregulating KCa3.1 channel expression in AGT-REN double transgenic hypertensive mice - Li-Ping Wang; Su-Jing Fan; Shu-Min Li; Xiao-Jun Wang; Jun-Ling Gao; Xiu-Hong Yang (Pflügers Archiv - European Journal of Physiology, 2017)

Long-term Ameliorative Effects of the Antidepressant Fluoxetine Exposure on Cognitive Deficits in 3 × TgAD Mice - Li Jin; Li-Feng Gao; Dong-Sheng Sun; Hao Wu; Qun Wang; Dan Ke; Hao Lei; Jian-Zhi Wang; Gong-Ping Liu (Molecular Neurobiology, 2017)

Residents’ satisfaction to post-Wenchuan earthquake recovery and reconstruction - Yueqiao Yang; Ping Gao; Haijun Li (Natural Hazards, 2017)

The difference analysis of physical-mechanical properties of sediments in the central South Yellow Sea and Zhe-Min coastal area in China - Yuanqin Xu; Ping Li; Peiying Li; Jun Du; Lejun Liu; Wei Gao; Jie Liu (Acta Oceanologica Sinica, 2017)

Detecting the Changes of Water Qualities and Fluorescent DOM in a Constructed Rapid Infiltration System - Ping-ping Gao; Yun-zhen Li; Xu-jing Guo; Tao Huang; Dong-hai Yuan; Xian-dong Tan (Wetlands, 2017)

Epigenetic Downregulation of Scn3a Expression by Valproate: a Possible Role in Its Anticonvulsant Activity - Na-Na Tan; Hui-Ling Tang; Guo-Wang Lin; Yong-Hong Chen; Ping Lu; Hai-Jun Li; Mei-Mei Gao; Qi-Hua Zhao; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Molecular Neurobiology, 2017)

A Point Mutation in SCN1A 5′ Genomic Region Decreases the Promoter Activity and Is Associated with Mild Epilepsy and Seizure Aggravation Induced by Antiepileptic Drug - Qu-Wen Gao; Li-Dong Hua; Jie Wang; Cui-Xia Fan; Wei-Yi Deng; Bin Li; Wen-Jun Bian; Chuan-Xing Shao; Na He; Peng Zhou; Wei-Ping Liao; Yi-Wu Shi (Molecular Neurobiology, 2017)

The Brain NO Levels and NOS Activities Ascended in the Early and Middle Stages and Descended in the Terminal Stage in Scrapie-Infected Animal Models - Li-Na Chen; Jing Sun; Xiao-Dong Yang; Kang Xiao; Yan Lv; Bao-Yun Zhang; Wei Zhou; Cao Chen; Chen Gao; Qi Shi; Xiao-Ping Dong (Molecular Neurobiology, 2017)

Identification and Characterization of the Lysine-Rich Matrix Protein Family in Pinctada fucata: Indicative of Roles in Shell Formation - Jian Liang; Jun Xie; Jing Gao; Chao-Qun Xu; Yi Yan; Gan-Chu Jia; Liang Xiang; Li-Ping Xie; Rong-Qing Zhang (Marine Biotechnology, 2016)

Protective role of ACE2-Ang-(1–7)-Mas in myocardial fibrosis by downregulating KCa3.1 channel via ERK1/2 pathway - Li-Ping Wang; Su-Jing Fan; Shu-Min Li; Xiao-Jun Wang; Jun-Ling Gao; Xiu-Hong Yang (Pflügers Archiv - European Journal of Physiology, 2016)

Netrin-1 Contributes to Myelinated Afferent Fiber Sprouting and Neuropathic Pain - Cai-Hua Wu; Xiao-Cui Yuan; Fang Gao; Hong-Ping Li; Jie Cao; Yan-Shen Liu; Wei Yu; Bo Tian; Xian-Fang Meng; Jing Shi; Hui-Lin Pan; Man Li (Molecular Neurobiology, 2016)

Se Enhances MLCK Activation by Regulating Selenoprotein T (SelT) in the Gastric Smooth Muscle of Rats - Jia-ping Li; Jing-xuan Zhou; Qi Wang; Gao-qin Gu; Shi-jin Yang; Cheng-ye Li; Chang-wei Qiu; Gan-zhen Deng; Meng-yao Guo (Biological Trace Element Research, 2016)

Genetic Diversity Analysis of Sugarcane Germplasm Based on Fluorescence-Labeled Simple Sequence Repeat Markers and a Capillary Electrophoresis-based Genotyping Platform - Qian You; Yong-Bao Pan; Li-Ping Xu; Shi-Wu Gao; Qin-Nan Wang; Ya-Chun Su; Yong-Qing Yang; Qi-Bin Wu; Ding-Gang Zhou; You-Xiong Que (Sugar Tech, 2016)

Advances on Bioactive Polysaccharides from Medicinal Plants - Jian-Hua Xie; Ming-Liang Jin; Gordon A. Morris; Xue-Qiang Zha; Han-Qing Chen; Yang Yi; Jing-En Li; Zhi-Jun Wang; Jie Gao; Shao-Ping Nie; Peng Shang; Ming-Yong Xie (Critical Reviews in Food Science and Nutrition, 2016)

Effect of CO 2 on Chemical and Microbial Changes of Pacific White Shrimp During Modified Atmosphere Packaging - Yun-Fang Qian; Jing Xie; Sheng-Ping Yang; Wen-Hui Wu; Qing Xiong; Zhi-Li Gao; Jian-Bing Shi (Journal of Aquatic Food Product Technology, 2016)

Changes and characteristics of dissolved organic matter in a constructed wetland system using fluorescence spectroscopy - Yuan Yao; Yun-zhen Li; Xu-jing Guo; Tao Huang; Ping-ping Gao; Ying-pei Zhang; Feng Yuan (Environmental Science and Pollution Research, 2016)

Calcitriol regulates angiotensin-converting enzyme and angiotensin converting-enzyme 2 in diabetic kidney disease - Mei Lin; Ping Gao; Tianya Zhao; Lei He; Mengshi Li; Yaoyao Li; Hua Shui; Xiaoyan Wu (Molecular Biology Reports, 2016)

Calpain-Dependent ErbB4 Cleavage Is Involved in Brain Ischemia-Induced Neuronal Death - Ying-mei Lu; Yin-ping Gao; Rong-rong Tao; Mei-hua Liao; Ji-yun Huang; Gang Wu; Feng Han; Xiao-ming Li (Molecular Neurobiology, 2016)

On the variability of near-bed floc size due to complex interactions between turbulence, SSC, settling velocity, effective density and the fractal dimension of flocs - Yang Yang; Ya Ping Wang; Chunyan Li; Shu Gao; Benwei Shi; Liang Zhou; Dandan Wang; Gaocong Li; Chen Dai (Geo-Marine Letters, 2016)

Sediment resuspension in tidally dominated coastal environments: new insights into the threshold for initial movement - Yang Yang; Ya Ping Wang; Shu Gao; Xiao Hua Wang; Ben Wei Shi; Liang Zhou; Dan Dan Wang; Chen Dai; Gao Cong Li (Ocean Dynamics, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Effect of fish oil supplement in maintenance hemodialysis patients: a systematic review and meta-analysis of published randomized controlled trials - Lei He; Meng-si Li; Mei Lin; Tian-ya Zhao; Ping Gao (European Journal of Clinical Pharmacology, 2016)

Molecular and pathogenicity characterization of Gallid herpesvirus 2 newly isolated in China from 2009 to 2013 - Yan-ping Zhang; Hong-chao Lv; Ke-yan Bao; Yu-long Gao; Hong-lei Gao; Xiao- le Qi; Hong-yu Cui; Yong-qiang Wang; Kai Li; Li Gao; Xiao-mei Wang; Chang-jun Liu (Virus Genes, 2016)

Effects of sialidase NEU1 siRNA on proliferation, apoptosis, and invasion in human ovarian cancer - Li-rong Ren; Li-ping Zhang; Shu-ying Huang; Yuan-fang Zhu; Wen-juan Li; Shan-yu Fang; Li Shen; Yan-ling Gao (Molecular and Cellular Biochemistry, 2016)

Paleo-environmental evolution based on high-resolution phytolith since 26 ka B. P. in Huanghe River Delta - Ping Li; Jun Du; Na Du; Wei Gao (Acta Oceanologica Sinica, 2016)

Remarkable Activation of the Complement System and Aberrant Neuronal Localization of the Membrane Attack Complex in the Brain Tissues of Scrapie-Infected Rodents - Yan Lv; Cao Chen; Bao-Yun Zhang; Kang Xiao; Jing Wang; Li-Na Chen; Jing Sun; Chen Gao; Qi Shi; Xiao-Ping Dong (Molecular Neurobiology, 2015)

Total glycosides of Yupingfeng protects against bleomycin-induced pulmonary fibrosis in rats associated with reduced high mobility group box 1 activation and epithelial–mesenchymal transition - Wenhui Cui; Liucheng Li; Delin Li; Xiaoting Mo; Wencheng Zhou; Zhihui Zhang; Liang Xu; Ping Zhao; Lianwen Qi; Ping Li; Jian Gao (Inflammation Research, 2015)

Effect of inbreeding on growth and genetic diversity of Portunus trituberculatus based on the full-sibling inbreeding families - Baoquan Gao; Ping Liu; Jian Li; Qingyin Wang; Zhike Han (Aquaculture International, 2015)

The miR-573/apoM/Bcl2A1-dependent signal transduction pathway is essential for hepatocyte apoptosis and hepatocarcinogenesis - Yan-Wei Hu; Zhi-Ping Chen; Xiu-Mei Hu; Jia-Yi Zhao; Jin-Lan Huang; Xin Ma; Shu-Fen Li; Yu-Rong Qiu; Xiao-Juan Wu; Yan-Hua Sha; Ji-Juan Gao; Yan-Chao Wang; et al. (Apoptosis, 2015)

Anti-inflammatory effect of procyanidin B1 on LPS-treated THP1 cells via interaction with the TLR4–MD-2 heterodimer and p38 MAPK and NF-κB signaling - Jing Xing; Rui Li; Nan Li; Jian Zhang; Yueqing Li; Ping Gong; Dongna Gao; Hui Liu; Yu Zhang (Molecular and Cellular Biochemistry, 2015)

The characteristics of consolidation settlement and its contribution to the topographical change in the northern modern Huanghe River subaqueous delta in China - Jie Liu; Ping Li; Xiao Liu; Yuanqin Xu; Wei Gao (Acta Oceanologica Sinica, 2015)

Identification of volatile and softening-related genes using digital gene expression profiles in melting peach - Xiong-wei Li; Jun Jiang; Li-ping Zhang; Yi Yu; Zheng-wen Ye; Xiu-min Wang; Jing-yi Zhou; Ming-liang Chai; Hui-qin Zhang; Pere Arús; Hui-juan Jia; Zhong-shan Gao (Tree Genetics & Genomes, 2015)

GRY79 encoding a putative metallo-β-lactamase-trihelix chimera is involved in chloroplast development at early seedling stage of rice - Chunmei Wan; Chunmei Li; Xiaozhi Ma; Yang Wang; Changhui Sun; Rui Huang; Ping Zhong; Zhiyan Gao; Dan Chen; Zhengjun Xu; Jianqing Zhu; Xiaoling Gao; et al. (Plant Cell Reports, 2015)

Endoplasmic Reticulum Protein 29 Protects Axotomized Neurons from Apoptosis and Promotes Neuronal Regeneration Associated with Erk Signal - Yun-Hui Zhang; Visar Belegu; Yu Zou; Fang Wang; Bao-Jiang Qian; Ran Liu; Ping Dai; Wei Zhao; Fa-Bao Gao; Lei Wang; Li-Mei Cao; John W. McDonald; et al. (Molecular Neurobiology, 2015)

Activation of VEGF/Flk-1-ERK Pathway Induced Blood–Brain Barrier Injury After Microwave Exposure - Li-Feng Wang; Xiang Li; Ya-Bing Gao; Shui-Ming Wang; Li Zhao; Ji Dong; Bin-Wei Yao; Xin-Ping Xu; Gong-Min Chang; Hong-Mei Zhou; Xiang-Jun Hu; Rui-Yun Peng (Molecular Neurobiology, 2015)

AcSKP1, a multiplex PCR-based co-dominant marker in complete linkage disequilibrium with the male-fertility restoration (Ms) locus, and its application in open-pollinated populations of onion - Yu Meng Huo; Bing Jiang Liu; Yan Yan Yang; Jun Miao; Li Min Gao; Su Ping Kong; Zhen Bao Wang; Hidemi Kitano; Xiong Wu (Euphytica, 2015)

Effects of Fluoride on DNA Damage and Caspase-Mediated Apoptosis in the Liver of Rats - Guo Hua Song; Fu Bing Huang; Ji Ping Gao; Mao Lin Liu; Wen Biao Pang; Wei bin Li; Xiao Yan Yan; Mei Jun Huo; Xia Yang (Biological Trace Element Research, 2015)

Elevated Serum Homocysteine (Hcy) Levels May Contribute to the Pathogenesis of Cerebral Infarction - Hong-Juan Fu; Li-Bo Zhao; Ju-Jun Xue; Zhi-Xuan Wu; Yue-Ping Huang; Wei Liu; Zhan Gao (Journal of Molecular Neuroscience, 2015)

All-trans retinoic acid up-regulates the human CD2AP gene expression through Sp1/Sp3 binding sites - Hua-Guo Xu; Rui Jin; Shan Gao; Wei Ren; Li Zou; Lifei Liu; Guo-Ping Zhou (Immunologic Research, 2015)

Molecular cloning, characterization and expression of the energy homeostasis-associated gene in piglet - Sheng-ping Wang; Yun-ling Gao; Gang Liu; Dun Deng; Rong-jun Chen; Yu-zhe Zhang; Li-li Li; Qing-qi Wen; Yong-qing Hou; Ze-meng Feng; Zhao-hui Guo (Journal of Zhejiang University-SCIENCE B, 2015)

Ectopic expression of a phytochrome B gene from Chinese cabbage (Brassica rapa L. ssp. pekinensis) in Arabidopsis thaliana promotes seedling de-etiolation, dwarfing in mature plants, and delayed flowering - Mei-Fang Song; Shu Zhang; Pei Hou; Hong-Zhong Shang; Hai-Ke Gu; Jing-Juan Li; Yang Xiao; Lin Guo; Liang Su; Jian-Wei Gao; Jian-Ping Yang (Plant Molecular Biology, 2015)

Evaluation of pedotransfer functions for estimating saturated hydraulic conductivity in coastal salt-affected mud farmland - Rong-Jiang Yao; Jing-Song Yang; Dan-Hua Wu; Fu-Rong Li; Peng Gao; Xiang-Ping Wang (Journal of Soils and Sediments, 2015)

Transcriptome Profiling Identified Multiple Jasmonate ZIM-Domain Proteins Involved in the Regulation of Alkaloid Biosynthesis in Tobacco BY-2 Cells - Yuping Yang; Jing Guo; Pengcheng Yan; Yunshuang Li; Kun Liu; Ping Gao; Heping Zhao; Yubao Chen; Yingdian Wang; Michael P. Timko; Shengcheng Han (Plant Molecular Biology Reporter, 2015)

Urgent landslide susceptibility assessment in the 2013 Lushan earthquake-impacted area, Sichuan Province, China - Zhi-hua Yang; Heng-xing Lan; Xing Gao; Lang-ping Li; Yun-shan Meng; Yu-ming Wu (Natural Hazards, 2015)

Effect of salt treatment on growth, isoenzymes and metabolites of Andrographis paniculata (Burm. f.) Nees - Yan-hua Shao; Jun-li Gao; Xiang-wei Wu; Qian Li; Jian-gang Wang; Ping Ding; Xiao-ping Lai (Acta Physiologiae Plantarum, 2015)

Genome-wide discovery of novel and conserved microRNAs in white shrimp (Litopenaeus vannamei) - Qian-Yun Xi; Yuan-Yan Xiong; Yuan-Mei Wang; Xiao Cheng; Qi-En Qi; Gang Shu; Song-Bo Wang; Li-Na Wang; Ping Gao; Xiao-Tong Zhu; Qing-Yan Jiang; Yong-Liang Zhang; et al. (Molecular Biology Reports, 2015)

Asymmetric dimethylarginine triggers macrophage apoptosis via the endoplasmic reticulum stress pathway - Dan Hong; Hai-Chao Gao; Xiang Wang; Ling-Fang Li; Chuan-Chang Li; Ying Luo; Kang-Kai Wang; Yong-Ping Bai; Guo-Gang Zhang (Molecular and Cellular Biochemistry, 2015)

Influence of PTGS1, PTGFR, and MRP4 genetic variants on intraocular pressure response to latanoprost in Chinese primary open-angle glaucoma patients - Li-chen Gao; Di Wang; Fang-qun Liu; Zheng-yu Huang; Hong-guang Huang; Gui-hua Wang; Xi Chen; Qun-zhi Shi; Li Hong; Li-ping Wu; Jie Tang (European Journal of Clinical Pharmacology, 2015)

Upregulation of HIF-1α Via Activation of ERK and PI3K Pathway Mediated Protective Response to Microwave-Induced Mitochondrial Injury in Neuron-Like Cells - Li Zhao; Yue-Feng Yang; Ya-Bing Gao; Shui-Ming Wang; Li-Feng Wang; Hong-Yan Zuo; Ji Dong; Xin-Ping Xu; Zhen-Tao Su; Hong-Mei Zhou; Ling-Ling Zhu; Rui-Yun Peng (Molecular Neurobiology, 2014)

Isolation and molecular characterization of an ethylene response factor NtERF1-1 in Nicotiana tabacum cv. Xanthi - Jun-Shan Gao; Li Hu; Peng Xie; Yan Meng; Yong-Ping Cai; Yi Lin (Journal of Biosciences, 2014)

Optimal intervention time of vagal stimulation attenuating myocardial ischemia/reperfusion injury in rats - Qiang Wang; Rui-Ping Li; Fu-Shan Xue; Shi-Yu Wang; Xin-Long Cui; Yi Cheng; Gao-Pu Liu; Xu Liao (Inflammation Research, 2014)

ABI-like transcription factor gene TaABL1 from wheat improves multiple abiotic stress tolerances in transgenic plants - Dong-Bei Xu; Shi-Qing Gao; You-Zhi Ma; Zhao-Shi Xu; Chang-Ping Zhao; Yi-Miao Tang; Xue-Yin Li; Lian-Cheng Li; Yao-Feng Chen; Ming Chen (Functional & Integrative Genomics, 2014)

Analyses of the Similarity and Difference of Global Gene Expression Profiles in Cortex Regions of Three Neurodegenerative Diseases: Sporadic Creutzfeldt-Jakob Disease (sCJD), Fatal Familial Insomnia (FFI), and Alzheimer’s Disease (AD) - Chan Tian; Di Liu; Wei Xiang; Hans A. Kretzschmar; Qing-Lan Sun; Chen Gao; Yin Xu; Hui Wang; Xue-Yu Fan; Ge Meng; Wei Li; Xiao-Ping Dong (Molecular Neurobiology, 2014)

Recycling of sediment into the mantle source of K-rich mafic rocks: Sr–Nd–Hf–O isotopic evidence from the Fushui complex in the Qinling orogen - Hao Wang; Yuan-Bao Wu; Chao-Ran Li; Tian-Yu Zhao; Zheng-Wei Qin; Liu-Qin Zhu; Shan Gao; Jian-Ping Zheng; Xiao-Ming Liu; Lian Zhou; Yang Zhang; Sai-Hong Yang (Contributions to Mineralogy and Petrology, 2014)

Toxic effects of sodium fluoride on cell proliferation and apoptosis of Leydig cells from young mice - Guo hua Song; Rui Li Wang; Zhao Yang Chen; Bin Zhang; Hai Long Wang; Mao Lin Liu; Ji Ping Gao; Xiao Yan Yan (Journal of Physiology and Biochemistry, 2014)

New natural hosts of Tomato yellow leaf curl virus identified in and near tomato-growing greenhouses in eastern China - Gang Li; Li-ming Zhao; Xiang Wang; Ying Gao; Guo-zhen Sun; Xiao-ping Zhu (Journal of General Plant Pathology, 2014)

Assessment of dietary phytoestrogen intake via plant-derived foods in China - Xiao Juan Hu; Wan Rui Song; Li Ying Gao; Shao Ping Nie; Gerhard Eisenbrand; Ming Yong Xie (Food Additives & Contaminants: Part A, 2014)

Bimodal voltage dependence of TRPA1: mutations of a key pore helix residue reveal strong intrinsic voltage-dependent inactivation - Xia Wan; Yungang Lu; Xueqin Chen; Jian Xiong; Yuanda Zhou; Ping Li; Bingqing Xia; Min Li; Michael X. Zhu; Zhaobing Gao (Pflügers Archiv - European Journal of Physiology, 2014)

Aquaporin-4 Mitigates Retrograde Degeneration of Rubrospinal Neurons by Facilitating Edema Clearance and Glial Scar Formation After Spinal Cord Injury in Mice - Qi Wu; Yong-Jie Zhang; Jun-Ying Gao; Xiu-Miao Li; Hui Kong; Yi-Ping Zhang; Ming Xiao; Christopher B. Shields; Gang Hu (Molecular Neurobiology, 2014)

Characterization of OsDREB6 responsive to osmotic and cold stresses in rice - Ya-Guang Ke; Zhi-Jun Yang; Shun-Wu Yu; Tian-Fei Li; Jin-Hong Wu; Huan Gao; Ya-Ping Fu; Li-Jun Luo (Journal of Plant Biology, 2014)

Identification of BACH2 as a susceptibility gene for Graves’ disease in the Chinese Han population based on a three-stage genome-wide association study - Wei Liu; Hai-Ning Wang; Zhao-Hui Gu; Shao-Ying Yang; Xiao-Ping Ye; Chun-Ming Pan; Shuang-Xia Zhao; Li-Qiong Xue; Hui-Jun Xie; Sha-Sha Yu; Cui-Cui Guo; Wen-Hua Du; et al. (Human Genetics, 2014)

Haplotype analysis of TLR4 gene and its effects on milk somatic cell score in Chinese commercial cattle - Xing Ping Wang; Zhuo Ma Luoreng; Shu Xin Gao; Dong Sheng Guo; Jun Ya Li; Xue Gao; Shang Zhong Xu; Feng Li; Gang Chen; Jin Ren Wang (Molecular Biology Reports, 2014)

Myocardial mitochondrial oxidative stress and dysfunction in intense exercise: regulatory effects of quercetin - Chao Gao; Xiaoqian Chen; Juan Li; Yanyan Li; Yuhan Tang; Liang Liu; Shaodan Chen; Haiyan Yu; Liegang Liu; Ping Yao (European Journal of Applied Physiology, 2014)

Endothelial Insulin-Like Growth Factor-1 Modulates Proliferation and Phenotype of Smooth Muscle Cells Induced by Low Shear Stress - Lu Wang; Yue Han; Yan Shen; Zhi-Qiang Yan; Ping Zhang; Qing-Ping Yao; Bao-Rong Shen; Li-Zhi Gao; Ying-Xin Qi; Zong-Lai Jiang (Annals of Biomedical Engineering, 2014)

Photosynthetic activity and efficiency of Bothriochloa ischaemum and Lespedeza davurica in mixtures across growth periods under water stress - Wei-Zhou Xu; Xi-Ping Deng; Bing-Cheng Xu; Zhi-Juan Gao; Wen-Li Ding (Acta Physiologiae Plantarum, 2014)

Coal-burning endemic fluorosis is associated with reduced activity in antioxidative enzymes and Cu/Zn-SOD gene expression - Qi Wang; Kang-ping Cui; Yuan-yuan Xu; Yan-ling Gao; Jing Zhao; Da-sheng Li; Xiao-lei Li; Hou-jin Huang (Environmental Geochemistry and Health, 2014)

cDNA cloning, characterization and expression analysis of peroxiredoxin 5 gene in the ridgetail white prawn Exopalaemon carinicauda - Yafei Duan; Ping Liu; Jitao Li; Jian Li; Baoquan Gao; Ping Chen (Molecular Biology Reports, 2013)

Activation of BKCa Channels Mediates Hippocampal Neuronal Death After Reoxygenation and Reperfusion - Ming Chen; Hong-Yu Sun; Ping Hu; Chun-Fei Wang; Bo-Xing Li; Shu-Ji Li; Jian-Jun Li; Hui-Ying Tan; Tian-Ming Gao (Molecular Neurobiology, 2013)

The cloning of the cdk2 transcript and the localization of its expression during gametogenesis in the freshwater giant prawn, Macrobrachium rosenbergii - Jie Chen; Ping Liu; Zhen Li; Ying Chen; Gao-Feng Qiu (Molecular Biology Reports, 2013)

Comparative Analysis of Gene Expression Profiles Between Cortex and Thalamus in Chinese Fatal Familial Insomnia Patients - Chan Tian; Di Liu; Qing-Lan Sun; Chen Chen; Yin Xu; Hui Wang; Wei Xiang; Hans A Kretzschmar; Wei Li; Cao Chen; Qi Shi; Chen Gao; et al. (Molecular Neurobiology, 2013)

Effects of temperature, pH, and UV radiation on alkaline phosphatase activity in the terrestrial cyanobacterium Nostoc flagelliforme - Ping Li; Wenhua Liu; Kunshan Gao (Journal of Applied Phycology, 2013)

1H-MRS Assessment of the Therapeutic Effect of Bilateral Intraventricular BDNF Infusion into APP/PS1 Double Transgenic Mice - Wei Zhang; Pei-jun Wang; Ming-hua Li; Guo-liang Wang; Ping Li; Xiao-long Gao (Journal of Molecular Neuroscience, 2013)

β-receptor blocker influences return of spontaneous circulation and chemical examination in rats during cardiopulmonary resuscitation - Xiao-jing Zhao; Zhuo Pen; Ping Li; Er-xiu Chen; Jian Liu; Yan-xia Gao; Yun-xia Ren; Li-jun Li (Journal of Zhejiang University-SCIENCE B, 2013)

Reducing the oxidative stress mediates the cardioprotection of bicyclol against ischemia-reperfusion injury in rats - Jie Cui; Zhi Li; Ling-bo Qian; Qin Gao; Jue Wang; Meng Xue; Xiao-e Lou; Iain C. Bruce; Qiang Xia; Hui-ping Wang (Journal of Zhejiang University-SCIENCE B, 2013)

Syntheses and antibacterial activity of Schiff bases from 16-isopropyl-5, 9-dimethyltetracyclo [10.2.2.0 1, 10 .0 4, 9 ] hexadec-15-ene-5, 14-dicarboxylic acid - Jian Li; Jie Song; Shi-Bin Shang; Xiao-Ping Rao; Yan-Qing Gao (Natural Product Research, 2013)

Identification of two SCAR markers co-segregated with the dominant Ms and recessive ms alleles in onion (Allium cepa L.) - Yan Yan Yang; Yu Meng Huo; Jun Miao; Bing Jiang Liu; Su Ping Kong; Li Min Gao; Chang Liu; Zhen Bao Wang; Yasuki Tahara; Hidemi Kitano; Xiong Wu (Euphytica, 2013)

Responses of two dominant plant species to drought stress and defoliation in the Inner Mongolia Steppe of China - Li-Ping Chen; Nian-Xi Zhao; Li-Hong Zhang; Yu-Bao Gao (Plant Ecology, 2013)

Mutations in AP22.65 accelerate flowering in Arabidopsis thaliana - Ji Hong Xing; Feng Ru Wang; Jiao Jia; Jing Zhang; Li Li; Zhan Chen; Qiao Yun Weng; Ping Yang; Ye Zhang; Bin Zhao; He Long Si; Jin Gao Dong; et al. (Journal of Plant Biology, 2013)

Fluid evolution of the Jiawula Ag–Pb–Zn deposit, Inner Mongolia: mineralogical, fluid inclusion, and stable isotopic evidence - De-Gao Zhai; Jia-Jun Liu; Jian-Ping Wang; Mei-Juan Yao; Sheng-Hua Wu; Chao Fu; Zhen-Jiang Liu; Shou-Guang Wang; Yu-Xi Li (International Geology Review, 2013)

Impacts of polar vortex, NPO, and SST configurations on unusually cool summers in Northeast China. Part I: Analysis and diagnosis - Yi Lian; Baizhu Shen; Shangfeng Li; Bin Zhao; Zongting Gao; Gang Liu; Ping Liu; Ling Cao (Advances in Atmospheric Sciences, 2013)

Expulsion of selenium/protein nanoparticles through vesicle-like structures by Saccharomyces cerevisiae under microaerophilic environment - Liang Zhang; Daping Li; Ping Gao (World Journal of Microbiology and Biotechnology, 2012)

cDNA cloning, characterization and expression analysis of catalase in swimming crab Portunus trituberculatus - Ping Chen; Jitao Li; Ping Liu; Baoquan Gao; Qingyin Wang; Jian Li (Molecular Biology Reports, 2012)

Molecular diversity of restriction enzyme sites, Indels and upstream open reading frames (uORFs) of 5′ untransalted regions (UTRs) of Waxy genes in Triticum L. and Aegilops L. species - Wei Li; Zhen Gao; Wei Xiao; Yu-Ming Wei; Ya-Xi Liu; Guo-Yue Chen; Zhi-En Pu; Hua-Ping Chen; You-Liang Zheng (Genetic Resources and Crop Evolution, 2012)

A Comparison of the Biological Activities of Human Osteoblast hFOB1.19 Between Iron Excess and Iron Deficiency - Guo-yang Zhao; Li-ping Zhao; Yin-feng He; Guang-Fei Li; Chao Gao; Kai Li; You-jia Xu (Biological Trace Element Research, 2012)

Quaternary palaeoenvironmental oscillations drove the evolution of the Eurasian Carassius auratus complex (Cypriniformes, Cyprinidae) - Yun Gao; Shu‐Yan Wang; Jing Luo; Robert W. Murphy; Rui Du; Shi‐Fang Wu; Chun‐Ling Zhu; Yan Li; Andrei D. Poyarkov; Sang Ngoc Nguyen; Peng‐Tao Luan; Ya‐Ping Zhang (Journal of Biogeography, 2012)
Aim We sought to reconstruct the spatio‐temporal genetic diversification in goldfish of the Carassius auratus complex, which is widely distributed in Eurasia, to test whether vicariance events or human‐mediated translocations best explained lineage divergence and genogeographical history. Location East Asia and the Oriental islands including Japan, the Ryukyus and Taiwan, and Europe, including Russia and the Czech Republic. Methods We reconstructed the matrilineal history of Eurasian goldfish using 1876 sequences from the partial mitochondrial DNA control region (426 bp) and 191 complete sequences of cytochrome b (1140 bp) from 67 localities representing most of the range of the species. Divergence times were estimated using a Bayesian Markov chain Monte Carlo approach based either on molecular clock data or on the fossil record. Genetic structure and the historical demography of populations were analysed using partial correlation tests and analyses of molecular variance. Results Three lineages had high levels of regional specificity. Lineages A and B from the main islands of Japan differed greatly from lineage C, which occurred on the mainland, Taiwan and the Ryukyus. Lineages A and B had late Pliocene origins. Six geographically constrained sublineages within lineage C had near‐simultaneous mid‐Pleistocene divergences. Main conclusions Genetic structure in the C. auratus complex appears to have been driven by palaeoenvironmental perturbations rather than human translocations. The disappearance of a land bridge in the Tsushima Strait around 3.0 Ma is responsible for the separation of Japanese and continental lineages; the estimated divergence time is 2.75–2.32 Ma. Fujian, China and Vietnam appear to have provided important refugia for the C. auratus complex during glaciation. After warm, moist summer monsoons intensified during the mid‐Pleistocene, goldfish are likely to have dispersed north‐eastwards to recolonize the Ryukyus via Taiwan and northwards to recolonize mainland China.

Neuroprotective properties of aucubin in diabetic rats and diabetic encephalopathy rats - Hong Yu Xue; Ya Nan Lu; Xue Mei Fang; Yong Ping Xu; Gui Zhen Gao; Li Ji Jin (Molecular Biology Reports, 2012)

Fluid Flow-Induced Calcium Response in Early or Late Differentiated Osteoclasts - Ping Li; Man Hu; Shujin Sun; Yan Zhang; Yuxin Gao; Mian Long; Bo Huo; Ding Zhang (Annals of Biomedical Engineering, 2012)

The evolution and utility of ribosomal ITS sequences in Bambusinae and related species: divergence, pseudogenes, and implications for phylogeny - HUI-XING SONG; SU-PING GAO; MING-YAN JIANG; GUANG-LI LIU; XIAO-FANG YU; QI-BING CHEN (Journal of Genetics, 2012)

Effects of insulin-like growth factor-1 on the properties of mesenchymal stem cells in vitro - Yu-li Huang; Ruo-feng Qiu; Wei-yi Mai; Jian Kuang; Xiao-yan Cai; Yu-gang Dong; Yun-zhao Hu; Yuan-bin Song; An-ping Cai; Zhi-gao Jiang (Journal of Zhejiang University-SCIENCE B, 2012)

Erratum to: Effects of proNGF on Neuronal Viability, Neurite Growth and Amyloid-beta Metabolism - Yan-Jiang Wang; Deborah Valadares; Ying Sun; Xin Wang; Jin-Hua Zhong; Xiao-Hong Liu; Shohreh Majd; Li Chen; Chang-Yue Gao; Si Chen; Yoon Lim; Anthony Pollard; et al. (Neurotoxicity Research, 2011)

A Novel PrP Partner HS-1 Associated Protein X-1 (HAX-1) Protected the Cultured Cells Against the Challenge of H2O2 - Yuan-Yuan Jing; Xiao-Li Li; Qi Shi; Zhao-Yun Wang; Yan Guo; Ming-Ming Pan; Chan Tian; Shu-Ying Zhu; Cao Chen; Han-Shi Gong; Jun Han; Chen Gao; et al. (Journal of Molecular Neuroscience, 2011)

Microsatellite Analysis of Homozygosity Progression of Heterozygous Genotypes Segregating in the Rice Subspecies Cross Pei’ai64s/Nipponbare - Yong-shu Liang; Qi-jun Zhang; Shi-quan Wang; Li-yong Cao; Zhi-qiang Gao; Ping Li; Shi-hua Cheng (Biochemical Genetics, 2011)

Aboveground dominant functional group predicts belowground properties in an alpine grassland community of western China - Gao-Lin Wu; Wei Li; Zhi-Hua Shi; Zhou-Ping Shangguan (Journal of Soils and Sediments, 2011)

Identification and expression analysis of two growth hormone receptors in zanzibar tilapia (Oreochromis hornorum) - Feng-Ying Gao; Mai-Xin Lu; Xing Ye; Zhang-Han Huang; Huan Wang; Hua-Ping Zhu; Li-Ping Yang (Fish Physiology and Biochemistry, 2011)

Aucubin modulates Bcl-2 family proteins expression and inhibits caspases cascade in H2O2-induced PC12 cells - Hong Yu Xue; Dong Yan Niu; Gui Zhen Gao; Qiu Ye Lin; Li Ji Jin; Yong Ping Xu (Molecular Biology Reports, 2011)

Interaction of green tea polyphenol epigallocatechin-3-gallate with sunitinib: potential risk of diminished sunitinib bioavailability - Jun Ge; Ben-Xu Tan; Ye Chen; Li Yang; Xing-Chen Peng; Hong-Ze Li; Hong-Jun Lin; Yu Zhao; Meng Wei; Ke Cheng; Long-Hao Li; Hang Dong; et al. (Journal of Molecular Medicine, 2011)

Molecular characterisation of cereal cyst nematodes in winter wheat on the Huang-Huai floodplain of China using RFLP and rDNA-ITS sequence analyses - Bo Fu; Hong-xia Yuan; Yu Zhang; Xing-song Hou; Gao-lei Nian; Peng Zhang; Xiao-ping Xing; Bing-jian Sun; Ian T. Riley; Hong-lian Li (Australasian Plant Pathology, 2011)

The soybean GmbZIP1 transcription factor enhances multiple abiotic stress tolerances in transgenic plants - Shi-Qing Gao; Ming Chen; Zhao-Shi Xu; Chang-Ping Zhao; Liancheng Li; Hui-jun Xu; Yi-miao Tang; Xin Zhao; You-Zhi Ma (Plant Molecular Biology, 2011)

Efficacy of a novel endotoxin adsorber polyvinylidene fluoride fiber immobilized with L-serine ligand on septic pigs - Jian-ping Gao; Man Huang; Ning Li; Peng-fei Wang; Huan-lin Chen; Qiu-ping Xu (Journal of Zhejiang University-SCIENCE B, 2011)

Molecular characterization and expression analysis of extracellular copper–zinc superoxide dismutase gene from swimming crab Portunus trituberculatus - Jitao Li; Ping Chen; Ping Liu; Baoquan Gao; Qingyin Wang; Jian Li (Molecular Biology Reports, 2011)

Cytosolic PrP Induces Apoptosis of Cell by Disrupting Microtubule Assembly - Xiao-Li Li; Gui-Rong Wang; Yuan-Yuan Jing; Ming-Ming Pan; Chen-Fang Dong; Rui-Min Zhou; Zhao-Yun Wang; Qi Shi; Chen Gao; Xiao-Ping Dong (Journal of Molecular Neuroscience, 2011)

Adiponectin reduces C-reactive protein expression and downregulates STAT3 phosphorylation induced by IL-6 in HepG2 cells - Haiyun Sun; Yingnan Zhang; Ping Gao; Qiang Li; Yuqian Sun; Jinchao Zhang; Changqing Xu (Molecular and Cellular Biochemistry, 2011)

Chromosomal localization of rDNA genes and genomic organization of 5S rDNA in Oreochromis mossambicus, O. urolepis hornorum and their hybrid - Hua Ping Zhu; Mai Xin Lu; Feng Ying Gao; Zhang Han Huang; Li Ping Yang; Jian Fang Gui (Journal of Genetics, 2010)

Application of collagen-chitosan/fibrin glue asymmetric scaffolds in skin tissue engineering - Chun-mao Han; Li-ping Zhang; Jin-zhang Sun; Hai-fei Shi; Jie Zhou; Chang-you Gao (Journal of Zhejiang University-SCIENCE B, 2010)

Effects of proNGF on Neuronal Viability, Neurite Growth and Amyloid-beta Metabolism - Yan-Jiang Wang; Deborah Valadares; Ying Sun; Xin Wang; Jin-Hua Zhong; Xiao-Hong Liu; Shohreh Majd; Li Chen; Chang-Yue Gao; Si Chen; Yoon Lim; Anthony Pollard; et al. (Neurotoxicity Research, 2010)

Spatial and seasonal characterization of net primary productivity and climate variables in southeastern China using MODIS data - Dai-liang Peng; Jing-feng Huang; Alfredo R. Huete; Tai-ming Yang; Ping Gao; Yan-chun Chen; Hui Chen; Jun Li; Zhan-yu Liu (Journal of Zhejiang University-SCIENCE B, 2010)

Prediction of summer grain crop yield with a process-based ecosystem model and remote sensing data for the northern area of the Jiangsu Province, China - Weimin Ju; Ping Gao; Yanlian Zhou; Jing M. Chen; Shu Chen; Xianfeng Li (International Journal of Remote Sensing, 2010)

Manganese-induced changes of the biochemical characteristics of the recombinant wild-type and mutant PrPs - Xiao-Li Li; Chen-Fang Dong; Gui-Rong Wang; Rui-Min Zhou; Qi Shi; Chan Tian; Chen Gao; Guo-Yong Mei; Cao Chen; Kun Xu; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2009)

Intercellular adhesion molecule-1 gene K469E polymorphism and ischemic stroke: a case-control study in a Chinese population - Xiao Xia Li; Jian Ping Liu; Jin Quan Cheng; Sheng Hong Han; Yi Jie Geng; Sheng Wei; Shi Tong Gao; Da Na Huang; Shao Fa Nie (Molecular Biology Reports, 2009)

Molecular Cloning, Expression, and Chromosomal Mapping of the Porcine CDC-2-Like Kinase 1 (CLK1) Gene - Shui Hua Xie; Jia Qi Li; Yao Sheng Chen; Ping Gao; Hao Zhang; Ze Yue Li (Biochemical Genetics, 2009)

Differential belowground allelopathic effects of leaf and root of Mikania micrantha - Ai-Ping Wu; Hua Yu; Shu-Qin Gao; Zhen-Ying Huang; Wei-Ming He; Shi-Li Miao; Ming Dong (Trees, 2009)

A cotton (Gossypium hirsutum) DRE-binding transcription factor gene, GhDREB, confers enhanced tolerance to drought, high salt, and freezing stresses in transgenic wheat - Shi-Qing Gao; Ming Chen; Lian-Qin Xia; Hui-Jun Xiu; Zhao-Shi Xu; Lian-Cheng Li; Chang-Ping Zhao; Xian-Guo Cheng; You-Zhi Ma (Plant Cell Reports, 2009)

Isolation and Description of a Stable Carbazole-Degrading Microbial Consortium Consisting of Chryseobacterium sp. NCY and Achromobacter sp. NCW - Weiqiang Guo; Daping Li; Yong Tao; Ping Gao; Jijun Hu (Current Microbiology, 2008)

Vimentin is required for dengue virus serotype 2 infection but microtubules are not necessary for this process - Wei Chen; Na Gao; Jia-li Wang; Yan-ping Tian; Zong-tao Chen; Jing An (Archives of Virology, 2008)

Triptolide protects against 1-methyl-4-phenyl pyridinium-induced dopaminergic neurotoxicity in rats: Implication for immunosuppressive therapy in Parkinson’s disease - Jun-Peng Gao; Shan Sun; Wen-Wei Li; Yi-Ping Chen; Ding-Fang Cai (Neuroscience Bulletin, 2008)

Mapping QTLs of root morphological traits at different growth stages in rice - Yanying Qu; Ping Mu; Hongliang Zhang; Charles Y. Chen; Yongming Gao; Yuxiu Tian; Feng Wen; Zichao Li (Genetica, 2008)

Human tau protein forms complex with PrP and some GSS- and fCJD-related PrP mutants possess stronger binding activities with tau in vitro - Xiao-Fan Wang; Chen-Fang Dong; Jin Zhang; Yan-Zhen Wan; Feng Li; Yin-Xia Huang; Lu Han; Bing Shan; Chen Gao; Jun Han; Xiao-Ping Dong (Molecular and Cellular Biochemistry, 2008)

Reduced expression of GSTM2 and increased oxidative stress in spontaneously hypertensive rat - Si-Gui Zhou; Ping Wang; Rong-Biao Pi; Jie Gao; Jia-Jia Fu; Jian Fang; Jia Qin; Hui-Jie Zhang; Rui-Fang Li; Shao-Rui Chen; Fu-Tian Tang; Pei-Qing Liu (Molecular and Cellular Biochemistry, 2008)

RNA interference (RNAi)-mediated vascular endothelial growth factor-C (VEGF-C) reduction interferes with lymphangiogenesis and enhances Epirubicin sensitivity of breast cancer cells - Ping Sun; Jie Gao; Yan-Li Liu; Lu-Wan Wei; Li-Ping Wu; Zhi-Yu Liu (Molecular and Cellular Biochemistry, 2008)

Successful tubes treatment of esophageal fistula - Ning Zhou; Wei-xing Chen; You-ming Li; Zhun Xiang; Ping Gao; Ying Fang (Journal of Zhejiang University-SCIENCE B, 2007)

Generation of genetic engineering monoclonal antibodies against prion protein - Yin-Xia Huang; Jun Han; Chen-Fang Dong; Li Sun; Chen Gao; Xiao-Fan Wang; Lu Han; Wei Zhou; Bao-Yun Zhang; Hui-Ying Jiang; Mi-Fang Liang; Xiao-Ping Dong (Medical Microbiology and Immunology, 2007)

Identification of poly-reactive natural IgM antibody that recognizes late apoptotic cells and promotes phagocytosis of the cells - Meng Fu; Ping-shen Fan; Wei Li; Cheng-xin Li; Ying Xing; Jing-gang An; Gang Wang; Xue-li Fan; Tian-wen Gao; Yu-feng Liu; Shigaku Ikeda (Apoptosis, 2007)

Short timescale air-sea coupling in the tropical deep convective regime - S. Gao; F. Ping; X. Cui; X. Li (Meteorology and Atmospheric Physics, 2006)

Streptomyces daliensis sp. nov. from soil - Ping Xu; Wen-Jun Li; Shu-Kun Tang; Hui-Ying Gao; Li-Hua Xu; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2006)

Cloud microphysical processes associated with the diurnal variations of tropical convection: A 2D cloud resolving modeling study - Shouting Gao; Fan Ping; Xiaofan Li (Meteorology and Atmospheric Physics, 2006)

Target HCV NS3 CD4+ Th1 Epitope to Major Histocompatibility Complex Class II Pathway - Ming Gao; Hai-Ping Wang; Yan-Ning Wang; Yong Zhou; Quan-Li Wang (Biotechnology Letters, 2006)

QTL mapping of root traits in a doubled haploid population from a cross between upland and lowland japonica rice in three environments - Zichao Li; Ping Mu; Chunping Li; Hongliang Zhang; Zhikang Li; Yongming Gao; Xiangkun Wang (Theoretical and Applied Genetics, 2005)

QTL mapping of phosphorus deficiency tolerance in soybean (Glycine max L. Merr.) - Yi-Dan Li; Yong-Jun Wang; Yi-Ping Tong; Ji-Guo Gao; Jin-Song Zhang; Shou-Yi Chen (Euphytica, 2005)

Estimation of ocean primary productivity and its spatio-temporal variation mechanism for East China Sea based on VGPM model - Guosheng Li; Ping Gao; Fang Wang; Qiang Liang (Journal of Geographical Sciences, 2004)

Effect of total alkaloid ofPeganum harmala L. in the treatment of experimental haemosporidian infections in cattle - Bingtang Fan; Jilan Liang; Jucheng Men; Fang Gao; Guangling Li; Sixi Zhao; Tingjun Hu; Ping Dang; Ling Zhang (Tropical Animal Health and Production, 1997)